Highly sensitive lateral flow immunoassays targeting PirA and PirB toxins for early on-site diagnosis of AHPND in shrimp - Chia-Chun Hsiao; You-Shan Cai; Shin-Yu Chou; Hung-Yun Lin; Shao-Chieh Yen; Han-Jia Lin; Shih-Chung Chang (Aquaculture, 2027)

Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Stratigraphy, sedimentology, and palaeoenvironment of dinosaur-bearing Upper Cretaceous Zhengyang Formation in Zhengyang Basin, Chongqing, Southwest China - Hui Dai; Jun Wang; Liang-Dong Luo; Qian-Ru Wen; Su-Chin Chang; Yu Lin; Ming Xiao; Hai Xing (Palaeoworld, 2026)

Life history strategy composition of fishes in the Yangtze River Basin and their response to the Ten-Year Fishing Ban - Lan Zhu; Dan Yu; Pengcheng Lin; Fei Liu; Tao Chang; Xin Gao; Mingzheng Li; Huanzhang Liu (Reviews in Fish Biology and Fisheries, 2026)

MEK inhibitor cobimetinib increases calreticulin and induces immune modulation in TNBC - Ling-Ming Tseng; Ka-Yi Lau; Ji-Lin Chen; Pei-Yi Chu; Chun-Teng Huang; Wan-Lun Wang; Yuan-Ya Chang; Jiun-I Lai; Chi-Cheng Huang; Ming-Shen Dai; Chun-Yu Liu (Journal of Molecular Medicine, 2026)
Immunogenic cell death (ICD) can activate immune cells and potentiate the response to immunotherapy. The mitogen-activated protein kinase (MAPK) signaling pathway regulates the immune response and mediates T-cell receptor signaling. Activation of the MAPK signaling pathway decreases the levels of tumor-infiltrating lymphocytes in triple-negative breast cancer (TNBC) and is associated with worse survival. Here, we investigated the potential of the MEK inhibitor cobimetinib as an ICD inducer in TNBC. We demonstrated that cobimetinib elicited hallmarks of ICD, including elevated levels of damage-associated molecular patterns. Ectopic ERK expression attenuated cobimetinib-induced CRT. Cobimetinib also evoked caspase-8 activation with increased Bax and Bak expression, while caspase inhibitor suppressed cobimetinib-induced CRT expression and apoptosis. In immunocompetent (BALB/c) mice bearing 4T1 tumors, cobimetinib exhibited stronger tumor growth inhibition than in immunodeficient (nude) mice, suggesting an immune-dependent antitumor effect. Furthermore, cobimetinib treatment increased the proportions of naïve CD8 + T cells and effector CD4 + T cells and decreases the proportion of myeloid-derived suppressor cells in immunocompetent mice bearing 4T1 tumors. Notably, we observed differential immunomodulatory effects of cobimetinib in tumor-bearing mice compared to non–tumor-bearing immunocompetent mice. Our findings indicate that MEK inhibition is associated with ICD-related molecular alterations, and that cobimetinib may contribute to immune modulation in TNBC.

Targeting EFEMP1 enhances chondrogenesis and inhibits hypertrophic differentiation in a spontaneous osteoarthritis mouse model - Yuhan Chang; Pei-Heng Jiang; Yung-Heng Hsu; Yu-Chih Lin; Chih-Chien Hu; Yi-Zhen Li; Steve Wen-Neng Ueng; Mei-Feng Chen (Journal of Molecular Medicine, 2026)

Selective recovery of palladium from actual acidic wastewater using a covalent triazine framework: The critical enabling role of chloride ions - Junyi Yu; Qingying Xiao; Ziwen Chang; Jianzhi Zhang; Hao Dong; Jiaochan Zhong; Lin Ding; Yidi Chen; Xubiao Luo; Penghui Shao (Water Research, 2026)

First record of Brachyphyllum (Cheirolepidiaceae) from the Lower Jurassic of the Ordos Basin, China: Paleogeographic and paleoclimatic implications linked to T-OAE - Chao-Hui Wei; Yun-Feng Li; Chang-Lu Zhang; Xiao Tan; Fei Liang; Chun-Lin Sun; Tao Li; Yu-Ling Na (Review of Palaeobotany and Palynology, 2026)

Palaeoenvironmental evolution and stage-dependent organic matter enrichment in the Late Permian Longtan Formation, Upper Yangtze Block, South China - Hai-Feng Chen; Xin Jin; Marcello Caggiati; Ting-Cong Ren; Bo Luo; Lin-Hao Fang; Hua-Wen Cao; Yang Liu; Chang-Cheng Huang; Bin Xiao; Zi-Han Ma; Hui-Dong Yu; et al. (Sedimentary Geology, 2026)

Phylogenomics and morphological evidence reveal a new genus Callibractia gen. Nov. (Apiaceae, Apioideae), a distinct alpine lineage of Sino-Himalaya shaped by uplift of the Pan-Tibetan Highlands - Zi-Xuan Li; Chang Peng; Xing-Jin He; Yu-Lin Xiao; Wei-Yan Tan; Li-Jia Liu; Song-Dong Zhou (Molecular Phylogenetics and Evolution, 2026)

Oxidation mechanism of rice bran protein components induced by microwave plasma: A perspective based on amino acid side chain modification - Chang Liu; Lin Li; Ruichi Guo; Xiangyu Du; Liqi Wang; Na Zhang; Dianyu Yu (Food Hydrocolloids, 2026)

Pre-transport dietary chitosan improves the physiological robustness of juvenile largemouth bass (Micropterus salmoides) by modulating antioxidant and inflammatory responses - Hong-Zheng Zhao; Yu-Lin Chang; Chang Wang; Yu-Yun He; Yi-Ran Zhao; Yi-Chen Dong; Xu-Xiong Huang; Guo-Fang Zhong (Fish & Shellfish Immunology, 2026)

LiCl@NH2-MIL-88b/Ta4C3TX/graphene aerogels for efficient atmospheric water harvesting - Yi’na Yang; Tianran Zhao; Liyang Zhao; Zikun Lin; Jia Chen; Chunna Yu; Chang Zhao; Guangjian Xing (Colloids and Surfaces C: Environmental Aspects, 2026)

Novel D-A1-A2-π-A self-assembled monolayer in suppressing the Voc deficit of the wide-bandgap perovskite solar cells - Dong-Tai Wu; Yu Hsuan Lin; Yi-Chen Lin; Hsin Li; Yu-Chen Liang; Yu-Tong Hung; Yi-Sheng Lin; Wei-Jia Qiu; Shi-Chun Liu; Yuan Jay Chang; Chieh-Ting Lin (Chemical Engineering Journal, 2026)

Electron-percolation-driven electric-field harmonization reprograms Zn nucleation for ultrastable Zn metal anodes - Jia-Sheng Lin; Daniel Chang; Che-Ning Yeh; Yi-Chun Yang; Hsing-Yu Tuan (Chemical Engineering Journal, 2026)

Immobilizing MIL-9 in PVDF spheres for durable and efficient peroxymonosulfate activation toward antibiotic degradation - Xing-Lin Lv; Peng Wang; Xiang-Yu Li; Fei Wang; Zi-Yu Jia; Miao Chang; Xin Jiang; Zhao-Yi Liu; Xiao-Hong Yi; Anping Wang; Jiguang Deng; Chong-Chen Wang (Chemical Engineering Journal, 2026)

Accumulation, elimination and biotransformation of paralytic shellfish toxins in ark shell Anadara kagoshimensis - Zhuo-Ru Lin; Hui-Xia Geng; Sara A. Cunha; Chang Xu; Ren-Cheng Yu (Marine Pollution Bulletin, 2026)

Research and application on the evolution law of secondary fractures in repeated mining strata of coal mines and gas prevention and control - Pengxiang Zhao; Zechen Chang; Shugang Li; Haifei Lin; Yu Shi; Jiajia Liu; Wenbo Pei; Jiaxin Zheng (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Enhanced simulations of overland-gully-sewer flow interactions in coupled three-layer dual drainage modeling - Chia-Ho Wang; Hsiang-Lin Yu; Tsang-Jung Chang; Albert S. Chen (Journal of Hydrology, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Cu-based MOFs@TiO2/PVDF composite membrane for efficient oil-water separation and bacterial isolation and sterilization - Lin-Lin Liu; Xue-Ling Zeng; Xuan Shi; Yu-Zhuo Fan; Wen-Yan Zeng; Ze-Hui Bai; Rong-Ke You; Xue-Qin Zhan; Fang-Chang Tsai; Ning Ma (Journal of Environmental Chemical Engineering, 2026)

Flexural bandgap of a metaplate carrying zigzag beam-mass systems - Jung-San Chen; Jie-Sheng Zheng; Yi-Chen Wu; Song-Rong Lin; Wei-Chang Li; Bhisham Sharma; Chin-Han Yang; Yu-Kai Lin (Engineering Structures, 2026)

Regulating cation disorder to stabilize oxygen redox in Li-rich DRX cathodes via Fe substitution - Chia-Ching Lin; Péter Udvarhelyi; Hao-Hsiang Chang; Tsung-Yi Chen; Zhenfei Cai; Yu Zhao; Han-Yi Chen; Denis Y.W. Yu (Chemical Engineering Journal, 2026)

Pyridoxine and valproic acid co-exposure induces ER-mediated calcium dysregulation and cardiac toxicity in zebrafish - Wei-Hsiang Chen; Po-Yuan Chen; Wen-Yu Chung; Tein-Yu Chiu; Wei-Ling Lin; Chen-Yu Huang; Hui-Hua Chang; Chin-Wei Huang; Bing-Hung Chen; Lin Kang; Tzu-Fun Fu (Chemico-Biological Interactions, 2026)

Multiplexed EDL-FET biosensor with tannic acid stabilization for simultaneous p-Tau217 and Aβ42/Aβ40 detection in plasma and whole blood from stroke patients - Shang-Chi Chien; I-Yin Chang; Yong-Chuan Chen; Yi-Zhen Lai; Yu-Fang Chen; Pei-Lun Sun; Bor-Ran Li; Yu-Lin Wang; Jung-Chih Chen (Analytica Chimica Acta, 2026)

Single-cell multi-omics dissects transcript isoform and immune repertoire dynamics in human immunosenescence - Yuhui Zheng; Ze-Hui Ren; Yafei Yang; Wenteng Liu; Fupeng Li; Yajun Zuo; Tao Zeng; Xue Wang; Xiumei Lin; Xinyue Zhu; Baibing Guan; Wenwen Zhou; et al. (Science China Life Sciences, 2026)

Postbiotics mitigate translucent post-larvae disease (TPD) in Penaeus vannamei by reinforcing hepatopancreatic cytoskeletal integrity against VHVP-2 toxin - Wenqiang Li; Shuang Liu; Jin Yan; Ping Li; Tingting Xu; Jin-Seng Lin; Hsiao-Tung Chang; Ting-Yu Lee; Qingli Zhang (Aquaculture, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Biodegradation of cyano liquid crystal monomers by an aerobic enrichment culture: Key degraders and interspecies synergistic mechanisms - Minghan Zhu; Chang He; Shaoyu Tang; Jiayu Zhang; Zhen Yu; Hui Lin; Yibo Yuan; Jonathan W.C. Wong; Hua Yin; Junfeng Niu; Xujun Liang; Zhi Dang (Water Research, 2026)

Directional disparity between oysters and mud snails in modulating marine carbon sequestration - Zhou Zhang; Xuan Dong; Yu-Jia Lei; Zhi-Yong Guo; Shuang-Jie Tian; Chang-Lin Li; Miao-Jun Pan; Xiang-Li Tian; Yun-Wei Dong; Jing-Yu Li; Shuang-Lin Dong (Journal of Environmental Management, 2026)

Toxin partitioning and sxtA4 expression in Alexandrium catenella under excess nitrogen supply - Ziru Lian; Chang Xu; Lin Guo; Jingxuan Li; Hao Huang; Ren-Cheng Yu (Harmful Algae, 2026)

Targeting the phenolic A-ring unifies the toxicology and remediation of environmental estrogens in aquatic environments - Liu-Feng Yu; Yi-Lin Ye; Jie Zhou; Yu-Han Jin; Yu-Han Sun; Li-Xia Yan; Chen-Man Li; Jia-Yi Chang; Wei-Jie Chen; Feng Liu; Yong-Wei Feng; Xiao-Dong Huang; et al. (Environmental Research, 2026)

Targeting the NOX4/NLRP inflammasome axis confers protection by isoliquiritigenin against H2O2-induced synovial inflammation - Yu-Chun Chang; Wei-Wen Kuo; Yen-Pin Chen; Shih-Wen Kao; Dennis Jine-Yuan Hsieh; Tsung-Jung Ho; Chia-Hua Kuo; Chien-Yao Fu; Chih-Yang Huang; Shinn-Zong Lin (Chemico-Biological Interactions, 2026)

Exposure-informed ventilation control for nanoparticle pollutants in an enclosed industrial built environment: A laser metal deposition case study - Ying-Fang Wang; Thi-Cuc Le; Jing Wang; Yu-Tung Dai; Phuong-Uyen Tran; Van-Nghia Tran; Guo-Ping Chang-Chien; Lin-Chi Wang (Building and Environment, 2026)

Decoupling of mass-based and oxidative-potential-based source contributions to PM2.5 in Nanjing: Random forest combined with PMF analysis - Yan-Yu Chen; Fang Cao; Chang-Liu Wu; Xiao-Ying Yang; Yu-Ting Mei; Yuan Dai; Meng-Ying Bao; Wen-Huai Song; Yan-Lin Zhang (Atmospheric Environment, 2026)

The 15th international workshop on modeling the ocean (IWMO-2025) in Stanford, California, USA, June 30th – July 1st, 2025 - Oliver Fringer; Ricardo de Camargo; Yu-Lin Chang; Huijie Xue; Tal Ezer (Ocean Dynamics, 2026)

Weather source heterogeneity affects disease forecasting: A case study of rice bacterial leaf blight in Taiwan - Jie-Hao Ou; Guo-Cih Lin; Yea-Fang Wu; Chi-Yu Chen; Guan-Ying Huang; Hau-Ping Chou; Chien-Chih Kuo; Hsin-Yuh Wu; Qiao-Juan Lai; Chih-Wei Wang; Yi-Chen Tsai; Chang-Hsin Kuo; et al. (Agricultural and Forest Meteorology, 2026)

Different drivers of active and inert carbon fraction on forest soil aggregate stability: a functional partitioning approach - Jing Lin; Rui Wang; Miao Xia; Jian-cong Zhang; Peng Qiu; Ke-xin Zhang; Bo Chang; Yu-lin Zhang; Tian-zi Xie; Yi Jian; Jia-yuan Wang; Shan-shan Guo (Journal of Soils and Sediments, 2026)

Correction: Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

One novel sesquiterpenoid from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Zi-Lin Wang; Shuai-Ming Zhu; Yu Yang; Rui Xu; Xue Zhao; Chen Sun; Qian Luo; You-Zhi Zhang; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2026)

Baicalin alleviates repeated superovulation induced ovarian dysfunction and oocyte impairment by suppressing excessive glycolysis - Lin-Feng Li; Hao Shen; Zhi-Min Qi; Tian Luo; Sheng-Ming Liu; Li-Li Ou; Chang-Long Xu; Yu Liu (Theriogenology, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Comprehensive analysis of microbial community assembly and metabolic dynamics reveals the effects of environmental acidity on flavor formation pathways during the Zhejiang rosy vinegar fermentation process - Cheng-Hao Jin; Yong-Zhu Zhang; Wen-Tian Song; Peng Wang; Chang-Ling Wu; Lin-Mei Liang; Wei Feng; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Food Research International, 2026)

Inhibitory effects of fruit powders on heterocyclic amine formation in charcoal-grilled pork: A comparative study of application methods and development of a functional barbecue sauce spray - Mei-Ling Li; Yu-Shun Lin; Pei-Yu Wu; Ling-Hsuan Chang; Shang-Ming Huang; Kuo-Chiang Hsu (Food Research International, 2026)

Non-overtly damaging cold atmospheric plasma induces adaptive epidermal molecular responses associated with integrin alpha 6 - Yu-Ping Cheng; Hua-Lin Chen; Yu-Hsuan Chen; Chang-Sheng Chen; Kuan-Wei Lee; Jong-Shinn Wu; Yun-Chien Cheng; Shih-Chang Lin; Jiun-Wen Guo (Chemico-Biological Interactions, 2026)

Caffeinated chewing gum improves military performances in special forces soldiers - Yi-Jie Shiu; Che-Hsiu Chen; Hung-Yu Lin; Chia-Cheng Yang; Chi-Wen Yen; Han-Yuan Chang; Hsuan-Ta Chen; Chih-Hui Chiu (European Journal of Applied Physiology, 2026)

Insular divergence and host-associated diversification in ovoid-gall Daphnephila (Diptera: Cecidomyiidae) from Taiwan, with description of a new species - Sheng-Feng Lin; Tung-Chuan Chiang; Hsuan Chang; Yu-Chu Weng; Man-Miao Yang (Applied Entomology and Zoology, 2026)
The Old World cecidomyiid genus Daphnephila is primarily associated with Machilus (Lauraceae) plants and exhibits exceptionally high gall diversity in Taiwan. At present, six described species correspond to only seven of 40 known Daphnephila gall morphospecies on the island. In this study, we clarified the species identities of Taiwanese Daphnephila inducing long ovoid-galls and ovoid-galls on the leaves of five Machilus plants, and explored their diversification using molecular evidence. Accordingly, two species, D. yukawai sp. n. and D. taiwanensis , were recognized based on morphological characteristics and species delimitation method (Assemble Species by Automatic Partitioning). The former species utilizes only the endemic M . mushaensis , primarily inducing ovoid-galls along the major leaf vein, whereas the latter species associates with five Machilus species and induces two gall types on various leaf parts. Notably, when sympatric with D. yukawai sp. n., D. taiwanensis exhibits character displacement of galling habit, forming long ovoid-galls along the minor leaf veins. Furthermore, the COI-based IQ tree supported: (1) a single origin of East Asian ovoid-gall Daphnephila species, (2) the sister-group relationship between the Taiwanese lineage and a Chinese species, and (3) the role of M. mushaensis as the probable ancestral host of the Taiwanese lineage, including D. taiwanensis. These results suggest that D. taiwanensis colonized additional Machilus hosts after diverging from D. yukawai sp. n. Taken together, our findings indicate that novel plant associations and shifts in galling sites may have facilitated diversification in Daphnephila cecidomyiids, contributing to the remarkable richness of Daphnephila galls in Taiwan.

Enzymatic synthesis of a new and bioactive dihydrochalcone: 3,4-dihydroxy-2′,6′-dimethoxy dihydrochalcone - Te-Sheng Chang; Jiumn-Yih Wu; Hsiou-Yu Ding; Tzi-Yuan Wang; Guan-Cheng Liu; Min-Lin Wang; Huei-Ju Ting (Natural Product Research, 2026)

Optimized Midbrain Organoid Transplantation Restores Dopaminergic Nigrostriatal Pathway and Motor Function in Parkinson’s Disease Mouse Model - Lin-Bo Chen; Xin-Yu She; Xi Jiang; Peng-Jian Wu; Chang-Qing Zheng; Jun Yao (Neuroscience Bulletin, 2026)

Synthesis and production of hydroxytyrosol derivatives with potent anti-inflammatory activities - Te-Sheng Chang; Wen-Yueh Ho; Jiumn-Yih Wu; Chien-Yu Wu; Pei-Rong Cai; Bo Eng Cheong; Wilson Thau Lym Yong; Peik Lin Teoh (Natural Product Research, 2026)

Automated computer vision monitoring of black soldier fly larval growth using metaheuristic optimization for waste-to-feed bioconversion - Jui-Sheng Chou; Benjawan Phakdee; Zih-Tong Lin; Chang-Ping Yu; Pei-Hsun Wu; Cheng-jen Shih (Computers and Electronics in Agriculture, 2026)

Management regimes underpin soil carbon accrual following forest conversion to tea plantations across China - Lin Chen; Li Ruan; Yu Duan; Biao Feng; Yixuan Bai; Scott X. Chang; Teng Yang; Yowhan Son; Yuwei Yuan; Shangwen Fu; Chuan Yue; Zhongyi Li; et al. (Science Bulletin, 2026)

A versatile colorimetric array sensor based on FeCu-based prussian blue analogue heterostructures for efficient discrimination of tetracycline antibiotics and rapid identification of urinary tract infection pathogens - Dan Wu; Xin-Yu Cheng; Chao-Man Wang; Ya-Nan Kong; Shu-Chang Zhao; Rui-Lin Liu (Journal of Hazardous Materials, 2026)

Research on the interface adsorption and emulsion properties of microwave cold plasma oxidized modified rice bran protein-phloridzin binary complex - Chang Liu; Ruichi Guo; Lin Li; Liqi Wang; Na Zhang; Weining Wang; Dianyu Yu (Food Research International, 2026)

Pollutant-specific pathways linking gaseous air pollution to adolescent depressive symptoms: Direct and sleep-mediated effects in a population-based retrospective cohort study - Chun-Ji Lin; Po-Ya Chang; Yu-Ling Li; Chih-Da Wu; Chao-Ying Tu; Chih-Yi Wu; Szu-Ying Chen; Hung-Yi Chiou (Environmental Research, 2026)

The 14th International Workshop on Modeling the Ocean (IWMO-2024) in Sapporo, Japan, 17–20 June 2024 - Yutaka Yoshikawa; Joanna Staneva; Joseph Zhang; Yu-Lin Chang; Amin Chabchoub; Tal Ezer (Ocean Dynamics, 2026)

Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Piezo-photocatalysis with BaTiO3 nanorod arrays–Ag nanoparticle composites for the photodegradation of rhodamine B - Yen-Lun Chiu; Thi Nghi Nhan Nguyen; Hsin-Yu Chi; Heng-Jun Lin; Kao-Shuo Chang (Journal of Environmental Chemical Engineering, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Dynamic electronic and spin-state modulations of ternary single-atom catalysts for ultrahigh power density and ultra-stable rechargeable zinc-air batteries - Yu-Chieh Ting; Shao-I Chang; Kai-An Lee; Chiung-Wen Chang; Tzu-Hsiang Lin; Chih-Heng Lee; Hsin-Yi Tiffany Chen; Shih-Yuan Lu (Chemical Engineering Journal, 2026)

Life cycle environmental impact of customer premises equipment: insights from a Wi-Fi router case study - Hsin-Tien Lin; Kuo-Che Weng; En-Yu Yeh; Chun-Wei Wang; Han-Chang Pan (The International Journal of Life Cycle Assessment, 2026)

Doxorubicin-Induced Cardiotoxicity in Breast Cancer: Mechanistic Pathways, Pharmacogenomic Modifiers, and Translational Strategies - Chi-Tong Kuok; Hao-Wei Lee; Chen-Yu Huang; Yu-Che Cheng; Shih-Chang Lin; Jiun-Wen Guo (Cardiovascular Toxicology, 2026)

Damage mechanism and optimization design of wall-type portal tunnels underseismic action: Seismic damage investigation and a theoretical model - Ming-Yu Chang; Deng Gao; Chao Wang; Hua Huang; Yi-lin Yu; Yusheng Shen (Soil Dynamics and Earthquake Engineering, 2026)

Mechanisms and control strategies of shrimp melanosis during storage: A review - Duanquan Lin; Qian Hong; Kai-Yuan Cao; Shu-Jun Hong; Yu-Lei Chen; Le-Chang Sun; Min-Jie Cao (Food Bioscience, 2026)

Study on the oil-water interfacial adsorption behavior and emulsion properties of rice bran protein modified by microwave plasma oxidation - Chang Liu; Lin Li; Ning Wang; Liqi Wang; Weining Wang; Na Zhang; Dianyu Yu (Food Hydrocolloids, 2026)

In vitro and in vivo antiviral effects of myrcene on MSRV infection in largemouth bass (Micropterus salmoides) - Zhengzhao Liu; Lin Huang; Jieying Yu; Qing Yu; Mingzhu Liu; Yanxia Gao; Xiangmou Qin; Junxiang Lai; Fei Ling; Yanlei Chang; Shuyu Han; Jia Cai; et al. (Fish & Shellfish Immunology, 2026)

Vegetation in Central Asia is more sensitive to soil moisture stress than to precipitation and vapor pressure deficit stresses - Hongwu Liang; Guli Jiapaer; Cun Chang; Tao Yu; Liancheng Zhang; Pingping Feng; Kaixiong Lin; Tongwei Ju; Xiapeng Jiang; Philippe De Maeyer; Tim Van de Voorde (Agricultural and Forest Meteorology, 2026)

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

Targeting aryl hydrocarbon receptor signaling attenuates hypertension programmed by maternal Di-2-ethylhexylphthalate exposure - Chien-Ning Hsu; Hsi-Yun Liu; Chih-Yao Hou; Yu-Wei Chen; Guo-Ping Chang-Chien; Shu-Fen Lin; You-Lin Tain (Toxicology and Applied Pharmacology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Electroanalytical profiling of Escherichia coli using MOFs-modified gold electrode sensing chips and endogenous β-galactosidase - Ching-Yu Lin; Bhuvan Lokesh Marenahalli; Su-Wei Hu; Po-Han Chiu; Yu-Hsuan Chang; Kevin C.-W. Wu; Yu-Sheng Yu; Ningappa Kumara Swamy; Chia-Hung Liu; Yu-Jui Fan (Journal of Water Process Engineering, 2026)

Thiourea-based networks with nanocarbon fillers for antistatic, self-healing, and plasma-resistant elastomers - Tse-Yu Lo; Shu-Fan Li; Chia-Wei Chang; Huan-Wei Lin; Heng-Hsuan Su; Kuan-Hung Liu; Po-Chia Huang; Jiun-Tai Chen (Chemical Engineering Journal, 2026)

Chlorine-resistant high-entropy spinel oxide catalyst for efficient and durable seawater anion exchange membrane water electrolysis - Thi Xuyen Nguyen; Ting-You Shih; Ngoc Thanh Thuy Tran; Thanh Tuan Nguyen; Yi-Chuan Chu; Bo-Han Lai; Chun-Kuo Peng; Yu-Ru Lin; Yan-Gu Lin; Kao-Shu Chuang; Jeng-Kuei Chang; Thi Y Phung Nguyen; et al. (Chemical Engineering Journal, 2026)

PEALD-derived ultrathin Al2O3 and MgO interphases on freestanding nitrogen-doped carbon nanofibers for robust potassium-ion battery anodes - Chih-Chieh Wang; Yi-Han Lin; Chia-Yu Chang (Chemical Engineering Journal, 2026)

Sustained performance and microbial succession in novel artificial rumen system coupling dynamic membrane with methanogenic granules for acid absorption - Xiang-Lin Chang; Bao-Shan Xing; Yu Qin; Juan Xie; Zhi-Bo Li; Xiaochang C. Wang; Rong Chen; Yu-You Li (Bioresource Technology, 2026)

Genetic Diversity of Spodoptera litura in China Based on Mitochondrial DNA Analysis - Yu-Lin Li; Jian-Kun Long; Zhi-Ming Chang; Han-Cheng Wang; Jian-Yu Meng; Lin Yang; Jun-Yi Gao; Xiang-Sheng Chen (Phytoparasitica, 2026)

The GATA3-RFPL3-ASK1 axis suppresses breast cancer growth and lung metastasis - Kang Li; Chang Liu; Jun-Hui Yin; Yu-Ting He; Zhi-Zhi Xu; Wen-Jing Zhang; Jian-Qi Wang; Lu-Yao Hou; Jing Feng; Le-Min Lin; Xiu-Qing Duan; Yi Zhou; et al. (Apoptosis, 2026)

Influence of Sea Surface Temperature on Precipitation Anomalies in Northeast China During the Late Summer, 2024: A Statistical Assessment Based on Generalised Equilibrium Feedback Analysis - Yitong Lin; Yihe Fang; Chunyu Zhao; Yu Zhang; Chang Liu; Xinze Li (International Journal of Climatology, 2026)
During the late summer (July–August) of 2024, the Northeast China (NEC) suffered extreme precipitation and severe floods, with rainfall in southern NEC marking the highest recorded since 1985. Using the daily precipitation records from 245 national meteorological stations across the NEC, this study analyses the characteristics of the rainfall anomalies and the associated large‐scale circulation patterns in the late summer of 2024. Based on the generalised equilibrium feedback analysis (GEFA) method, we investigate the response of precipitation and atmospheric circulation anomalies to sea surface temperature (SST) anomalies across various oceanic basins. The results indicate that the NEC precipitation anomalies in the late summer of 2024 exhibit a remarkable response to both the first empirical orthogonal function (EOF) mode of the North Pacific SST (NP1) and the second EOF mode of the tropical Atlantic SST (TA2). The NP1 features widespread positive SST anomalies extending from the Kuroshio Extension to the west coast of North America, and the TA2 is marked by positive anomalies in the northern tropical Atlantic and negative anomalies in the southeastern region. Both modes induce enhanced precipitation over NEC, with anomaly centres located southward, closely matching the observations. Specifically, the positive SST anomalies of the NP1 mode enhance the upward heat flux over the Japan Sea and its eastern regions, inducing positive geopotential height anomalies over Japan, thereby leading to an enhanced and northward anticyclone in the Northwest Pacific. Moreover, for the TA2 mode, the positive SST anomalies in the northern tropical Atlantic are closely associated with the downstream propagating Rossby wave train, resulting in an anomalous circulation pattern characterised by active Northeast China cold vortexes over the NEC and an intensified western Pacific subtropical high. These circulation anomalies facilitate the northward transport of warm and humid airflows to the NEC and promote the frequent convergence of cold and warm airflows over the NEC region, thereby contributing to the anomalously more precipitation over the NEC in the late summer of 2024. By quantifying the relative contributions of different SST modes, this study helps better target key precursors of NEC summer rainfall anomalies, which provides useful guidance for seasonal climate forecasting in NEC.

Application of ENU-mediated efficient mutagenesis in breeding of the big belly seahorse (Hippocampus abdominalis) - Xiao-lei Su; Chun-yu Hou; Lin Shi; Shi-chang Zhang; Cheng-de Fan; Jie-zhou Wang; Yi-cong Ma; Wu-hong Lv; Cong Liu; Guo-dong Zheng; Kai Wang (Aquaculture, 2026)

In-situ reactivation of the catalyst for hydrodeoxygenation of bio-oil to biofuel by coupling the self-rotation and revolution of catalysts in the swirling flow - Yao Zhang; Zheng-hao Yang; Yu-long Chang; Jian-ping Li; Bang-da Wang; Zi-heng Jin; Liang Ma; Xia Jiang; Hua-lin Wang (Journal of Cleaner Production, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

A novel approach for utilizing UAV imaging and deep learning techniques for river channel measurement and flood simulation - Jen-Yu Han; Chun-Jia Huang; Yuan-Shun Chang; Yen-Cheng Lin; Hao-Che Ho (Geomorphology, 2026)

Dynamic remodeling of intramuscular structural proteins and its impact on abalone muscle quality during post-mortem cold storage - Hua Liu; Tian-Bo Zhang; Fu-Hao Zhang; Le-Chang Sun; Duanquan Lin; Tengchuan Jin; Ling-Jing Zhang; Jia-Yin Huang; Min-Jie Cao; Yu-Lei Chen (Food Chemistry, 2026)

Mechanistic insights into cold plasma treatment of rice bran protein for enhanced vegetable oil-based whipped cream properties - Lin Li; Chang Liu; Ning Wang; Dianyu Yu; Liqi Wang; Na Zhang (Food Hydrocolloids, 2026)

Improvement of indoor air quality and health effects in COPD patients in a heavy industrial area - Jia Lin Zhang; Yi Ting Chang; Ching Yu Hsiao; Chung-Shin Yuan; Yen-Ping Peng; Da Wei Wu; Huang-Chi Chen; Jia-Yu Kuo; Huai-Lei Juan; Pei-Shih Chen (Environmental Research, 2026)

Noise-resistant automatic seismic framework for monitoring rockslide slope - Chung-Ray Chu; Chiao-Yin Lu; Guan-Wei Lin; En-Jui Lee; Che-Hsin Liu; Chih-Hsin Chang; Hsiao-Yu Huang (Engineering Geology, 2026)

Triarylamine-based epoxy thermosets featuring bright polyelectrochromic energy-storage and energy-saving behaviors - Yu-Jen Shao; Peng-Yi Lin; Hung-Lin Ho; Hsuan-Hsi Pai; William Sun; Yu-Jie Wang; Cha-Wen Chang; Guey-Sheng Liou (Chemical Engineering Journal, 2026)

Decoupling detoxification from resource recovery: Mechanisms of organic electromigration control in bipolar membrane electrodialysis - Hao-Ran Yang; Zhi-Hua Yuan; Chang-Jiang Li; Yan-Fang Guan; Jiuyang Lin; Mohammad Younas; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng (Chemical Engineering Journal, 2026)

Rapid microfluidic sample preparation for mass spectrometric analysis of wild-type and mutant BRAF protein - Yen-Heng Lin; Heng-Yun Chang; Chia-Chun Wu; Yung-Chin Hsiao; Ying-Hao Wen; Jau-Song Yu (Analytica Chimica Acta, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Synergistic pathogenic mechanisms of EHP and IHHNV co-infection in Litopenaeus vannamei: Insights from RNA-seq analysis - Lin-Rui Chang; Cai-Yi Chen; Fan Yang; Chuan-Yu He; Fan Li; Ting Li; Ling-Jun Si; Dong-Chun Yan (Journal of Invertebrate Pathology, 2026)

Enhanced fluoxetine removal from water via Fe/Cu-doped biochar-activated percarbonate under sunlight and aeration - Yang Wu; Zhi-hao Li; Xi-xi Lu; Zi-xuan Lin; Chang-ping Yu (Journal of Environmental Chemical Engineering, 2026)

Aldehyde dehydrogenase 2 mitigates acrolein-driven ferroptosis to preserve kidney function - Yu-Ming Kuo; Shiu-Dong Chung; Jui-Ting Chang; Hui-Min Yang; Chieh-Chen Lee; Chih-Ching Lin; Hsiang-Tsui Wang (Environmental Pollution, 2026)

Advancing water and resource recovery from brackish water through electrodialysis-based technologies for circular product ecosystems - Shu-Yuan Pan; Jeremiah Mulia Gianto; Yu-I Lin; Hau-Ming Chang (Desalination, 2026)

Evolution of tactoid structures and pore water distribution during wetting in saturated clay aggregates driven by montmorillonite-water interaction - Kai-wen Tong; Chang-fu Wei; Yong-gui Chen; Zi-yu Ding; Hao Wang; Ya-kun Tian; Rong Gui; Ling-ling Wu; Zhi-jun Zhang; Lin Hu (Computers and Geotechnics, 2026)

Assessment of dynamic drought risk and transition characteristics by combining an indicator-based approach and Markov chain model - Bin Huang; Tao Peng; Tianyi Fan; Vijay P. Singh; Xiaohua Dong; Qingxia Lin; Wenjuan Chang; Ji Liu; Yan Huang; Jiali Guo; Yinghai Li; Dan Yu (Natural Hazards, 2026)

Aqueous LC-MS/MS quantification of α-/β-nicotinamide mononucleotide in dietary supplements using a pentabromophenyl column - Chng Sze Hoei; Nian-Hua Wu; Chao-Ming Tsen; Ping-Wei Sun; Han-Wei Chang; Shin-Yuan Wang; Hung-Yu Lin (Analytica Chimica Acta, 2026)

Correction: Dapagliflozin protects against doxorubicin-induced cardiotoxicity by restoring STAT3 - Wei-Ting Chang; Jhih-Yuan Shih; Yu-Wen Lin; Zhih-Cherng Chen; Wei-Chih Kan; Tsung-Hsien Lin; Chon-Seng Hong (Archives of Toxicology, 2026)

Spatio-temporal dynamics of fish assemblages at an offshore wind farm and a comparison with mature artificial reefs - Kwang Tsao Shao; Ching Han Chang; Ching Yi Chen; Lin Tai Ho; Yi Ta Shao; Hsin-Chieh Chiang; Wei-Ning Lee; Hsien Ju Tsai; Tien-Yu Huang; Chun-Yu Chang (Frontiers in Marine Science, 2026)
Introduction Offshore wind farms (OWFs) are vital for sustainable energy. The underwater foundations of those wind turbines provide a complex structure that creates new habitats and attracts fishes. However, whether OWFs had the same ecological function as purpose-built artificial reef (AR) and how they alter the original fish community remain unclear. Methods To evaluate the spatial and temporal variations in fish assemblages, we conducted a multi-part investigation at the Formosa Wind Farm, located off the coast of Miaoli County, Taiwan. Temporal changes were assessed through SCUBA surveys at turbine foundations in 2017, 2018, and 2025, with the 2025 data allowing for a direct comparison with the nearby existing artificial reefs. To assess spatial effects, pole-and-line surveys were conducted from Apr to Oct in 2024 and 2025 at varying distances from the turbines. Results Our investigation documented 86 species of reef-associated fishes exclusively within 50 m of turbine foundations; none were caught in the surrounding sandy areas or documented in pervious fishery records. The results demonstrated that fish assemblages around the turbine piles changed successively over the years. Although the species composition in 2025 differed between the OWF and the established AR sites, key ecological metrics such as species richness, diversity, and trophic structures showed no significant differences. Discussion These findings demonstrated that the underwater structure of offshore wind turbines can function as AR, creating novel reef habitats and supporting reef-associated fish community within a finite spatial extent. Overall, OWFs may provide ecological benefits in addition to renewable energy, highlighting their potential role in balancing energy development with marine conservation.

Evaluation of MarR-deleted Streptococcus agalactiae as a live-attenuated vaccine candidate for Nile Tilapia (Oreochromis niloticus) - Tian-Yu Ma; Feng-yang Li; Chang-Song Wu; Jian-Hao Lin; Ming Chen; Yong-An Zhang; Hui Zeng (Aquaculture, 2026)

Modified QuEChERS coupled with hybrid mass spectrometry for 322 target pesticides and suspect screening of emerging organic contaminants in agricultural soils - Yu-Hui Chang; Chi-Chieh Hu; Chinn-Yuan Fu; Sichao Wang; Yu-Min Tzou; Shiou-Ruei Lin; Hsiao-Ying Yang; Jerry J. Wu; Cheng-Hua Liu; Ya-Hui Chuang (Journal of Hazardous Materials, 2026)

Experimental study of flame height and merging condition of jet fire arrays - Yujie Lin; Yuhang Chen; Guanlin Peng; Chen Kuang; Jiang Lv; Chang Qi; Anfeng Yu; Yi Liu (Fuel, 2026)

Association between urinary metabolites of 1,3-butadiene and toluene exposure with kidney function indices in Taiwanese school-aged children living near a petrochemical complex - Po-Keng Cheng; Vinoth Kumar Ponnusamy; Wei-Hong Lin; Jeganathan Chinnadurai; Pei-Chien Tsai; Cai-Yu Chen; Wan-Ting Chang; Po-Chin Huang (Environmental Pollution, 2026)

Terminal-carboxyl-engineered 3D PLA nanochannels via ionic liquid templating for high osmotic energy conversion - Leqi Chang; Cuncai Lin; Xingteng Ma; Yuankun Ning; Zeyang Yu; Shuhong Hu; Yanshu Chen; Xin Sui; Longcheng Gao; Kunyan Sui (Chemical Engineering Journal, 2026)

Electrochemically activated polypyrrole for full-polymer electrochemical deionization: Unraveling potential-gated ion exchange behavior and its application to oxyanion removal - Hung-Yi Huang; Yi-Heng Tu; Yi-An Chen; Cheng-Wei Lin; Yu-Hung Cheng; Hsing-Mei Chou; Yu-Hsiang Yang; Yun Ku; Zhiyin Yang; Sophia Uemura; Hsin-Lung Chen; Richard B. Kaner; et al. (Chemical Engineering Journal, 2026)

Evaluating hygroscopic cloud-seeding effects by in-situ observation and real-case simulation - Kai-I Lin; Sheng-Hsiang Wang; Kao-Shen Chung; Pay-Liam Lin; Yu-Chieng Liou; Yi-Hui Chang; Yu-Chih Huang; Lin Yi-Sheng (Atmospheric Research, 2026)

A proposed framework based on traffic volume and the design of a bottom-up methodology to estimate the CO emission of on-road vehicles - Shan-Yi Shen; Ru-Yun Chang; Yun-Wei Liao; Wei-Chun Chou; Yu-Hao Lin; Ping-Yu Liu (Atmospheric Pollution Research, 2026)

AMPK Activation by ENERGI Ameliorates Behavioral and Synaptic Deficits in a Mouse Model of Autism - Ming-Chia Chu; Chi-Chun Wu; Yueh-Jung Chung; Chieh-Yu Chang; Han-Fang Wu; Sze-Chi Tsai; Tzu-Ning Peng; Tzu-Jung Yang; Hui-Ching Lin (Molecular Neurobiology, 2026)
Autism spectrum disorder (ASD), a neurodevelopmental disorder, is characterized by synaptic dysregulation as its underlying pathophysiological mechanism. AMP-activated protein kinase (AMPK), an intracellular energy sensor, plays a pivotal role in regulating synaptic integrity and function. Current treatments for ASD exhibit limited benefits in alleviating the core symptoms of ASD. Consequently, we investigated the therapeutic potential of ENERGI, a novel AMPK-activating compound, in a valproate (VPA)-induced mouse model of ASD. ENERGI was administered via drinking water to VPA-induced ASD offspring. After 7 days of treatment, ENERGI gradually alleviated social defects, repetitive behaviors, and emotional comorbidities in VPA-induced ASD offspring. At the synaptic level, ENERGI treatment restored aberrant plasticity, spine structure, and dendritic arborization in the hippocampus of VPA-induced ASD offspring. Notably, the curative effects of ENERGI in VPA-induced ASD offspring were equivalent to those of D-cycloserine (DCS), a known therapeutic candidate for ASD. Moreover, ENERGI demonstrated superior efficacy in restoring spine abnormalities than DCS. Mechanistically, 7-day ENERGI treatment reversed the reduction in AMPK phosphorylation, and normalized the elevated PSD95 and synaptic GluA2 levels in VPA-induced ASD offspring, whereas DCS treatment only rescued the synaptic GluA2 levels. Overall, these findings suggest that AMPK activation by ENERGI effectively reverses behavioral and synaptic deficits in a preclinical ASD model, supporting AMPK as a promising target for developing novel ASD therapies.

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

Correction: Isolation and functional identification of Jasmonate resistant 1, a jasmonic acid isoleucine-conjugating enzyme in catharanthus roseus - Aikun Pan; Haiqiao Gao; Ying Lin; Bingrun Yang; Chunhao Chang; Zhiwen Liu; Yanyan Wang; Zhaoxia Jin; Fang Yu (Journal of Plant Research, 2026)

Harnessing pyroptosis to restrain melanoma through aripiprazole - Yu-Teng Chang; I-Hsiang Lin; Jeng-Jer Shieh; Tsuo-Hung Lan; Jia-Ning Syu; Shiau-Shian Huang; Po-Hsun Hou (Apoptosis, 2026)

Identification and quantification of per- and polyfluoroalkyl substances in wastewater from Taiwan using targeted and non-targeted approaches - Jen-Yi Hsu; Chih-Wei Chang; Yu-Wen Lin; Yuan-Chih Chen; Pao-Chi Liao (Chemosphere, 2025)

Spawning stock recovery of Pacific bluefin tuna (Thunnus orientalis): Evidence from length, age and catch data of Taiwanese longline fishery in 2010–2023 - Yu-Wen Lin; Yi-Jay Chang; Jhen Hsu; Owyn E. Snodgrass; Travis Richards; Jen-Chieh Shiao (Fisheries Research, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Intra-oceanic arc subduction within the Meso-Tethys Ocean constrained by arc crust remnants in the Lagkorco ophiolite, Central Tibet - Wei-Qi Zhang; Chuan-Zhou Liu; Tong Liu; Xiao-Ni Li; Chang Zhang; Zhen-Yu Zhang; Zhen Zhang; Yin-Zheng Lin (Lithos, 2025)

Temperature-dependent expression profiling of 16 HSP genes across developmental stages in Frankliniella occidentalis - Lin Shu; Yi-Jie Ma; Yu-Cheng Wang; Ya-Wen Chang; Yu-Zhou Du (Journal of Thermal Biology, 2025)

Trigger efficient peroxydisulfate-assisted photocatalysis by S-scheme Co3O4/BiOCl heterojunctions: Vital roles of Co2+/Co3+ redox centers and oxygen vacancies - Chang-Bin Yu; Chong Xu; Lin He; Wei-Ya Huang; Kai Yang; Dan Li (Journal of Environmental Chemical Engineering, 2025)

Immobilization of partial glyceride lipase and its application in the high phytosterol and γ-oryzanol rice bran oil - Chang Liu; Ning Wang; Lin Li; Liqi Wang; Fuming Yang; Dianyu Yu (Innovative Food Science & Emerging Technologies, 2025)

Transforming gastrointestinal health with probiotic fermented milk: a systematic review and meta-analysis - Ngan Thi Kim Nguyen; Yu-Hsin Chang; Lee-Yuan Lin; Philippe Noirez; Roma Panwar; Tzu-Wen L. Cross; Nguyen-Phong Vo; Shyh-Hsiang Lin (International Dairy Journal, 2025)

A refined calibration of the Na-Li geothermometer for pelitic lithologies before and after orogenic metamorphism - Hou-Chun Liu; Chao-Chang Chen; Yi-Chia Lu; Huai-Jen Yang; Yan-Hong Chen; Yu-Feng Lu; In-Tian Lin; Sung-Ping Chang (Geothermics, 2025)

Sustainable energy generation through engineered copper molybdate: a ternary metal oxide catalyst for efficient oxygen evolution in alkaline environments - Hung-Chang Cheng; Dhanapal Vasu; Hsin-Yu Lin; Zhen-Yuan Lan; Leggins Abraham; Tetsu Yonezawa; Te-Wei Chiu (Fuel, 2025)

Advances in the research on phenolic acids and flavonoids in vinegar: Sources, formation and degradation mechanisms, and functional properties - Cheng-Hao Jin; Yong-Zhu Zhang; Feng-Hua Wu; Chang-Ling Wu; Peng Wang; Wei Feng; Lin-Mei Liang; Wei-Jiang Xu; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Food Research International, 2025)

Effect of carboxymethyl chitosan on the properties of soybean oil body-carboxymethyl chitosan emulsion - Lin Li; Ning Wang; Chang Liu; Liqi Wang; Na Zhang; Yingjie Yu; Dianyu Yu (Food Research International, 2025)

Astaxanthin enhances broiler health via integrated regulation of antioxidant capacity, immune function, and gut microbiota - Xiao-Ming Gu; Ding-Cheng Ye; Jun-Wei Cheng; Zhi-Xin Lin; Hai-Xuan Lv; Zai-Xing Cai; Yun Yang; Chang-Kang Wang; Yu-Yun Gao; Ling Jin (Food Chemistry, 2025)

Exploring the potential antimicrobial ability of Lactiplantibacillus plantarum against common fish pathogens - Ting-Chang Lin; Yu-Chi Wu (Fish & Shellfish Immunology, 2025)

In-situ control of biohythane production in electro-anaerobic digestion - Chao-Chin Chang; Yu-Wen Lin; Chang-Ping Yu; Zhen He (Chemical Engineering Journal, 2025)

Unveiling the role of Zn−N1S3 sites in atomic-precision ZnIn2S4/g-C3N4 heterostructure for highly efficient CO2-to-CO conversion - Hossam A.E. Omr; Raghunath Putikam; Mahmoud Kamal Hussien; Amr Sabbah; Tsai-Yu Lin; Kuei-Hsien Chen; Li-Chyong Chen; Heng-Liang Wu; Shien-Ping Feng; Ming-Chang Lin; Hyeonseok Lee (Chemical Engineering Journal, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

Pluvial flood warnings in a tidally influenced basin enhanced by rainfall–tide compound indicators: Taipei case study - Mei-Ying Lin; Wen-Yih Sun; Huei-Syuan Fu; Chih-Hsin Chang; Wei-Bo Chen; Chieh-Ju Wang; Hsuan-Wei Wang; Yi-Chiang Yu; Yen-Wei Li (Stochastic Environmental Research and Risk Assessment, 2025)

Trans-anethole enhances mesenchymal stem cell derived exosomes function to inhibit H2O2-induced rheumatoid arthritis-like inflammation in HIG-82 synovial cells - Tai-Lung Huang; Yu-Chun Chang; Wei-Wen Kuo; Shih-Wen Kao; Chia-Hua Kuo; Dennis Jine-Yuan Hsieh; Kuan-Ho Lin; Tsung-Jung Ho; Chih-Yang Huang (Molecular Biology Reports, 2025)

Early hyperferritinemia in polytrauma: a biomarker of systemic inflammation and mortality risk in a multicenter cohort study - Shunyao Chen; Teding Chang; Jialiu Luo; Cong Zhang; Peidong Zhang; Shuaipeng Gu; Zhiqiang Lin; Yujie Chen; Youxie Shen; Liming Dong; Qian Wan; Liang He; et al. (Inflammation Research, 2025)

Correction: Effects of 12-week free sprint training and speed, agility, and quickness training (SAQT) on reaction time and lower limb muscle activation during crouch start - Yu-Hua Chang; Mei-Hsuan Wu; Kuei-Fu Lin; Kok-Hwa Tan (European Journal of Applied Physiology, 2025)

Effects of 12-week free sprint training and speed, agility, and quickness training (SAQT) on reaction time and lower limb muscle activation during crouch start - Yu-Hua Chang; Mei-Hsuan Wu; Kuei-Fu Lin; Kok-Hwa Tan (European Journal of Applied Physiology, 2025)

Analytical and usability comparison of microsampling dried blood spot devices for glucocorticoid detection in sports using ultra-high-performance liquid chromatography–tandem mass spectrometry - Cheng-Chia Chen; Yu-En Lin; Mei-Chich Hsu; Yu-Chuan Lin; William Chih-Wei Chang (Analytica Chimica Acta, 2025)

Fast Forward Modeling of Resistivity Method under Complex Topography Using Finite Element Method - Zhan Wang; Chang-Wei Li; Yu-Zeng Lv; Run-Lin Luo; Bo Cheng; Bo Li (Applied Geophysics, 2025)

Revision of the Armoreye dory genus Zenion (Zeiformes: Zeniontidae) in the South China Sea, with a description of a new species - Yen‐Ting Lin; Chia‐Hao Chang; Yu‐San Han; Chien‐Hsiang Lin (Journal of Fish Biology, 2025)
This study describes a new species of armoreye dory, Zenion boops sp. nov., from Dongsha Island, Taiwan, as part of a comprehensive revision of the genus Zenion in the South China Sea. The new species is clearly distinguishable from its tropical congeners, Z. hololepis and Z. japonicum , based on a combination of distinct morphological features, meristic counts, otolith morphology and c oxidase subunit I ( COI ) gene sequences. Z. boops is characterized by a smooth second dorsal spine, a long first dorsal spine, 30–35% of second (longest) dorsal spine, a small and narrow notch at the symphysis of the maxilla, and a relatively large eye diameter, 55–61% of head length. Furthermore, otolith morphology and phylogenetic analyses based on partial sequences of the cytochrome COI gene reveal significant genetic divergence between this new species and its congeners. With the addition of Z. boops , the genus Zenion now includes four valid species. We also present an identification key for all Zenion species and provide detailed descriptions of their otoliths. Also, we provide data that show that Z . hololepis is restricted to the Atlantic Ocean.

Analysis of cellular and gene therapy product reviews in the United States - Cheng-Fang Weng; Jhe-Yuan Dong; Shiuan-Fei Lin; Ai-Lei Jiang; Yu-Li Cheng; Lin-Chau Chang (Regulatory Toxicology and Pharmacology, 2025)

Hypoglycemic cucurbitane-type triterpenoids from fruits of Citrullus colocynthis - Hua-Wei Lv; Yu Wan; Wen-Lin Fan; Meng-Di Zhu; Qiao-Liang Wang; Zhong-Bo Zhou; Chang-Chun Chen; Hong Wang; Xing-Nuo Li (Phytochemistry, 2025)

Effective peroxymonosulfate activation over cobalt oxide (CoO)/nitrogen-doped graphene aerogel for rhodamine b degradation - Xian-Lun Liao; Dhayanantha Prabu Jaihindh; Tzu-Ting Chang; Yi-Feng Lin; Wei-Hung Chiang; Yu-Chun Wang (Journal of Water Process Engineering, 2025)

Linking source-to-sink processes, organic matter composition, and oxygen consumption on a shallow passive margin shelf sustained by small mountainous rivers - Yu-Shih Lin; Chih-Lin Wei; Yuan-Pin Chang; Jih-Terng Wang; Shu-Ying Chuang; Liang-Chi Wang; James T. Liu; Hong-Chun Li; Chieh-Wei Hsu (Geochimica et Cosmochimica Acta, 2025)

Collagen peptides from Skipjack tuna (Katsuwonus pelamis) bones: Composition, characterization, and mechanism of high-fat diet-induced NAFLD amelioration - Yu-Lin Jiang; Shuang-Yi Zhang; Bin Wang; Yu-Hui Zeng; Li Xu; Chang-Feng Chi (Food Research International, 2025)

Layer-by-layer assembly mechanism of particulate-continuous phase for sandwich-like nanoparticles in oral colon-targeted protein delivery - Wen-Xuan Hu; Chang-Sen Jin; Si-Lin Li; Jia-Yang Fu; Liang-Sen Liao; Xiuzhu Yu; Shuang-kui Du (Food Chemistry, 2025)

Microfluidic device for high-throughput cancer drug screenings - Po-Hsun Chen; Lin-Yu Wang; Chia-Yuan Chang; Yuh-Shiuan Chien; Yu-Chia Su; Chi-Kuang Wang; Kuang-Chong Wu; Hsian-Jean Chin; Chien-Fu Chen (Chemical Engineering Journal, 2025)

Dipyridinium salt-enhanced type II ROS photodynamic antibacterial nanofiber films for long-term preservation of blueberries - Xue-Qi Zhang; Xiuxian Zhu; Fei Guo; Zi-Ming Zhou; Yu-Ting Zhao; Lin-Xuan Song; Zhao-Yang Zhi; Zi-Hui Liang; Zhen-Ke Li; Chang-Hai Yi; Zhen Wang (Chemical Engineering Journal, 2025)

Targeting neuroblastoma with 3β,5α-tetrahydrocorticosterone: Activation of aryl hydrocarbon receptor inhibits tumor growth, metastasis, and stemness while promoting neural differentiation - Zhu-Qian Wen; Wen-Ming Hsu; Chien-Chun Chiou; Farhan Azhwin Maulana; Chia-Hwa Chang; Jie-Ming Huang; Zhi-Kai Yu; Chien-Chin Chen; Neng-Yu Lin; Chun-FA. Tsai; Jheng-Siou Lai; Yue-Ling Chen; et al. (Chemico-Biological Interactions, 2025)

Fermented Soybean Pulp Alleviates Disease Progression of 5×FAD Model Mice - Chun-Yen Yang; Yu-Hsuan Liu; Ta-Chun Lin; Kuo-Hsuan Chang; Hsiu Mei Hsieh-Li (Molecular Neurobiology, 2025)
Alzheimer’s disease (AD) is the most common neurodegenerative disorder of the central nervous system, characterized by memory loss and cognitive decline. The two main hypotheses regarding AD involve the accumulation of amyloid-β (Aβ) forming plaques and the intracellular hyperphosphorylation of tau protein, leading to the formation of neurofibrillary tangles (NFT). These processes are accompanied by neuroinflammation and oxidative stress, and eventual neuronal death. While soy foods are widely recognized for their nutritional benefits, soybean pulp (okara), the residue left over from making tofu or soybean milk, is mostly discarded as kitchen waste, despite being rich in nutrients such as dietary fiber, protein, and isoflavones. This underutilized byproduct may serve as a valuable resource for functional food development and sustainable resource use. In this study, fermented soybean pulp (FS) demonstrated neuroprotective effects. In vitro, FS at concentrations of 0.001 µg/mL and 0.01 µg/mL significantly improved cell viability in Aβ-induced HT-22 cells and reduced lipid peroxidation. Further, in vivo oral administration of FS attenuated the cognitive deficits of 5 × FAD mice, enhancing both short and long-term memory and reducing anxiety-like behaviors. Immunohistochemical analysis revealed that the FS-treated 5 × FAD mice group significantly reduced hippocampal amyloid plaque accumulation and gliosis. FS also upregulated the expression levels of brain-derived neurotrophic factor (BDNF), PSD95, and synaptophysin, while preventing hippocampal neuronal loss. Mechanistically, FS may activate the Nrf2 antioxidant pathway and NF-κB-mediated inflammation through the modulation of the Akt/GSK3β signaling axis in the hippocampus. These molecular actions likely contribute to increased antioxidant enzymes and suppressed neuroinflammatory responses. Overall, this study suggests that FS has therapeutic potential for alleviating cognitive and behavioral impairments in AD. Moreover, the repurposing of soybean pulp, which would otherwise be discarded, enhances its utilization value and supports sustainable green recycling.

Deep learning-based species identification of gymnosperm xylem: The practice in digital forestry - Chang Zheng; Tuo He; Lichao Jiao; Yang Lu; Shoujia Liu; Tianxiao Li; Yuanyuan Miao; Dejun Feng; Jian Lin; Xian Feng; Zhonghua Huang; Min Yu; et al. (Computers and Electronics in Agriculture, 2025)

An activatable aptamer probe Q2c for detection of grouper iridovirus - Mingzhu Liu; Jing Huang; Lin Huang; Qiwei Qin; Yanlei Chang; Lei Shi; Yun Sun; Yongcan Zhou; Shaowen Wang; Shuyu Han; Qing Yu; Pengfei Li (Aquaculture, 2025)

Estimating and classifying urban carbon budget based on land use intensity with regulatory strategies developing - Li-tzu Yu; Cing Chang; Tzu-Ping Lin (Sustainable Cities and Society, 2025)

Evaluation of the asymmetric distribution of Japanese eel recruitment to eastern and western Japan - Yu-Lin K. Chang; Mari Kuroki (Regional Studies in Marine Science, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

Exploring the anticancer potential of Polygonum barbatum (L.) against colorectal cancer: In vitro and in vivo investigations - Pi-Kai Chang; I-Chuan Yen; Wei-Cheng Tsai; Kuen-Tze Lin; Shih-Yu Lee (Phytochemistry Letters, 2025)

Application of multi-dimensional isotope fractionation to characterize the biotic and abiotic transformation mechanisms of the herbicide 2,4-dichlorophenoxyacetic acid - Jukun Xiong; Yongyu Liang; Chang Yuan; Suyun Chen; Meicheng Wen; Wanjun Wang; Qinhao Lin; Yingxin Yu (Journal of Hazardous Materials, 2025)

Waste valorization into K-doped alumina catalysts via Al-MOF templates for efficient COS hydrolysis - Jia-Yin Lin; Jia-Yu Lee; Pei-Tzu Chang; Chih-Ying Wang (Journal of Environmental Chemical Engineering, 2025)

Rapid detection of duck egg ovalbumin (D-OVA) in surimi via fluorescent immunochromatographic assay utilizing shark-derived single-domain antibody - Zhong-Lin Li; Ling-Jing Zhang; Kai-Yuan Cao; Jian-Lian Huang; Chang-Gong Zhang; Le-Chang Sun; Yu-Lei Chen; Min-Jie Cao (Food Chemistry, 2025)

Effects of puerarin on growth performance, digestive ability, immune response, and resistance to ammonia stress in Pacific white shrimp (Litopenaeus vannamei) in low-salinity water - Yu-Lin Chang; Long Qi; Chao-Li Guan; Yu-Yun He; Wen-Xing Lu; Guo-Fang Zhong (Fish & Shellfish Immunology, 2025)

Perhydroxylated benzoquinoid covalent triazine framework for ultra-high-density lithium-ion storage - Nhu T.H. Luu; Rajeshkumar Anbazhagan; Alexander S. Ivanov; Sung-En Lin; Chia-Hsin Chang; Chen-Yu Hung; Ilja Popovs; Jui-Chin Lee; Teng-Hao Chen; Watchareeya Kaveevivitchai (Chemical Engineering Journal, 2025)

Ultra-long and rapid operating zinc metal batteries enabled by multifunctional polarizable interface stabilizer - Song-Lin Tian; Li Lin; Si-Yu Jiang; Li-Na Song; Hai-Rui Wang; Ping Nie; Li-Min Chang; Wan-Qiang Liu (Chemical Engineering Journal, 2025)

The threat of diaphragm closure to thermal runaway during battery charging - Jianqi Zhang; Tao Fan; Zhengnan Liu; Lin Yu; Yuhui Wang; FangZhou Li; Shuai Yuan; Chongye Chang; Kuo Wang; Ziwei Song; Xinming Qian; Qing Wang (Chemical Engineering Journal, 2025)

Mobile measurements of atmospheric isoprene across subtropical forests in Southern China - Haifeng Yu; Xiangcheng Wu; Lin Cheng; Wen Tan; Liang Zhu; Yunhua Chang (Atmospheric Environment, 2025)

Analysis of the relationship between C, N, P and dry matter content of 41 subtropical woody plants from seasonal and developmental scales - Zheng-Chao Yu; Xiao-Ting Zheng; Wei Lin; Wei He; Hui Zhu; Chang-Lian Peng (Trees, 2025)

The Antimicrobial Peptide Tilapia Piscidin 4 Induced the Apoptosis of Bladder Cancer Through ERK/SIRT1/PGC-1α Signaling Pathway - Chun-Feng Chang; Po-Chih Chang; Yi-Chen Lee; Chieh-Yu Pan; Hui-Min Chang; Wan-Ju Wu; Mei-Ying Lin; Chung-Yi Chen; Zhi-Hong Wen; Chien-Hsing Lee (Probiotics and Antimicrobial Proteins, 2025)

Humidity-dependent ammonium formation and enhanced light scattering in agricultural aerosols - Chien-Hao Lin; Ling-Ya Chen; Ting-Yu Chiang; Sally C. W. Tai; Shih-Yu Chang (Environmental Geochemistry and Health, 2025)

Both biotic and abiotic soil N₂O productions are lower under organic N than inorganic N deposition in a Moso bamboo forest - Wenting Jiang; Yan Wang; Yongxin Lin; Hiroko Akiyama; Yunying Fang; Tony Vancov; Shenglei Fu; Hojeong Kang; Xinli Chen; Zhengqin Xiong; Zhijie Li; Shuijin Hu; et al. (Biology and Fertility of Soils, 2025)

A novel approach for quantifying therapeutic monoclonal antibodies in blood through liquid chromatography–tandem mass spectrometry - Tsun-Hao Chi; Chiao Lo; Shin-Yi Lin; Yi-Hsin Liang; Wen-Chi Chang; Chia-Yu Yeh; Huai-Hsuan Chiu; Ching-Hua Kuo (Analytica Chimica Acta, 2025)

System temperature prediction and verification of all-sky electrostatic analyzer on the lunar surface - Tsung-Pin Hung; Chih-Yu Chiang; Tzu-Fang Chang; Zhao-Yu Huang; Yu-Rong Cheng; Sheng-Cheng Tsai; Tzu-En Yen; Jih-Run Tsai; Shin-Fa Lin (Advances in Space Research, 2025)

Geological Structural Characteristics of Subashi in West Kunlun Revealed by Aero Geophysical and Remote Sensing Data - Ming Wang; Yi-chuan Li; Hai-qing Wang; Yan-yan Wei; Xiao-xing Lin; Dao-qing Zhou; Jin-zhong Yang; Chang Zhong; Chang-chun Yu (Applied Geophysics, 2025)

Atmospheric emerging pollutants of cyclic volatile methyl siloxanes across the Yangtze River Delta region revealed by mobile measurements - Lin Cheng; Yunhua Chang; Haifeng Yu; Xiang Che; Wen Tan; Liang Zhu (Chemosphere, 2025)

A three-dimensional Pt@Ti₃C₂Tₓ-based smart platform for discrimination of hydrated ammonia in multi‐scenario environmental monitoring - Qingqing Zhou; Chencheng Hu; Yu Qi; Xiaoyi Tan; Jiaqi Yang; Zitong Kan; Long Yang; Biao Dong; Zhiyong Chang; Hongwei Song; Lin Xu (Journal of Hazardous Materials, 2025)

Sustainable aviation fuel and next-generation aircraft: Low-carbon pathway for China's civil aviation industry - Rui Yan; Bao-Jun Tang; Yu-Jie Hu; Chang-Jing Ji; Kun-Ben Lin; Meng Shen (Journal of Environmental Management, 2025)

Fundamental study of horizontal wind velocity effect on PM2.5 and PM10 sampling accuracy of low-Cost sensors - Yi-Ming Lee; Thi-Cuc Le; Ying-Chang Chen; Gung-Hwa Hong; Guan-Yu Lin; Chuen-Jinn Tsai (Journal of Aerosol Science, 2025)

Synergistic treatment of respiratory syncytial virus induced pneumonia by multifunctional Baicalin-Resveratrol self-assembled nanomedicine - Chenqi Chang; Yu Zheng; Chang Lu; Ying Ma; Liang Wu; Yunyu Zhang; Lili Lin; Liang Guo; XiuZhen Chen; Linwei Chen; Jianming Cheng; Rui Chen (Chemical Engineering Journal, 2025)

Isolation and functional identification of Jasmonate resistant 1, a Jasmonic acid isoleucine-conjugating enzyme in Catharanthus roseus - Aikun Pan; Haiqiao Gao; Ying Lin; Bingrun Yang; Chunhao Chang; Zhiwen Liu; Yanyan Wang; Zhaoxia Jin; Fang Yu (Journal of Plant Research, 2025)

Updated insights into steady-modified anthocyanin food packaging: Novel strategies, characterization, application and future challenges - Jia-Yin Huang; Yu-Lei Chen; Duan-Quan Lin; Le-Chang Sun; Kang Liu; Ling-Jing Zhang; Ya-Qin Hu; Min-Jie Cao (Food Chemistry, 2025)

SYNLAC Prime probiotics alleviate Enterocytozoon hepatopenaei-induced damage in white shrimp, Penaeus vannamei by enhancing growth, immunity, and resistance to Vibrio parahaemolyticus - Ann-Chang Cheng; Hsiao-Tung Chang; Ting-Yu Lee; Jin-Seng Lin; Chun-Hung Liu (Fish & Shellfish Immunology, 2025)

FlashSim: A novel particle-in-cell numerical model for vacuum surface flashover simulation based on finite element method - Hao-Yan Liu; Guang-Yu Sun; Yue-Lin Liu; Shu Zhang; Chang-Chun Qi; Sheng Zhou; Wen-Rui Li; Guan-Jun Zhang (Computer Physics Communications, 2025)

Revolutionary photoelectrochemical water splitting performance of BiVO₄/Bi₂S₃ heterojunction photoanodes boosted by trace bio-Cr₂O₃ through multiple mechanisms - Yefei Su; Yang Yu; Tingting Xue; Kai Teng; Yuning Fan; Jiangjun Lin; Chang Liu; Qing Qu; Lei Li (Chemical Engineering Journal, 2025)

Comparative Analysis of Stent-Assisted Versus Non-Stent-Assisted Coiling in the Management of Ruptured Intracranial Aneurysms: A Systematic Review and Meta-Analysis - Yu-Hu Ma; Yong-Lin He; Xiao-Yue Zhang; Rui Shang; Hai-Tao Hu; Ting Wang; Sen Lin; Ya-Wen Pan; Chang-Wei Zhang (Translational Stroke Research, 2025)

CCN1 Is a Therapeutic Target for Reperfused Ischemic Brain Injury - Gilbert Aaron Lee; Yu-Wei Chang; Jing-Huei Lai; Tzu-Hao Chang; Shiu-Wen Huang; Chih‑Hao Yang; Ting-An Shen; Wan-Li Lin; Ying-Chieh Wu; Li-Wen Tseng; Sung-Hui Tseng; Yung-Chieh Chen; et al. (Translational Stroke Research, 2025)

Astrocytic P2X7 receptor in retrosplenial cortex drives electroacupuncture analgesia - Wei Zhao; Si-Le Liu; Si-Si Lin; Ying Zhang; Chang Yu (Purinergic Signalling, 2025)

Enhanced Hair Growth Through Transdermal Delivery of Bacopa Monnieri Extract Using a Needle-Free Supersonic Atomizer - Yu-Chiuan Wu; Yi-Ping Lin; Ching-Yi Chang; Hsia-Ying Cheng; Tien-Huei Chu; Chien-Chih Chen; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2025)

Exploring Lumbar Ligamentum Flavum, Disc Height and Foraminal Height Variations Across Different Postures: A Cadaveric Computed Tomography Investigation - Yuan-Fu Liu; Nozomu Inoue; Yu-Hua Dean Fang; Jing-Yao Wang; Alejandro A. Espinoza Orías; Chao-Jui Chang; Cheng-Li Lin (Journal of Medical and Biological Engineering, 2025)

Phage Therapy Enhances Survival, Immune Response, and Metabolic Resilience in Pacific White Shrimp (Litopenaeus vannamei) Challenged with Vibrio parahaemolyticus - Chao Zeng; Long Qi; Chao-Li Guan; Yu-Lin Chang; Yu-Yun He; Hong-Zheng Zhao; Chang Wang; Yi-Ran Zhao; Yi-Chen Dong; Guo-Fang Zhong (Fishes, 2025)
Acute hepatopancreatic necrosis disease (AHPND), caused by the bacterium Vibrio parahaemolyticus, is a major threat to global shrimp aquaculture. In this study, we evaluated the therapeutic effects of phage therapy in Litopenaeus vannamei challenged with AHPND-causing Vibrio parahaemolyticus. Phage application at various concentrations significantly improved shrimp survival, with the 1 ppm group demonstrating the highest survival rate. Enzymatic assays revealed that phage-treated shrimp exhibited enhanced immune enzyme activities, including acid phosphatase (ACP), alkaline phosphatase (AKP), and lysozyme (LZM). In addition, antioxidant defenses such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-PX), and total antioxidant capacity (T-AOC) significantly improved, accompanied by reduced malondialdehyde (MDA) levels. Serum biochemical analyses demonstrated marked improvements in lipid metabolism, particularly reductions in triglyceride (TG), total cholesterol (TC), and low-density lipoprotein (LDL), alongside higher levels of beneficial high-density lipoprotein (HDL). Transcriptomic analysis identified 2274 differentially expressed genes (DEGs), notably enriched in pathways involving fatty acid metabolism, peroxisome functions, lysosomes, and Toll-like receptor (TLR) signaling. Specifically, phage treatment upregulated immune and metabolic regulatory genes, including Toll-like receptor 4 (TLR4), myeloid differentiation primary response protein 88 (MYD88), interleukin-1β (IL-1β), nuclear factor erythroid 2-related factor 2 (Nrf2), and peroxisome proliferator-activated receptor (PPAR), indicating activation of innate immunity and antioxidant defense pathways. These findings suggest that phage therapy induces protective immunometabolic adaptations beyond its direct antibacterial effects, thereby providing an ecologically sustainable alternative to antibiotics for managing bacterial diseases in shrimp aquaculture.

Mercury flows in a cement plant adopting circular economy policies - Liang Yu Chen; Chia Chi Hsu; Chin Lung Lin; Ming Lun Lu; Hung Lin Chiang; Moo Been Chang (Waste Management, 2025)

Petrogenesis and tectonic implication of the Neoproterozoic Shuimo alkaline-carbonatite complex from Northwestern margin of the Yangtze Block (China) - Bin Lin; Lian-Xun Wang; Yu-Fang Zhong; Xiao-Bing Qi; Xue-Wei Fu; Chang-Qian Ma (Precambrian Research, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

A numerical study of NO removal from exhaust gas at low-temperature using metal Zeolite catalysts - Way Lee Cheng; Ding-Hui Wang; Yi-Chi Chang; Pei-Cheng Cheng; Yu-Zheng Wang; Yuan-Chung Lin (Fuel, 2025)

Tailoring Cu3Nx clusters on TiO2 nanosheets to the sub-nanometric scale for enhancing NH3 photosynthesis - Hyun Sik Moon; Yu-Jeong Yang; Getasew Mulualem Zewdie; Geon Youn; Yi-An Chen; Yu-Peng Chang; Kai-Chi Hsiao; Ting-Han Lin; Yi-Dong Lin; Jun Kue Park; Jucheol Park; Yan-Gu Lin; et al. (Chemical Engineering Journal, 2025)

Building with nature: Morphological spatial pattern of green infrastructure in urban heat mitigation - Bau-Show Lin; Yu-Hua Tsai; Han-Chin Chang; Chin-Chung Yu; Cheng-I Hsieh (Building and Environment, 2025)

Reversing Neuronal Klotho Dysfunction–Mediated Diabetic Neuropathy Through 16:8 Intermittent Fasting - Ying-Shuang Chang; Yu-Yu Kan; Tzu-Ning Chao; Yi-Hsuan Chen; Yu-Lin Hsieh (Molecular Neurobiology, 2025)

Alternating electric field as an effective inhibitor of bioavailability and phytotoxicity of heavy metals during electric field-assisted aerobic composting - Tao Fu; Chang Shen; Huan Mi; Jiahuan Tang; Long Li; Hao Lin; Huayuan Shangguan; Zhen Yu (Journal of Hazardous Materials, 2025)

Electric field-assisted aerobic composting: From basic principles to applications - Tao Fu; Huan Mi; Chang Shen; Shuqun Zhang; Huayuan Shangguan; Jiahuan Tang; Hao Lin; Zhen Yu (Journal of Environmental Management, 2025)

Mantle evolution beneath a back-arc basin: Highly siderophile elements and Os isotope of Dongco ophiolitic peridotites, Tibet - Xiao-Ni Li; Wei-Qi Zhang; Tong Liu; Chang Zhang; Yin-Zheng Lin; Zhen Zhang; Jia-Ning Zhu; Hong-Yu Li; Chuan-Zhou Liu (Chemical Geology, 2025)

Field experiment study to assess critical wave conditions leading to failure of mangrove Rhizophora stylosa - Nobuhito Mori; Che-Wei Chang; Kenji Ono; Hironori Noguchi; Shigeyuki Baba; Hideaki Yanagisawa; Toyohiko Miyagi; Naoki Tsuruta; Kojiro Suzuki; Shiro Yamagata; Yusuke Hasegawa; Yu-Lin Tsai; et al. (Coastal Engineering, 2025)

Spatiotemporal response of agricultural drought to meteorological drought in the upper Hanjiang River Basin from three-dimensional perspective - Shenghong Liu; Shaokang Yang; Ji Liu; Te Zhang; Qingxia Lin; Wenjuan Chang; Tao Peng; Dan Yu (Agricultural and Forest Meteorology, 2025)

Potential links between the progress in environmental governance and the prevalence of mental disorder burden: New insight from a dynamic panel-data analysis for 197 countries - Jun-Yan Xi; Li-Chang Chen; Xue-Qi Li; Jie Hu; Wei Hu; Jian-Jun Bai; Yi-Ning Xiang; Yu-Can Zhang; Jia-Jia Wang; Shi-Hao Wang; Jing Gu; Yuan-Tao Hao; et al. (Sustainable Cities and Society, 2025)

Deriving leaf-scale chlorophyll index (CIleaf) from canopy reflectance by correcting for the canopy multiple scattering based on spectral invariant theory - Chenpeng Gu; Jing Li; Qinhuo Liu; Hu Zhang; Alfredo Huete; Hongliang Fang; Liangyun Liu; Faisal Mumtaz; Shangrong Lin; Xiaohan Wang; Yadong Dong; Jing Zhao; et al. (Remote Sensing of Environment, 2025)

Development of an alkali-producing bioelectrochemical system for sewage-polluted seawater: nutrient removal, scalant mitigation, and resource recovery - Chao-Chin Chang; Chieh-Yun Wu; Jia-Zhe Jiang; Chen-An Hsu; Chang-Ping Yu; Yi-Li Lin (Journal of Water Process Engineering, 2025)

High content heteroatoms doped and valuable biomass derived activated carbon composited with graphene for high performance supercapacitors - Ming-Che Cheng; Yu-Sung Chang; Du-Cheng Tsai; Yen-Lin Huang; Fuh-Sheng Shieu (Fuel, 2025)

Synergistic effects of matrix metalloproteinases on the degradation of collagen in abalone (Haliotis discus hannai) - Yu-Lei Chen; Le-Le Su; Hua Liu; Tian-Bo Zhang; Guiling Li; Le-Chang Sun; Duanquan Lin; Tengchuan Jin; Ling-Jing Zhang; Min-Jie Cao (Food Chemistry, 2025)

Parallel floral evolution of Lilium species pollinated by pierid butterflies - Yun-Bo Duan; Hong-Qiang Lin; Zhe Chen; Chang-Qiu Liu; Yu-Mei Yuan; Yun-Dong Gao; Mei-Yan Lei; Mao-Lin Wang (Flora, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Human Umbilical Cord Mesenchymal Stem Cells for the Treatment of Systemic Lupus Erythematosus via Glucose Metabolism of CD4+T Cells - Meng Ding; Lu Jin; Shaoxin Cui; Lin Yang; Jingjing He; Xiaoping Wang; Fei Chang; Qun Wang; Xue Liu; Hongtao Jin; Shuran Song; Min Shi; et al. (Stem Cell Reviews and Reports, 2025)

Correlation between the utilization of sodium-glucose cotransporter-2 (SGLT2) inhibitors and the risk of dementia: a nationwide population-based study in Taiwan - Wu-Lung Chuang; Stella Chin-Shaw Tsai; Yi-Chun Yang; Tsai-Ling Hsieh; Heng-Jun Lin; Yu-Han Huang; Fuu-Jen Tsai; Kuang-Hsi Chang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Spinocerebellar Ataxia 44 Caused by a Novel GRM1 Variant: Reviewing the Contrasting Pathogenic Mechanisms Underlying Two GRM1-Associated Hereditary Ataxias - Shih-Chun Lan; Yung-Yee Chang; Tsu-Kung Lin; Min-Yu Lan (The Cerebellum, 2025)

Origin and metamorphism of ophiolitic serpentinites from the Yuli belt, eastern Taiwan: new findings and tectonic implications - Dominikus Deka Dewangga; Chin-Ho Tsai; Yoshiyuki Iizuka; Ilona Talvikki Sakaguchi; Yui Kouketsu; Sun-Lin Chung; Chi-Yu Lee; Wen-Yen Chang; Huei-Fen Chen (International Geology Review, 2025)

Knockout of dead end 1 by CRISPR/Cas9 leads to loss of germ cells and male-biased sex development in freshwater angelfish (Pterophyllum scalare) - Wai-Kwan Chu; Shih-Chin Huang; Ching-Fong Chang; Yu-Ho Lin; Jen-Leih Wu; Hong-Yi Gong (Aquaculture, 2025)

Dietary supplementation with Pediococcus pentosaceus promotes resistance to betanodavirus and ranavirus in giant groupers - Chun-Kuei Chang; Zhe-Li Lin; Yu-Hsuan Kai; Mu-Yun Peng; Yu-Chi Wu (Aquaculture, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Synergistic properties of single-component hexagonal iron borate for superior and sustainable photo-Fenton catalysis - Po-Yi Wu; Jing-Cheng Hsu; Tsung-Yueh Lin; Yu-Lun Zhu; Yu-Rong Chang; Pei Yuin Keng (Journal of Environmental Chemical Engineering, 2025)

Chemical constituents from the pericarps of Zanthoxylum bungeanum Maxim. and their chemotaxonomic significance - Di-Wei Ma; Khalid Hassan Mohamed; Jian-Lin Hu; Chang-Qin Yin; Yu-Bin Wei; Xiao-Pan Chai; Qing-Bao Zhang; Lan-Chun Zhang; Jia Liu; Hao-Fei Yu (Biochemical Systematics and Ecology, 2025)

Displacement evolution of failure and non-failure sliding rock slopes - Hsien-Li Kuo; Guan-Wei Lin; Ting-Yu Lin; Che-Hsin Liu; Chung-Ray Chu; Chih-Hsin Chang; Ching-Weei Lin; Hongey Chen (Landslides, 2025)

Multi-omics analysis reveals the potential mechanisms underlying long-term exercise-induced enhancement of learning and memory in male mice - Qiu-Xia Xiao; Hao-Yue Qin; Jun-Jie Chen; Chang-Le Fang; Qiu-Lin Wang; Qi-Jun Li; Shuai-Yu Zhu; Liu-Lin Xiong (Biogerontology, 2025)

What does it mean when the pleasant smells come and go? Correlation between UPSIT odor identification status and fluctuation of non-motor symptoms in Parkinson’s disease - Hsin-Bei Lei; Ting-Chun Fang; Yu-Hsuan Lin; Shih-Chi Chiu; Ming-Hong Chang; Yi-Jen Guo (Acta Neurologica Belgica, 2025)
Parkinson’s disease (PD) is characterized by motor and non-motor symptoms, including olfactory dysfunction. Prior studies have shown that olfaction deteriorates with disease progression, however fluctuations in olfaction and related PD symptoms have been less explored. This study aimed to investigate correlations between changes in odor identification ability and PD symptoms. PD patients recruited from Taichung Veterans General Hospital underwent at least two consecutive Movement Disorder Society Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) and University of Pennsylvania Smell Identification Test (UPSIT) evaluations. The patients were grouped based on changes in olfactory identification ability between evaluations, and fluctuations in PD symptoms were compared between groups. Ninety-seven PD patients with 114 complete sets of data were analyzed. Significant divergent results were observed between changes in five MDS-UPDRS non-motor subscores and the conversion status of five pleasant odors, including anxiety vs. bubble gum, apathy vs. banana, dizziness vs. coconut, urination vs. root beer, and dopamine dysregulation syndrome (DDS) vs. grape. Fluctuations in the ability to detect pleasant odors, may have a complex interaction with other non-motor symptoms, including in the neurobehavioral and autonomic domains. Serial monitoring of olfactory function, particularly with pleasant odors, may provide valuable insights for tracking non-motor symptoms in PD and warrants further investigation into their therapeutic implications.

Genetic Analysis of Polyunsaturated Fatty Acids Biosynthesis Pathway Determines Four Distinct Thraustochytrid Types - Sou‐Yu Cheng; Yi‐Jing Chen; Hsiu‐Chin Lin; Hsin‐Yang Chang; Ming‐Der Huang (Environmental Microbiology, 2025)
Thraustochytrids, diverse marine unicellular protists encompassing over 10 recognised genera, are renowned for synthesising polyunsaturated fatty acids (PUFAs), with content and composition varying substantially across genera. While PUFAs are known to be produced via PUFA synthase (PUFA‐S) and/or elongase/desaturase (ELO/DES) pathways, the distinctions in genes involved remain unexplored. This study analysed PUFA biosynthetic genes in 19 thraustochytrid strains across six genera, categorising them into four types. Type I exclusively utilises the ELO/DES pathway, Type II employs both PUFA‐S and complete ELO/DES pathways, while Types III and IV primarily rely on PUFA‐S, with Type III lacking the canonical Δ9 desaturase and Type IV missing most desaturase and elongase enzymes. Notably, the Δ9 desaturase and ATP‐citrate lyase ( ACLY ) are exclusive to Types I and II, while β‐carotene hydroxylase ( CrtZ ) is absent in these types. ACLY absence suggests alternative acetyl‐CoA supply pathways in Types III and IV, whereas CrtZ absence implies either a lack of specific xanthophylls or alternative biosynthetic pathways in Types I and II. Synteny analysis revealed conserved genomic organisation of PUFA biosynthetic genes, indicating a shared evolutionary trajectory. This study provides insights into the genetic diversity underlying PUFA biosynthesis in thraustochytrids, while proposing putative evolutionary pathways for the four lineages.

Artificial digestion represents the worst-case scenario for studying nanoplastic fate in gastrointestinal tract - Giselle Lee; Ya-Jhu Jhang; Yu-Tung Jhang; Yen-Chen Chang; Hui-Wen Chang; Chun-Yu Chuang; Yung-Kun Chuang; Ching-Wei Lin; I-Lun Hsiao (Journal of Hazardous Materials, 2025)

Effect of microwave plasma processing on the structure, physicochemical properties and functional properties of rice bran protein - Chang Liu; Ning Wang; Lin Li; Dandan Wu; Liqi Wang; Na Zhang; Dianyu Yu (Food Hydrocolloids, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Mobile measurements of atmospheric decamethylcyclopentasiloxane (D5) in Eastern China - Haifeng Yu; Yunhua Chang; Lin Cheng; Wen Tan; Liang Zhu; Jianlin Hu (Atmospheric Environment, 2025)

Interannual early life history variation and larval dispersal of three tropical anguillid eel species recruiting in French Polynesia - Julie Viana; Fabien Morat; Michael J. Miller; Yu-Lin Chang; Émilie Boissin; Pierre Sasal (Reviews in Fish Biology and Fisheries, 2025)

In vitro and in silico studies on α-glucosidase inhibitory properties of bioactive components from the rhizomes of Alpinia officinarum Hance - Zakhele Mphatsi Dlamini; Bongani Sicelo Dlamini; Shih-Han Fu; Ya-Lin Chang; Chi-Chien Lin; Yu-Kuo Chen; Kok-Tong Tan; Chi-I Chang (Medicinal Chemistry Research, 2025)

Indoxyl Sulfate Induces Ventricular Arrhythmias Attenuated by Secretoneurin in Right Ventricular Outflow Tract Cardiomyocytes - Yuan Hung; Chen-Chuan Cheng; Yen-Yu Lu; Shih-Yu Huang; Yao-Chang Chen; Fong-Jhih Lin; Wei-Shiang Lin; Yu-Hsun Kao; Yung-Kuo Lin; Shih-Ann Chen; Yi-Jen Chen (Cardiovascular Toxicology, 2025)

AI integration into wavelength-based SPR biosensing: Advancements in spectroscopic analysis and detection - Ying-Feng Chang; Yu-Chung Wang; Tsung-Yu Huang; Meng-Chi Li; Sin-You Chen; Yu-Xen Lin; Li-Chen Su; Kwei-Jay Lin (Analytica Chimica Acta, 2025)

Correction: CCL4 contributes to aging related angiogenic insufficiency through activating oxidative stress and endothelial inflammation - Ting-Ting Chang; Liang-Yu Lin; Ching Chen; Jaw-Wen Chen (Angiogenesis, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Spatial and temporal variation of nutrient distribution in the Yangtze River estuary and adjacent waters: Insights from GOCI data analysis - Chaozhi Yu; Cancan Lu; Yangdong Li; Hongli Li; Jun Lin; Liang Chang (Marine Environmental Research, 2025)

Remnants of a Jurassic marginal sea plate in the Meso-Tethyan Ocean revealed by multi-stage magmatism in the Lagkorco ophiolite, Central Tibet - Wei-Qi Zhang; Chuan-Zhou Liu; Tong Liu; Chang Zhang; Xiao-Ni Li; Zhen-Yu Zhang; Zhen Zhang; Yin-Zheng Lin (Lithos, 2025)

Monitoring soil arsenic content in densely vegetated agricultural areas using UAV hyperspectral, satellite multispectral and SAR data - Yanan Zhou; Chang Liu; Jie Wang; Mei-Wei Zhang; Xiaoqing Wang; Ling-Tao Zeng; Yu-Pei Cui; Huili Wang; Xiao-Lin Sun (Journal of Hazardous Materials, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

Research on the explosive characteristics and suppression mechanisms of gas generation during thermal runaway of batteries in a charged state - Jianqi Zhang; Fangzhou Li; Lin Yu; Yuhui Wang; Kuo Wang; Chongye Chang; Minghui Li; Wenhao Hao; Xinming Qian (Chemical Engineering Journal, 2025)

Integrating sentinel-2a imagery, DEM data, and spectral feature analysis for landslide detection via fully convolutional networks - Yu Qu; Hanfa Xing; Lin Sun; Xian Shi; Jianfeng Huang; Zurui Ao; Zexiu Chang; Jiaju Li (Landslides, 2025)

Recycling of subduction-modified refractory mantle beneath the Marion Rise, Southwest Indian Ridge - Yin-Zheng Lin; Chuan-Zhou Liu; Wei-Qi Zhang; Zhen-Yu Zhang; Chang Zhang; Tong Liu (Contributions to Mineralogy and Petrology, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

Modeling and analysis of explicit dynamics of foot landing - Wu Ren; Ziya Zhao; Shuaiheng He; Xueling Zhang; Kailu Zhang; Yawei Li; Fei Lin; Zhenghui Wang; Guoan Zhao; Jinlong Chang; Qianfang Jia; Yi Yu; et al. (Medical & Biological Engineering & Computing, 2025)

Sulfur-functionalized sawdust biochar for enhanced cadmium adsorption and environmental remediation: A multidisciplinary approach and density functional theory insights - M.M.M. Ahmed; Chih-Hao Liao; S. Venkatesan; Yu-Ting Liu; Yu-Min Tzou; Shih-Hao Jien; Ming-Chang Lin; Yi-Cheng Hsieh; Ahmed I. Osman (Journal of Environmental Management, 2025)

Phosphine oxide functionalized porous aromatic frameworks enabled wireless bionic olfactory system with preconcentration capability for trace ammonia monitoring - Shuai Zhao; Hongyang Jin; Zihao Chen; Yonglai Zhang; Xiaoqin Zou; Lin Xu; Shaolei Wang; Zhenglei Yu; Zhiyong Chang (Chemical Engineering Journal, 2025)

Box-shaped necklace-like Fe3O4/MoS2-CNFs composite nanofibers with confinement effect enhancing sodium storage performance - Huayu Wu; Mohan Yue; Lin He; Miao Zhang; Yimin Huang; Chang Sun; Yu Liu; Jindi Wang; Rongguan Lv; Rong Xing (Chemical Engineering Journal, 2025)

Northern shifts in the migration of Japanese glass eels to subarctic Hokkaido Island over the past three decades - Yu-Lin K. Chang; Kentaro Morita; Kanta Muramatsu; Osamu Kishida; Mari Kuroki (Ocean Dynamics, 2025)

Changes in the small-molecule fingerprints of rice planted near an industrial explosion site in Taiwan - Wen-Ling Chen; Husan-Yu Tai; Chang-Chuan Chan; Hung-Chien Lin; Ting-Hsuan Hung; Mong-Hsun Tsai; Chia-Cheng Wei; Yu-San Han; Chuan-Chou Shen (Environmental Science and Pollution Research, 2024)

Protective Effects of Antcin H Isolated from Antrodia cinnamomea Against Neuroinflammation in Huntington’s Disease via NLRP3 Inflammasome Inhibition - Yu-Jun Chang; Cheng-Hsu Chen; Yi-Chen Chen; Ming-Tse Wu; Ting-Yu Lin; Kuo-Feng Hua; Tz-Chuen Ju (Journal of Neuroimmune Pharmacology, 2024)

Combining geographic information and climate data to develop urban building energy prediction models in Taichung, Taiwan - Cing Chang; Chieh-Yu Chen; Tzu-Ping Lin (Sustainable Cities and Society, 2024)

Quantifying the effects of the microphysical hygroscopic restructuring of soot on ensemble optical properties and satellite aerosol optical depth retrievals - Kuo-En Chang; Tang-Huang Lin; Ta-Chih Hsiao; Yi-Ling Chang; Tzu-Chi Lin; Chih-Yu Chan; Charles C.-K. Chou (Science of The Total Environment, 2024)

First direct measurements of the nitrogen isotopic composition of vehicle tailpipe-emitted NH3 and implications for the source apportionment of NH3 in urban atmosphere - Yu-Ning Feng; Yunhua Chang; Lin Cheng; Haifeng Yu; Jinling Lv; Wendell W. Walters (Science of The Total Environment, 2024)

Observation-based quantification of aerosol transport using optical flow: A satellite perspective to characterize interregional transport of atmospheric pollution - Tianhao Zhang; Yu Gu; Bin Zhao; Lunche Wang; Zhongmin Zhu; Yun Lin; Xing Chang; Xinghui Xia; Zhe Jiang; Hongrong Shi; Wei Gong (Remote Sensing of Environment, 2024)

Long-term subculture induces syncytialization and influent the response to bisphenol A (BPA) of placental JEG-3 cells - Yu-Shiuan Huang; Ai-An Chang; Zhi-Jie Yang; Jung-An Chen; Chi-Kang Lin; Hsin-Chieh Lan (Reproductive Toxicology, 2024)

Sulfur-functionalized rice straw biochar for enhanced cadmium sorption: Spectroscopic, kinetic and computational insights - M.M.M. Ahmed; Chih-Hao Liao; Yu-Ting Liu; S. Venkatesan; Yi-Chen Hsieh; H.M. Nail; Hui-Min David Wang; Ming-Chang Lin; Shih-Hao Jien; Yu-min Tzou (Journal of Cleaner Production, 2024)

The impact of cooking methods on the physical, sensory, and nutritional quality of fish - Sook Chin Chew; Yu Hsuan How; Lee Sin Chang; Choon Hui Tan; Kalvin Meng Jun Chuo; Stephenie Yoke Wei Wong; Pascal Degraeve; Kar Lin Nyam (International Journal of Gastronomy and Food Science, 2024)

SYNLAC prime probiotics enhances growth performance, and resistance of white shrimp, Penaeus vannamei to Enterocytozoon hepatopenaei and Vibrio alginollyticus: Insights into immune and metabolic pathway modulations - Ann-Chang Cheng; Hsiao-Tung Chang; Ting-Yu Lee; Jin-Seng Lin; Chun-Hung Liu (Fish & Shellfish Immunology, 2024)

Di(2-ethylhexyl) phthalate disrupts circadian rhythm associated with changes in metabolites and cytochrome P450 gene expression in Caenorhabditis elegans - Pei-Ling Yen; Ting-An Lin; Chun-Han Chang; Chan-Wei Yu; Yu-Hsuan Kuo; Tzu-Ting Chang; Vivian Hsiu-Chuan Liao (Environmental Pollution, 2024)

The association of air pollution with blood pressure, heart rate and stress among office workers using essential oils - Chien-Yu Lee; I-Jung Liu; Chih-Hong Pan; Lian-Yu Lin; Hsiao-Chi Chuang; Kin-Fai Ho; Chia-Huang Chang; Kai-Jen Chuang (Atmospheric Environment, 2024)

The Association Among Urinary Di-(2-ethylhexyl) Phthalate Metabolites, Serum Lipid Profiles, and Serum Apoptotic Microparticles in a Young Taiwanese Population - Chien-Yu Lin; Sandy Huey-Jen Hsu; Ching-Way Chen; Chikang Wang; Fung-Chang Sung; Ta-Chen Su (Exposure and Health, 2024)

Positive Association Between Serum Concentration of 4-Tertiary-octylphenol and Oxidation of DNA and Lipid in Adolescents and Young Adults - Chien-Yu Lin; Hui-Ling Lee; Chikang Wang; Fung-Chang Sung; Ta-Chen Su (Exposure and Health, 2024)

Validation of the constitution in Chinese medicine questionnaires with the newly developed blood-vacuity category: a rare Taiwanese case study - Ting-Yu Huang; Shi-Chen Ou; Wei-Te Huang; Yu-Chuan Lin; Hao-Hsiu Hung; Chin-Wei Chang; Kai-Yuan Hsiao; Yi-Wei Kao; Chien-Hua Wu; Wei-Shan Chang; Ben-Chang Shia; Sheng-Teng Huang (Advances in Traditional Medicine, 2024)

Improved identification and tracking of three-dimensional eddies in the Southern Ocean utilizing 3D-U-Res-Net - Chang Liu; Xiayan Lin; Guangjun Xu; Guoqing Han; Yu Liu (Frontiers in Marine Science, 2024)
Oceanic mesoscale eddies are prevalent throughout the global ocean, playing a critical role in material and energy transport while significantly influencing climate change. Accurate characterization of their three-dimensional structures and movement is essential for a quantitative analysis of their transport processes. Traditional eddy detection algorithms have lower successful detection rate and with more limitations, so they fall short in the complex and dynamic ocean environment. The rising trend of applying artificial intelligence (AI) algorithms, due to their efficiency, precision, and automation, addresses this challenge. This study employs the 3D-U-Res-Net algorithm to identify the three-dimensional structures of mesoscale eddies in the Southern Ocean using GLORYS12V1 data from 2011 to 2020. A vector geometry-based eddy detection algorithm (VG) initially identified 1587292 eddy snapshots in the Southern Ocean (2011–2019), which were used for training the 3D-U-Res-Net algorithm. Data from 2020 served as the ground truth and validation set. The successful detection rate of 3D-U-Res-Net algorithm is 100%, which means that it identified all 135734 eddy snapshots from the VG dataset in 2020. For eddy tracking, the VG algorithm counted 18168 eddy tracks, whereas the 3D-U-Res-Net counted 18559, reflecting a 2.15% bias. To reduce uncertainty, eddies with lifespans shorter than two weeks were excluded. The average lifespans and traveling distances for eddies detected by the 3D-U-Res-Net (VG) algorithm were 29.35 (29.61) days and 77.78 (37.60) km, respectively, with the 3D-U-Res-Net identifying eddies with longer traveling distances. The mean radius of eddies detected by the VG algorithm was 43.16 km, while the 3D-U-Res-Net detected eddies with a mean radius of 43.74 km, a 0.58 km increase. We categorized eddies into four three-dimensional structures: bowl-shaped, cone-shaped, lens-shaped, and cylindrical. The VG algorithm identified these structures in proportions of 32%, 31%, 25%, and 12%, respectively, whereas the 3D-U-Res-Net algorithm found 19.48%, 19.58%, 0.04%, and 60.9%, respectively. The 3D-U-Res-Net identified more cylindrical eddies and was approximately ten times faster than the VG algorithm. Overall, this algorithm has good performance and higher efficiency. It is an attempt of using AI for oceanic research, and more works can be carried out in the future.

Coral mariculture using abandoned abalone farming ponds in northeastern Taiwan - Shinya Shikina; Yin-Chu Cheng; Tzu-Chieh Lin; Yu-En Chang; Pin-Hsuan Tsai; Emma Chen; Yu-Chuan Chang; Yuen-Yi Leung; Yi-Chun Yu; Yi-Ling Chiu (Aquaculture, 2024)

Performance and biotoxicity of electro-Fenton treatment of bisphenol A: Evaluation of copper recovered from microbial fuel cell cathodes for subsequent catalytic applications - Chi-Wen Lin; Guan-Yi Chen; Shu-Hui Liu; Wei Tong Chen; Shih-Hsien Chang; Chih-Yu Ma (Process Safety and Environmental Protection, 2024)

Enhancing effect of conductive materials and rumen microorganisms on the anaerobic digestion performance of a real traditional Chinese medicine wastewater - Han Gao; Xiang-Lin Chang; Su Li; Rong Chen; Yu-You Li; Bao-Shan Xing (Journal of Water Process Engineering, 2024)

High-contrast electrochromic coatings and devices for health assurance, visual comfort and energy-saving in buildings - Chung-Wen Kuo; Han-Yu Chen; Chen-Hao Yeh; Yuan-Chung Lin; Jeng-Kuei Chang; Pei-Ying Lee; Tzi-Yi Wu (Energy and Buildings, 2024)

A wearable exhaled breath condensate (EBC) collector with controllable condensation microfluidics and a branched hydrophilic film - Chun-Hao Chang; Ying-Hsuan Yu; Hsiu-Pen Lin; Ping-Hsien Tsou; Yaw-Kuen Li; Bor-Ran Li (Chemical Engineering Journal, 2024)

Role of HIF-1α-Activated IL-22/IL-22R1/Bmi1 Signaling Modulates the Self-Renewal of Cardiac Stem Cells in Acute Myocardial Ischemia - Wei Lee; Syuan-Ling Lin; Chih-Sheng Chiang; Jui-Yu Chen; Wee-Wei Chieng; Shu-Rou Huang; Ting-Yu Chang; B. Linju Yen; Mien-Chie Hung; Kuan-Cheng Chang; Hsu-Tung Lee; Long-Bin Jeng; et al. (Stem Cell Reviews and Reports, 2024)

Evaluation of air pollution tolerance index of urban roadside young leaf and the correlation with its capturing capacity for water-insoluble fine particulate matters - Chen He; Zhuofan Zhang; Qi Wang; Yupeng Zhang; Chenhui Wei; Lin Zhang; Zhuo Li; Hongqian Yu; Chunyan Chang; Yilong Zhang (Air Quality, Atmosphere & Health, 2024)

Ganoderic acid T, a Ganoderma triterpenoid, modulates the tumor microenvironment and enhances the chemotherapy and immunotherapy efficacy through downregulating galectin-1 levels - Suyu Chen; Kuangdee Chen; Yihsiu Lin; Ssuchia Wang; Huichuan Yu; Chaohsuan Chang; Tingchun Cheng; Chiaoyun Hsieh; Jiayi Li; Hsiaohsuan Lai; Denghai Chen; Chengpo Huang (Toxicology and Applied Pharmacology, 2024)

Response of N, P, and metal ions in deep soil layers to long-term cultivation of rubber and rubber-based agroforestry systems - Chang-An Liu; Yu Nie; Jia-Lin Zhang; Jian-Wei Tang; Xin Rao; Kadambot H.M. Siddique (Science of The Total Environment, 2024)

Petrogenesis of the pyroxenitic Moho transition zone in the Zedong ophiolite, Southeastern Tibet - Zhen-Yu Zhang; Chuan-Zhou Liu; Yan Liang; Liang-Liang Zhang; Chang Zhang; Tong Liu; Bo-Da Liu; Wei-Qi Zhang; Yin-Zheng Lin; Wen-Bin Ji (Lithos, 2024)

Molecular characterization of histone gene in golden pompano (Trachinotus ovatus) and antimicrobial activity of its derived peptides - Yu Liang; Jin-Min Pan; Ke-Cheng Zhu; Lin Xian; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Teng-Fei Zhu; Dian-Chang Zhang (Fish & Shellfish Immunology, 2024)

Examining the impact of polyfluoroalkyl substance exposure on erythrocyte profiles and its related nutrients: Insights from a prospective study on young Taiwanese - Chien-Yu Lin; Hui-Ling Lee; Chikang Wang; Fung-Chang Sung; Ta-Chen Su (Environmental Pollution, 2024)

Dual-Salt aqueous electrolyte for enhancing Charge-Storage properties of VO2 polymorphic cathodes for Zn-Ion batteries - Jing-Hong Huang; Xu-Feng Luo; Tzu-Yu Kuo; Yu-Hua Lai; Purna Chandra Rath; Chun-Wei Huang; Ming-Hsien Lin; An-Yuan Hou; Ju Li; Yu-Sheng Su; Wen-Wei Wu; Jeng-Kuei Chang (Chemical Engineering Journal, 2024)

Long non-coding RNA FKSG29 regulates oxidative stress and endothelial dysfunction in obstructive sleep apnea - Yung-Che Chen; Po-Yuan Hsu; Mao-Chang Su; Yung-Lung Chen; Ya‐Ting Chang; Chien-Hung Chin; I.-Chun Lin; Yu-Mu Chen; Ting-Ya Wang; Yong-Yong Lin; Chiu-Ping Lee; Meng-Chih Lin; et al. (Molecular and Cellular Biochemistry, 2024)

Measuring Spatial Radiation Dose Distribution During Abdominal Computed Tomography Scanning with Optically Stimulated Luminescence Dosimeters - Wen-Chuan Chang; Tian-Yu Shih; Pei-Ren Fang; Cheng-Hsun Lin (Journal of Medical and Biological Engineering, 2024)
Purpose As the proportion of medical radiation exposure increases, the exposure dose has received increasing attention. When performing interventional radiological diagnosis, examiners are often exposed to radiation. Therefore, patients and medical personnel are exposed to higher amounts of radiation dose. Accordingly, we used optically stimulated luminescence dosimeters (OSLDs) to measure the ambient air kerma during abdominal CT scanning to observe the spatial distribution of the doses. Methods An abdominal CT scan under a voltage of 120 kVp was performed, and OSLDs were used for the measurement. The measurement range extended from the examination couch that serves as the center point to the walls and was divided into four areas. The OSLD measurements were undertaken at three different heights (i.e., 85, 140, and 150 cm from the floor) for spatial dose detection. The OSLDs were fixed up to lines at the three height levels. Each dosimetry point was 50 cm apart. In addition, the surface incident doses of the prosthesis's mammary gland, liver, and gonad were estimated. Results According to the spatial dose distribution at the three different heights, the maximum dose and minimum dose in front of the bore were 0.194 ± 0.008 and 0.006 ± 0.001 mGy, respectively; 2 m away from the bore, the dose reduced to 9% of the maximum dose. The surface incident doses of the mammary gland, liver, and gonad were 1.321 ± 0.121, 13.083 ± 0.642, and 13.441 ± 0.658 mGy, respectively. Conclusion The spatial dose distribution revealed that the dose was the highest at the height of 140 cm and in front of the bore. The dose on the left side was higher than that on the right side. In addition, the dose was inversely proportional to the square of the distance. If the examiners must perform interventional radiological diagnosis during CT scanning, they should put on radiation protection equipment and stand behind the bore to minimize the radiation exposure.

Examining a decade-long trend in exposure to per- and polyfluoroalkyl substances and their correlation with lipid profiles: Insights from a prospective cohort study on the young Taiwanese population - Chien-Yu Lin; Sandy Huey-Jen Hsu; Hui-Ling Lee; Chikang Wang; Fung-Chang Sung; Ta-Chen Su (Chemosphere, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Unlocking synergies of drawdown operation: Multi-objective optimization of reservoir emergency storage capacity - Shufei Li; Di Zhu; Fanqi Lin; Jun Xia; Yanlai Zhou; Fi-John Chang; Chong-Yu Xu (Journal of Environmental Management, 2024)

Biofunctionalized hydrogel composed of genipin-crosslinked gelatin/hyaluronic acid incorporated with lyophilized platelet-rich fibrin for segmental bone defect repair - Er-Yuan Chuang; Yi-Cheng Lin; Yu-Min Huang; Chih-Hwa Chen; Yi-Yen Yeh; Lekha Rethi; Yu-Jen Chou; Pei-Ru Jheng; Jen-Ming Lai; Chang-Jung Chiang; Chin-Chean Wong (Carbohydrate Polymers, 2024)

Emergency room visits (ERVs) among occupational groups associated with ambient conditions in Taiwan - Ayushi Sharma; Kang Yajing; Min-Chun Lin; Liwen Deng; Yu-Kai Lin; Lin-Han Chianghsieh; Fung-Chang Sung; Yu-Chun Wang (International Archives of Occupational and Environmental Health, 2024)

Streptococcus taoyuanensis sp. nov., a Novel Species Isolated from a Patient with Bacteremia - Chien-Yu Lee; Chin-Kan Chan; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Jia-rong Zhang; Hong-yu Chen; Li-Ting Wang (Current Microbiology, 2024)

Mild chemical recycling of carbon fiber-reinforced epoxy composites in aqueous buffers and development of hydrothermally recyclable vitrimer composites from recyclates - Cheng Hao; Baoming Zhao; Lin Shao; Yiding Cao; Mingen Fei; Wangcheng Liu; Tuan Liu; Yu-Chung Chang; Kevin L. Simmons; Jinwen Zhang (Resources, Conservation and Recycling, 2024)

Organic light-emitting diode therapy promotes longevity through the upregulation of SIRT1 in senescence-accelerated mouse prone 8 mice - Yue-Hua Deng; Chi-Sheng Chiou; Ching-Yu Tsai; Abhinay Kumar Singh; Edlin Anahi Pelaze Achtmann; Bou-Yue Peng; Tommy Yet-Min Lin; Hsin-Chung Cheng; Pao-Chang Chiang; Win-Ping Deng (Journal of Photochemistry and Photobiology B: Biology, 2024)

Photocatalytic reduction of carbon dioxide by BiTeX (X = Cl, Br, I) under visible-light irradiation - Yu-Yun Lin; Fu-Yu Liu; I-Chia Chen; Hwei-Yan Tsai; Jhen-Wei Huang; Jia-Hao Lin; Chiing-Chang Chen (Journal of Environmental Management, 2024)

The role of a novel secretory peptidoglycan recognition protein with antibacterial ability from the Chinese Oak Silkworm Antheraea pernyi in humoral immunity - Xutong Duan; Ting Fu; Chang Liu; Fuhui Wang; Chengbao Liu; Lin Zhao; JinZhu Yu; Xialu Wang; Rong Zhang (Insect Biochemistry and Molecular Biology, 2024)

Policies for reducing the greenhouse gas emissions generated by the road transportation sector in Taiwan - Ching-Chih Chang; Kuei-Chao Chang; Yu-Lien Lin (Energy Policy, 2024)

Enhancing open-circuit voltage and suppression of energy loss in ternary organic photovoltaics utilizing carbazole/bicarbazole-based guest donors - Chun-Yu Lin; Bing-Huang Jiang; Pei-Jui Weng; Yu Hsuan Lin; Yu-Wei Su; Hui-Shan Shih; Zhong-En Shi; Yan-Ru Lin; Jijitha Vailassery; Shih-Sheng Sun; Chih-Ping Chen; Yuan Jay Chang (Chemical Engineering Journal, 2024)

Accumulation and bio-oxidation of arsenite mediated by thermoacidophilic Cyanidiales: innate potential biomaterials toward arsenic remediation - Yen-Lin Cho; Yu-Min Tzou; Afifah Assakinah; Nhu Anh Thi Than; Hwan Su Yoon; Seung In Park; Chun-Chieh Wang; Yao-Chang Lee; Liang-Ching Hsu; Pei-Yu Huang; Shao-Lun Liu; Yu-Ting Liu (Bioresource Technology, 2024)

Unlocking the ocean's potential: enhancing carbon capture through innovative replacement of methane hydrate by CO2 - Ting-Ting Chang; Wonjung Choi; Yongwon Seo; Anisa Fitri Santosa; Jian-Jhih Lin; Po-Yu Chen; Yao-Chuan Tasi; Wu-Yang Sean (Modeling Earth Systems and Environment, 2024)

Predicting ischemic stroke patients’ prognosis changes using machine learning in a nationwide stroke registry - Ching-Heng Lin; Yi-An Chen; Jiann-Shing Jeng; Yu Sun; Cheng-Yu Wei; Po-Yen Yeh; Wei-Lun Chang; Yang C. Fann; Kai-Cheng Hsu; Jiunn-Tay Lee (Medical & Biological Engineering & Computing, 2024)
Accurately predicting the prognosis of ischemic stroke patients after discharge is crucial for physicians to plan for long-term health care. Although previous studies have demonstrated that machine learning (ML) shows reasonably accurate stroke outcome predictions with limited datasets, to identify specific clinical features associated with prognosis changes after stroke that could aid physicians and patients in devising improved recovery care plans have been challenging. This study aimed to overcome these gaps by utilizing a large national stroke registry database to assess various prediction models that estimate how patients’ prognosis changes over time with associated clinical factors. To properly evaluate the best predictive approaches currently available and avoid prejudice, this study employed three different prognosis prediction models including a statistical logistic regression model, commonly used clinical-based scores, and a latest high-performance ML-based XGBoost model. The study revealed that the XGBoost model outperformed other two traditional models, achieving an AUROC of 0.929 in predicting the prognosis changes of stroke patients followed for 3 months. In addition, the XGBoost model maintained remarkably high precision even when using only selected 20 most relevant clinical features compared to full clinical datasets used in the study. These selected features closely correlated with significant changes in clinical outcomes for stroke patients and showed to be effective for predicting prognosis changes after discharge, allowing physicians to make optimal decisions regarding their patients’ recovery. Graphical Abstract

CCL4 contributes to aging related angiogenic insufficiency through activating oxidative stress and endothelial inflammation - Ting-Ting Chang; Liang-Yu Lin; Ching Chen; Jaw-Wen Chen (Angiogenesis, 2024)
Aging is a natural process associated with chronic inflammation in the development of vascular dysfunction. We hypothesized that chemokine C-C motif ligands 4 (CCL4) might play a vital role in aging-related vascular dysfunction. Circulating CCL4 was up-regulated in elderly subjects and in aged animals. CCL4 inhibition reduced generation of reactive oxygen species (ROS), attenuated inflammation, and restored cell functions in endothelial progenitor cells from elderly subjects and in aged human aortic endothelial cells. CCL4 promoted cell aging, with impaired cell functioning, by activating ROS production and inflammation. CCL4 knockout mice and therapeutic administration of anti-CCL4 neutralizing antibodies exhibited vascular and dermal anti-aging effects, with improved wound healing, via the down-regulation of inflammatory proteins and the activation of angiogenic proteins. Altogether, our findings suggested that CCL4 may contribute to aging-related vascular dysfunction via activating oxidative stress and endothelial inflammation. CCL4 may be a potential therapeutic target for vascular protections during aging.

Influences on medical app adoption by patients: the unified theory of acceptance and use of technology model and the moderating effects of technology readiness - Yung-Zung Chang; Chen-Wei Yu; Cheng-Min Chao; Fang-Chen Lin (The Social Science Journal, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Feasibility studies in applying cork to pile-type two-layered seismic metamaterials - Tung-Yu Wu; Wei-Lin Teng; Hsiang-Hao Hsieh; Shiang-Jung Wang; Kuo-Chun Chang (Soil Dynamics and Earthquake Engineering, 2024)

Study on the swelling of macromolecular geological organic matter with hydrocarbons and heteroatomic compounds - Tian Liang; Xiao-Hui Lin; Yan-Rong Zou; Zhao-Wen Zhan; Shuang Yu; Chang-Chun Pan; Ping’an Peng (Organic Geochemistry, 2024)

The joint effect of long-term exposure to multiple air pollutants on non-accidental and cause-specific mortality: A longitudinal cohort study - Xianglin Wei; Kin Fai Ho; Tsung Yu; Changqing Lin; Ly-yun Chang; Dezhong Chen; Tony Tam; Bo Huang; Alexis K.H. Lau; Xiang Qian Lao (Journal of Hazardous Materials, 2024)

Development of validated sandwich ELISA for detecting peanut allergen Ara h 3 in food - Jia-Fong Lin; Kee-Lung Chang; Bau-Shan Hsieh; Yu-Chen Hu; Edward S. Huang; Hsu-Sheng Yu (Food Chemistry, 2024)

Urine cadmium and urolithiasis: A systematic review and meta-analysis - Yuan-Hsin Chen; Chih-Fu Wei; Ya-Yun Cheng; Carol Mita; Chinh Lu Duc Hoang; Cheng-Kuan Lin; Yu-Tzu Chang; David C. Christiani (Environmental Research, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Spatiotemporal characterization of PM2.5, O3, and trace gases associated with East Asian continental outflows via drone sounding - Chih-Yuan Chang; Jia-Lin Wang; Yen-Chen Chen; Wei-Nai Chen; Sheng-Hsiang Wang; Ming-Tung Chuang; Neng-Huei Lin; Charles C.-K. Chou; Wei-Syun Huang; Li-Jin Ke; Xiang-Xu Pan; Yu-Jui Ho; et al. (Science of The Total Environment, 2024)

Climate-regulation of organic carbon export in erosive mountain settings: A case study from Taiwan since the last glacial maximum - Li-Wei Zheng; Robert G. Hilton; Yuan-Pin Chang; Rick J. Yang; Xiaodong Ding; Xufeng Zheng; Tsung-Yu Lee; Hsi-Jih Lu; Jung-Tai Lu; Yu-Shih Lin; James T. Liu; Shuh-Ji Kao (Quaternary Science Reviews, 2024)

Postvaccination serosurveillance of foot-and-mouth disease through virus-neutralizing and nonstructural protein antibody tests on pig farms in Taiwan: 2009–2020 - Ming-Chang Lee; Yu-Fen Sun; Ming-Chung Deng; Nien-Nung Lin; Jung-Pin Hsu; Chwei-Jang Chiou; Wen-Jane Tu; Shih-Ping Chen (Preventive Veterinary Medicine, 2024)

Efficiencies of filtration sampling and extraction for recovery of viable Staphylococcus aureus bioaerosols - Ching-Wen Chang; Yen-Ni Lin; Sheng-Hsiu Huang; Yu-Ju Horng (Journal of Aerosol Science, 2024)

The effects of repeated freezing and thawing on bovine sperm morphometry and function - Chang-Guo Min; Xin Ma; Yu-Chan Wang; Cheng-Kun Zhong; Chong-shan Yuan; Kai-Yan Zhang; Cheng-Lin Zhan; Sheng-Kui Hou; Xin-Hai Wang; Jun Wang; Jing Zhao; Yi Fang; et al. (Cryobiology, 2024)

CuO NWs boosted triboelectric microfluidic nanosensor functionalized by collagen-protein interactions for real-time platelet count monitoring - Jia-Cheng Lin; Kuldeep Kaswan; Subhodeep Chatterjee; Yu-Wen Wu; Manish Kumar Sharma; Ashok Ranjan; Snigdha Roy Barman; Yu-Zih Lin; Thierry Burnouf; Wilfrid Boireau; Ming-Yen Lu; Yong-Kwang Tu; et al. (Chemical Engineering Journal, 2024)

Unleashing the potential of waste: A supercharged high-performance 3D printing resin from discarded polylactic acid - Yu-Chung Chang; Lin Shao; Wangcheng Liu; Brian J. Bliss; Baoming Zhao; Zihui Zhao; Jinwen Zhang (Chemical Engineering Journal, 2024)

A compound enzyme as an additive to a continuous anaerobic dynamic membrane bioreactor for enhanced lignocellulose removal from codigestion: Performance, membrane characteristics and microorganisms - Bao-Shan Xing; Xiang-Lin Chang; Yi Zhang; Sifan Cao; Xi-Fang Tang; Yong-Chen Han; Yu-You Li; Xiaochang C. Wang; Rong Chen (Bioresource Technology, 2024)

Losing Tidal Flats at the Midpoint of the East Asian-Australasian Flyway over the past 100 Years - Wan-Jyun Chen; An-Yu Chang; Chia-Chi Lin; Ruey-Shing Lin; Da-Li Lin; Pei-Fen Lee (Wetlands, 2024)
The ecosystem services and functions of tidal flats have been overlooked for many decades, and tidal flat loss has been identified as a serious threat to many taxa in recent years, especially for migratory waterbirds. Despite the understanding of tidal flats change on the global scale, there are still a lot of unknowns on the small scale, including tidal flats in Taiwan, which are important stopover sites for migratory waterbirds along the East Asian–Australasian Flyway. Therefore, we collated historic topographic maps, Landsat Archive images between the 1920s and the 2020s to determine the trajectories of tidal flat change along the coastline of Taiwan. Our results show that tidal flat coverage expanded between the 1920s and the 1950s, but lost approximately 266 km 2 (58%) between the 1950s and the 2010s. The status of the tidal flats along the western coastline of Taiwan has been identified as “Endangered” based on the criteria of the IUCN Red List of Ecosystems. According to the aims of the Global Biodiversity Framework, we suggest rethinking the land use plans along the coastline to mitigate the tidal flat loss, especially the controversial issues concerning the expansion of green energy infrastructure. To realize the Nature Positive goals by 2030, recovering and restoring the tidal flat ecosystem could be one of the key strategies.

An ensemble-based data assimilation system for forecasting variability of the Northwestern Pacific ocean - Yasumasa Miyazawa; Max Yaremchuk; Sergey M. Varlamov; Toru Miyama; Yu-Lin K. Chang; Hakase Hayashida (Ocean Dynamics, 2024)
An adjoint-free four-dimensional variational (a4dVar) data assimilation (DA) is implemented in an operational ocean forecast system based on an eddy-resolving ocean general circulation model for the Northwestern Pacific. Validation of the system against independent observations demonstrates that fitting the model to time-dependent satellite altimetry during a 10-day DA window leads to substantial skill improvements in the succeeding 60-day hindcast. The a4dVar corrects representation of the Kuroshio path variation south of Japan by adjusting the dynamical balance between amplitude/wavelength of the meander and flow advection. A larger ensemble spread tends to reduce the skill in representing the observed sea surface height anomaly, suggesting that it is possible to use the ensemble information for quantifying the forecast error. The ensemble information is also utilized for modification of the background error covariance (BEC), which improves the accuracy of temperature and salinity distributions. The modified BEC yields the skill decline of the Kuroshio path variation during the 60-day hindcast period, and the ensemble sensitivity analysis shows that changes in the dynamical balance caused by the ensemble BEC result in such skill deterioration.

Investigating the effects of urban morphology on vitality of community life circles using machine learning and geospatial approaches - Sanwei He; Zhen Zhang; Shan Yu; Chang Xia; Chih-Lin Tung (Applied Geography, 2024)

Critical roles of tubular mitochondrial ATP synthase dysfunction in maleic acid-induced acute kidney injury - Hugo Y.-H. Lin; Chan-Jung Liang; Ming-Yu Yang; Phang-Lang Chen; Tzu-Ming Wang; Yen-Hua Chen; Yao-Hsiang Shih; Wangta Liu; Chien-Chih Chiu; Chih-Kang Chiang; Chang-Shen Lin; Han-Chen Lin (Apoptosis, 2024)
Maleic acid (MA) induces renal tubular cell dysfunction directed to acute kidney injury (AKI). AKI is an increasing global health burden due to its association with mortality and morbidity. However, targeted therapy for AKI is lacking. Previously, we determined mitochondrial-associated proteins are MA-induced AKI affinity proteins. We hypothesized that mitochondrial dysfunction in tubular epithelial cells plays a critical role in AKI. In vivo and in vitro systems have been used to test this hypothesis. For the in vivo model, C57BL/6 mice were intraperitoneally injected with 400 mg/kg body weight MA. For the in vitro model, HK-2 human proximal tubular epithelial cells were treated with 2 mM or 5 mM MA for 24 h. AKI can be induced by administration of MA. In the mice injected with MA, the levels of blood urea nitrogen (BUN) and creatinine in the sera were significantly increased ( p p p p p p

Corrigendum to “An end-to-end approach to predict physical properties of heterogeneous porous media: Coupling deep learning and physics-based features” [Fuel 352 (2023) 128753] - Yuqi Wu; Senyou An; Pejman Tahmasebi; Keyu Liu; Chengyan Lin; Serveh Kamrava; Chang Liu; Chenyang Yu; Tao Zhang; Shuyu Sun; Samuel Krevor; Vahid Niasar (Fuel, 2024)

Landfill leachate treatment by direct contact membrane distillation: Impacts of landfill age on contaminant removal performance, membrane fouling and scaling - Zhimeng Yang; Songze Lin; Linxiong Ye; Dan Qu; Haiyang Yang; Haiqing Chang; Huarong Yu; Zhongsen Yan; Hongwei Rong; Fangshu Qu (Desalination, 2024)

3D-printed Al2O3 framework supported carbon-bridged tri-s-triazine of g-C3N4 for photocatalytic tetracycline oxidation - Chechia Hu; Lee-Lee Chang; Wei Chen; Wan-Yuan Hsu; Szu-Chia Chien; Chien-Hua Chen; Yu-Ting Lin; Tzu-Jung Hsu; Kuo-Lun Tung (Chemical Engineering Journal, 2024)

Extinction coefficient of dry and deliquescent chemical components of PM_(2.) 5 in urban areas and their impacts on visibility deterioration - Chien-Hao Lin; Shao-En Sun; Chung-Te Lee; Ting-Yu Chiang; Shih-Yu Chang; Tzu-Shuan Wu; Hsin-Yu Wei; Ling-Ya Chen; Hao-Wei Liu; Sally C.W. Tai (Atmospheric Pollution Research, 2024)

Roles of Neuronal Protein Kinase Cε on Endoplasmic Reticulum Stress and Autophagic Formation in Diabetic Neuropathy - Yu-Yu Kan; Ying-Shuang Chang; Wen-Chieh Liao; Tzu-Ning Chao; Yu-Lin Hsieh (Molecular Neurobiology, 2024)
In chronic diabetic neuropathy (DN), the cellular mechanisms of neuropathic pain remain unclear. Protein kinase C epsilon (PKCε) is an intracellular signaling molecule that mediates chronic pain. This paper addresses the long-term upregulated PKCε in DN associated with endoplasmic reticulum (ER) stress and autophagic formation and correlates to chronic neuropathic pain. We found that thermal hyperalgesia and mechanical allodynia course development were associated with PKCε upregulation after DN but not skin denervation. Pathologically, PKCε upregulation was associated with the expression of inositol-requiring enzyme 1α (IRE1α; ER stress–related molecule) and ubiquitin D (UBD), which are involved in the ubiquitin-proteasome system (UPS)-mediated degradation of misfolded proteins under ER stress. Manders coefficient analyses revealed an approximately 50% colocalized ratio for IRE1α(+):PKCε(+) neurons (0.34–0.48 for M1 and 0.40–0.58 for M2 Manders coefficients). The colocalized coefficients of UBD/PKCε increased (M1: 0.33 ± 0.03 vs. 0.77 ± 0.04, p < 0.001; M2: 0.29 ± 0.05 vs. 0.78 ± 0.04; p < 0.001) in the acute DN stage. In addition, the regulatory subunit p85 of phosphoinositide 3-kinase, which is involved in regulating insulin signaling, exhibited similar expression patterns to those of IRE1α and UBD; for example, it had highly colocalized ratios to PKCε. The ultrastructural examination further confirmed that autophagic formation was associated with PKCε upregulation. Furthermore, PKCεv1-2, a PKCε specific inhibitor, reverses neuropathic pain, ER stress, and autophagic formation in DN. This finding suggests PKCε plays an upstream molecule in DN-associated neuropathic pain and neuropathology and could provide a potential therapeutic target.

Nucleocytoplasmic shuttling of BEFV M protein-modulated by lamin A/C and chromosome maintenance region 1 through a transcription-, carrier- and energy-dependent pathway - Yu-Kang Chang; Yi-Jyum Lin; Ching-Yuan Cheng; Pei-Chien Tsai; Chi-Young Wang; Brent L. Nielsen; Hung-Jen Liu (Veterinary Microbiology, 2024)

Potassium diformate alleviated inflammation of IPEC-J2 cells infected with EHEC - Ying Lin; Jun-Lei Zhai; Ya-Ting Wang; Ping-Ting Guo; Jing Zhang; Chang-Kang Wang; Ling Jin; Yu-Yun Gao (Veterinary Microbiology, 2024)

The SMAC mimetic GDC-0152 is a direct ABCB1-ATPase activity modulator and BIRC5 expression suppressor in cancer cells - I-Li Lin; Yu-Ting Lin; Yung-Chieh Chang; Sree Karani Kondapuram; Kai-Hsuan Lin; Pin-Chen Chen; Chung-Ying Kuo; Mohane Selvaraj Coumar; Chun Hei Antonio Cheung (Toxicology and Applied Pharmacology, 2024)

Improving time-series InSAR deformation estimation for city clusters by deep learning-based atmospheric delay correction - Peifeng Ma; Chang Yu; Zeyu Jiao; Yi Zheng; Zherong Wu; Wenfei Mao; Hui Lin (Remote Sensing of Environment, 2024)

Di-n-butyl phthalate promotes the neural differentiation of mouse embryonic stem cells through neurogenic differentiation 1 - Ying-Chu Lin; Kenly Wuputra; Kohsuke Kato; Chia-Chen Ku; Shigeo Saito; Michiya Noguchi; Yukio Nakamura; Michael Hsiao; Chang-Shen Lin; Deng-Chyang Wu; Atsushi Kawaguchi; Hsin-Su Yu; et al. (Environmental Pollution, 2024)

Oxidative stress and potential effects of metal nanoparticles: A review of biocompatibility and toxicity concerns - Yung-Li Wang; Yu-Hsuan Lee; Chu-Lin Chou; Yu-Sheng Chang; Wen-Chih Liu; Hui-Wen Chiu (Environmental Pollution, 2024)

Enhanced catalytic activity of H2 heat-treated porous ceria for direct conversion of carbon dioxide into dimethyl carbonate - Zhuxian Yang; Monica Mengdie Lin; Xinhuan Lu; Justin Tay Zheng; Wen-Yueh Yu; Yanqiu Zhu; Hong Chang; Yongde Xia (Chemical Engineering Journal, 2024)

Streptococcus taonis sp. nov., a novel bacterial species isolated from a blood culture of a patient - Chien-Yu Lee; Chin-Kan Chan; Momoko Chida; Mika Miyashita; Yun-Shien Lee; Hui-Chung Wu; Yu-Chung Chang; Wen-Ting Lin; Yi-Sheng Chen (Archives of Microbiology, 2024)

A hybrid system for Nickel ions removal from synthesized wastewater using adsorption assisted with electrocoagulation - Jean Claude Nizeyimana; Pamphile Ndagijimana; Junaid Khan; Liu Xiangru; Gratien Twagirayezu; Habasi Patrick Manzi; Olivier Irumva; Chang-Ping Yu; Anyi Hu; Shanshan Lin (Environmental Science and Pollution Research, 2024)

Lack of effects of eight-week left dorsolateral prefrontal theta burst stimulation on white matter macro/microstructure and connection in autism - Chun-Hung Yeh; Po-Chun Lin; Rung-Yu Tseng; Yi-Ping Chao; Chen-Te Wu; Tai-Li Chou; Rou-Shayn Chen; Susan Shur-Fen Gau; Hsing-Chang Ni; Hsiang-Yuan Lin (Brain Imaging and Behavior, 2024)

Impact of occupational noise exposure on the hearing level in hospital staffs: a longitudinal study - Tang-Chuan Wang; You-Cheng Yu; Alan Hsu; Jia-Yi Lin; Yung-An Tsou; Chiu-Shong Liu; Kai-Jen Chuang; Wen-Chi Pan; Chin-An Yang; Sung-Lin Hu; Chien-Yi Ho; Tzu-Liang Chen; et al. (Environmental Science and Pollution Research, 2024)

Ecological and human health hazards of soil heavy metals after wildfire: A case study of Liangshan Yi autonomous prefecture, China - Lin Rao; Chao Zheng; Jian-Bin Chen; Jun-Zhuo Cai; Zhan-Biao Yang; Xiao-Xun Xu; Guo-Chun Lv; Chang-Lian Xu; Gui-Yin Wang; Yu-Bon Man; Ming-Hung Wong; Zhang Cheng (Chemosphere, 2024)

Migration of phosphorus in pig manure during pyrolysis process and slow-release mechanism of biochar in hydroponic application - Ru-Qing Jiang; Guang-Wei Yu; Lin-Hui Yu; Yu Wang; Chang-Jiang Li; Zhen-Jiao Xing; Xi-Mei Xue; Yin Wang; Cheng Yu (Science of The Total Environment, 2024)

Does saponin in quinoa really embody the source of its bitterness? - Lin Meng Song; Yuan Yu; Li Dong Du; Xue Ying Ji; Hui Gao; Yu Qing Cai; Chang Jian Li; Peng Xue (Food Chemistry, 2024)

Leaching and evolution of anthocyanins and aroma compounds during Cabernet Sauvignon wine fermentation with whole-process skin-seed contact - Xue-Chen Yao; Hua-Lin Zhang; Xin-Rui Ma; Nong-Yu Xia; Chang-Qing Duan; Wei-Ming Yang; Qiu-Hong Pan (Food Chemistry, 2024)

Analyzing the correlation between quinolone-resistant Escherichia coli resistance rates and climate factors: A comprehensive analysis across 31 Chinese provinces - Yi-Chang Zhao; Zhi-Hua Sun; Ming-Xuan Xiao; Jia-Kai Li; Huai-yuan Liu; Hua-Lin Cai; Wei Cao; Yu Feng; Bi-Kui Zhang; Miao Yan (Environmental Research, 2024)

Experimental verification of seismic vibration control of high-rise buildings with friction-type multiple tuned mass dampers - Ging-Long Lin; Chi-Chang Lin; Tsung-Han Yang; Hao-Yu Lung (Engineering Structures, 2024)

Electropolymerization stabilized bipolar metal coordination complex for high-performance dual-ion batteries - Chen-xing Zhang; Xian-he Chen; Wei-sheng Zhang; Yue Wang; Shi-lin Mei; Yu-Wu Zhong; Chang-Jiang Yao (Chemical Engineering Journal, 2024)

TALE-based organellar genome editing and gene expression in plants - Jer-Young Lin; Yu-Chang Liu; Yan-Hao Tseng; Ming-Tsair Chan; Ching-Chun Chang (Plant Cell Reports, 2024)

The two-back task leads to activity in the left dorsolateral prefrontal cortex in schizophrenia patients with predominant negative symptoms: a fNIRS study and its implication for tDCS - Chin-Chao Ma; Yen-Yue Lin; Yong-An Chung; Sonya Youngju Park; Cathy Chia-Yu Huang; Wei-Chou Chang; Hsin-An Chang (Experimental Brain Research, 2024)

Effects of gas to water ratio and nano-Cu dosage on CH4 hydrate growth: A combined molecular simulation and experimental study - Chenxing Huang; Riyi Lin; Chang Lu; Xichong Yu; Zhengda Yang; Chengzhi Wu; Jinyu Li; Yiya Wang (Fuel, 2024)

GW4064 inhibits migration and invasion through cathepsin B and MMP2 downregulation in human bladder cancer - Chien-Chang Kao; Chien-Rui Lai; Yi-Hsuan Lin; Tzu-Min Chen; Yu-Ling Tsai; Wen-Chiuan Tsai; Tze-Yun Ong; Hisao-Hsien Wang; Sheng-Tang Wu; Ying Chen (Chemico-Biological Interactions, 2024)

Breaking prolonged sitting increases 24-h physical activity and self-perceived energy levels but does not acutely affect cognition in healthy adults - Feng-Chih Kuo; Yun-Ting Lin; Ting-Yu Chueh; Yu-Kai Chang; Tsung-Min Hung; Yung-Chih Chen (European Journal of Applied Physiology, 2024)

Effect of stress on the rehabilitation performance of rats with repetitive mild fluid percussion-induced traumatic brain injuries - Yu-Lin Wang; Chi-Chun Chen; Ching-Ping Chang (Cognitive Neurodynamics, 2024)

A numerical investigation of an indoor dry storage facility on heat transfer - Chia-Wei Lin; Yung-Shin Tseng; Kai-Qi Lin; Yu-Hsuan Chang; Tzu-Chen Hung; Hua-Yi Hsu (Annals of Nuclear Energy, 2024)

Linkage analysis for water-energy-economic system efficiency in China - Zhong Fang; Yung-ho Chiu; Yiqin Chen; Tai-Yu Lin; Tzu-Han Chang (Environment, Development and Sustainability, 2024)

Expression of polyphenol oxidase of Litopenaeus vannamei and its characterization - Qian Hong; Yu-Lei Chen; Duanquan Lin; Ru-Qing Yang; Kai-Yuan Cao; Ling-Jing Zhang; Yi-Ming Liu; Le-Chang Sun; Min-Jie Cao (Food Chemistry, 2024)

Preliminary assessments of population exposure to glycidyl esters and 3-monochloropropane-1,2-diol esters from miscellaneous oil-containing packaged foods in Taiwan - Yu-Hsuan Chang; Kai-Wei Liao; Zih-Ee Lin; Wei-Ju Lee (Food Chemistry, 2024)

Electro-forward osmosis through a titanium-dioxide-modified membrane to enhance aquaculture wastewater recovery - Yi-Li Lin; Nai-Yun Zheng; Yu-Sheng Chen; Chao-Chin Chang (Desalination, 2024)

Exposure to phenols reduces melanogenesis in B16F10 cells and zebrafish - Chung-Yu Lin; Chang-Yi Wu; Chia C. Wang; Che-Hsin Lee (Aquatic Toxicology, 2024)

Association between obstructive sleep apnea and low bone mass in adults: a systematic review and meta-analysis - Xin-Yuan Wang; Xin-Yu Wang; Zhi-Xin Liao; Yue-An Zhao; Chang Wei; Lin-Jing Gong (Sleep and Biological Rhythms, 2024)

The Bioeconomic Analysis of Hybrid Giant Grouper (Epinephelus fuscoguttatus × Epinephelus lanceolatus) and Green Grouper (Epinephelus malabaricus): A Case Study in Taiwan - Po-Lin Huang; Farok Afero; Yao Chang; Bo-Ying Chen; Hsun-Yu Lan; Yen-Lung Hou; Cheng-Ting Huang (Fishes, 2023)
Grouper aquaculture is a rapidly growing and dynamic industry within the Taiwan aquaculture sector that serves as an important source of income generation. Farming fishes at a better location (FFABL) is a promising production strategy. This study evaluated the production and economic performance of grouper farming in Taiwan. This investigation employed two steps: (1) a cost–benefit analysis to determine the main component affecting profitability; and (2) multivariate statistics to clarify the relationship between biological and economic factors. The findings suggest that the best choice of species is hybrid giant grouper that generates and highlights a positive income, viable benefit–cost ratio and profit rate. The study found the feed management of hybrid giant groupers requires more consideration due to its low feed conversion ratio. The producers need to replace trash fish in commercial feed during the production cycle to ensure better feed management. Finally, this paper argues that feed is the main constraint for grouper farming, which is sensitive to any change in feed productivity, and this constraint must be solved to sustain the grouper industry in Taiwan.

Scenarios of temporal environmental alterations and phytoplankton diversity in a changing bay in the East China Sea - Yu Wang; Weibo Wang; Yaqin Huang; Lin Chang; Xiaoming Tang; Xuebao He; Hui Lin (Frontiers in Marine Science, 2023)
In the context of global change, the stressors of warming and eutrophication have significant ecological implications in coastal waters. In order to examine the diversity of phytoplankton and its relationship with water quality, we conducted a survey of phytoplankton community compositions and their correlation with environmental changes over four seasons in a eutrophic bay located in the East China Sea. Through a systematic analysis, we identified diatoms and dinoflagellates as the primary dominant groups, with the species Skeletonema costatum , Skeletonema marinoi , Biddulphia sinensis , Thalassiosira eccentrica , Leptocylindrus danicus , Coscinodiscus oculus-iridis , Coscinodiscus jonesianus , and Chaetoceros knipowitschi as the most abundant species in all seasons. Significant seasonal alterations were observed in both environmental settings and phytoplankton species richness, dominance, and abundance. The phytoplankton community varied in its response to diverse aquatic environments and was principally affected by temperature, silicic acid concentrations, and suspended solids. Elevated temperatures were found to promote an increase in phytoplankton abundance. However, no clear evidence of diatom and dinoflagellate succession in relation to N:P ratio was observed across seasons. Water quality analysis illustrated that the majority of the study area exhibited a mid-eutrophic with severe organic pollution. The abundance of phytoplankton was significantly influenced by eutrophication and organic pollution. The accelerated warming process related to coastal nuclear power plants and nutrient regime alterations significantly affect the temporal shift of the phytoplankton community. These findings contribute valuable insights into the effects of eutrophic environments on the structure of phytoplankton communities in coastal aquatic systems.

Spatial variability of nitrogen cycling in the sediments of the Danshuie River Estuary (Northern Taiwan) - Ting Chia Chang; Wei Yu Lin; Tien Hsi Fang (Marine Pollution Bulletin, 2023)

Inhibition of continuous cropping obstacle of celery by chemically modified biochar: An efficient approach to decrease bioavailability of phenolic allelochemicals - Chia-Chia Lin; Yu-Ting Liu; Po-Hsiang Chang; Yi-Cheng Hsieh; Yu-Min Tzou (Journal of Environmental Management, 2023)

Active packaging incorporating chitosan, casein phosphopeptide, and plasmonic modification to maintain quality and regulate the respiration rate of fresh-cut Pyrus serotina Rehder during storage - Chao-Kai Chang; Fang-Yu Lin; Sheng-Yen Tsai; Mohsen Gavahian; Kuan-Chen Cheng; Chih-Yao Hou; Min-Hung Chen; Shella Permatasari Santoso; Chang-Wei Hsieh (Food Packaging and Shelf Life, 2023)

Screening of small molecule compounds targeting hnRNPA2 protein - Yuan-Rong Zheng; Chao-Jie Wang; Ling Yang; Yu-Jun Zhang; Mei-Juan Fang; He Chang; Kai-Qiang Guo; Song-Lin Shi (Medicinal Chemistry Research, 2023)

Associations between paraben exposure, thyroid capacity, homeostasis and pituitary thyrotropic function in the general Taiwanese: Taiwan Environmental Survey for Toxicants (TEST) 2013 - Po-Chin Huang; Hsin-Chang Chen; Shih-Hao Leung; Yu-Jung Lin; Han-Bin Huang; Wan-Ting Chang; Hsin-I. Huang; Jung-Wei Chang (Environmental Science and Pollution Research, 2023)

Pyroxenite–harzburgite sequences in the Dazhuqu ophiolite (Southern Tibet) formed through hydrous melt infiltration and melt–peridotite reaction - Zhen-Yu Zhang; Chuan-Zhou Liu; Yan Liang; Tong Liu; Chang Zhang; Bo-Da Liu; Yin-Zheng Lin; Wei-Qi Zhang; Wen-Bin Ji (Contributions to Mineralogy and Petrology, 2023)

Miticidal activity of Photorhabdus luminescens for controlling two spider mites, Tetranychus urticae and Tetranychus kanzawai, in Carica papaya - Tzay-Tien Hsieh; Ju-Chun Chang; Chienyan Hsieh; Jui-Tang Tseng; Show-Jow Lin; Cheng-Ju Yang; Feng-Chia Hsieh; Yu-Shin Nai (BioControl, 2023)

Improved functionality and safety of peptides by the formation of peptide-polyphenol complexes - Duanquan Lin; Le-Chang Sun; Wei-Sen Huo; Ling-Jing Zhang; Yu-Lei Chen; Song Miao; Min-Jie Cao (Trends in Food Science & Technology, 2023)

Overcoming the fluorescent interference during Raman spectroscopy detection of microplastics - Yu Liu; Jiale Hu; Liqian Lin; Bing Yang; Minhua Huang; Min Chang; Xiaoxin Huang; Zhenqing Dai; Shengli Sun; Lei Ren; Chengyong Li (Science of The Total Environment, 2023)

Stereochemical insights into structurally diverse lignanamides from the herbs of Solanum lyratum Thunb. - Ye Chang; Ming Bai; Xin Zhang; Jiao-Yang Hou; Cheng-Yu Chu; Jia-Qi Niu; Guo-Dong Yao; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Scene-aware refinement network for unsupervised monocular depth estimation in ultra-low altitude oblique photography of UAV - Kailong Yu; Hao Li; Linjie Xing; Tao Wen; Die Fu; Yang Yang; Chengjiang Zhou; Rong Chang; Shan Zhao; Lin Xing; Haicheng Bai (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

An end-to-end approach to predict physical properties of heterogeneous porous media: Coupling deep learning and physics-based features - Yuqi Wu; Senyou An; Pejman Tahmasebi; Keyu Liu; Chengyan Lin; Serveh Kamrava; Chang Liu; Chenyang Yu; Tao Zhang; Shuyu Sun; Samuel Krevor; Vahid Niasar (Fuel, 2023)

Analysis and classification of coffee beans using single coffee bean mass spectrometry with machine learning strategy - Jia-Jen Tsai; Che-Chia Chang; De-Yi Huang; Te-Sheng Lin; Yu-Chie Chen (Food Chemistry, 2023)

Nanoscale photocatalytic hydrogen production system mitigates inflammation by harnessing glycolysis waste - Cheng-Yu Wu; Cam-Hoa Mac; Tung-Han Yang; Khanh Nguyen; Shih-Kai Lo; Yen Chang; Po-Liang Lai; Hsing-Wen Sung; Yu-Jung Lin (Chemical Engineering Journal, 2023)

Oxygen doped graphite carbon nitride as efficient metal-free catalyst for peroxymonosulfate activation: Performance, mechanism and theoretical calculation - Shaofeng Xiang; Yu Lin; Tongda Chang; Bingrui Mei; Yuhang Liang; Ziqian Wang; Wenwu Sun; Chun Cai (Chemosphere, 2023)

Using drone soundings to study the impacts and compositions of plumes from a gigantic coal-fired power plant - Yen-Chen Chen; Jia-Lin Wang; Chih-Yuan Chang; Ming-Tung Chuang; Charles C.-K. Chou; Xiang-Xu Pan; Yu-Jui Ho; Chang-Feng Ou-Yang; Wen-Tzu Liu; Chih-Chung Chang (Science of The Total Environment, 2023)

Assessing the suitability of municipal sewage sludge and coconut bran as breeding medium for Oryza sativa L. seedlings and developing a standardized substrate - Linyi Lin; Jiemin Qin; Yu Zhang; Jiaxin Yin; Genmao Guo; Muhammad Amjad Khan; Yin Liu; Quan Liu; Qingqing Wang; Kenlin Chang; Ondřej Mašek; Junfeng Wang; et al. (Journal of Environmental Management, 2023)

Promotion of the catalytic polymerization of hydroquinone towards humic-like substances by graphitic carbon nitride - M.M.M. Ahmed; Yu-Ting Liu; S. Venkatesan; Min Chien Wu; Howida M. Nail; Der-Lii M. Tzou; Ming-Chang Lin; Kai-Yue Chen; Yu-min Tzou (Journal of Environmental Chemical Engineering, 2023)

Valorization of heavy metal-adsorbed microalgae from a membrane bioreactor for levulinic acid production - Chung-Yu Guan; Yen-Lin Kao; Van Toi Pham; Pei-Hsun Wu; Chang-Ping Yu (Journal of Environmental Chemical Engineering, 2023)

The biocompatibility and hemostatic efficacy of silk fibroin nanofibrils fabricated by Shear-Induced phase separation process - Po-Wen Lu; Yu-Tzu Wu; Liang-Yu Chang; Tzu-Wei Lu; Chonlachat Jaihao; Ching-Shuan Huang; Mo-Fei Murphy Chuang; Chunche Lin; Innie Chen; Agnese Brangule; Aleksej Zarkov; Aivaras Kareiva; et al. (Chemical Engineering Journal, 2023)

Spatial-temporal evaluation of PM2.5 concentration for health risk reduction strategy development in a basin with different weather patterns - Ho-Wen Chen; Chien-Yuan Chen; Teng-Wei Chang; Guan-Yu Lin (Atmospheric Pollution Research, 2023)

Severity of Liver Cirrhosis Evaluated by Digital Subtraction Angiography Using Quantitative Color-Coding Analysis Before Transarterial Embolization - Lung-Hui Giiang; Chang-Hsien Liu; Chih-Yung Yu; Te-Pao Lin; Hsiang-Cheng Chen; Chun-Jung Juan; Yu-Ching Chou (Journal of Medical and Biological Engineering, 2023)

Profit-seeking enterprise production and business waste treatment efficiency in Taiwan - Tai-Yu Lin; Yung-Ho Chiu; Yi-Nuo Lin; Tzu-Han Chang (Environment, Development and Sustainability, 2023)

Research on stability and control strategies for a spring-loaded valve with bypass outlet - Jie Jian; Zhi-Jun Shuai; Jia-Xuan He; Chang-Lin Meng; Tao Yu; Xi Wang; Wan-You Li; Shi-Wei Ni; Chen-Xing Jiang (Annals of Nuclear Energy, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Application of water-saving irrigation and biostimulants on the agronomic performance of maize (Zea mays) - Cheng-Hsuan Chen; Kuan-Hung Lin; Yu-Sen Chang; Yu-Jie Chang (Process Safety and Environmental Protection, 2023)

From arc accretion to within-plate extension: Geochronology and geochemistry of the Neoproterozoic magmatism on the northern margin of the Yangtze Block - Yu Huang; Xiao-Lei Wang; Jun-Yong Li; Ru-Cao Li; De-Hong Du; Chang-Hong Jiang; Lin-Sen Li; Ning Ding (Precambrian Research, 2023)

Investigation of the fall armyworm (Spodoptera frugiperda) gut microbiome and entomopathogenic fungus-induced pathobiome - Yao-Chia Liu; Tzu-Han Chen; Yu-Feng Huang; Chang-Lin Chen; Yu-Shin Nai (Journal of Invertebrate Pathology, 2023)

Properties of Pacific white shrimp (Litopenaeus vannamei) collagen and its degradation by endogenous proteinases during cold storage - Xu-Chen Xiao; Duanquan Lin; Kai-Yuan Cao; Le-Chang Sun; Yu-Lei Chen; Ling Weng; Ling-Jing Zhang; Min-Jie Cao (Food Chemistry, 2023)

In-situ gas flow separation between biochar and the heat carrier in a circulating fluidized bed reactor for biomass pyrolysis - Zheng-hao Yang; Zhen He; Xiang-gang Zhang; Xia Jiang; Zi-heng Jin; Jian-ping Li; Liang Ma; Hua-lin Wang; Yu-long Chang (Chemical Engineering Journal, 2023)

Toward ultra-high efficiency tandem OLEDs: Benzothiazole-based bipolar hosts and specific device architectures - Jui-Ming Wang; Ting-Chun Lee; Chia-Chen Chung; Wun-Yu Chen; Sih-Yu Wu; Yan-Ding Lin; Yuan Jay Chang; Chin-Wei Lu; Chih-Hao Chang (Chemical Engineering Journal, 2023)

A strategy for regulation of gas–liquid microflow patterns by changing gas kinetic energy - Lin Sheng; Yu Chang; Junjie Wang; Jian Deng; Guangsheng Luo (Chemical Engineering Journal, 2023)

An anaerobic dynamic membrane bioreactor (AnDMBR) system enhanced the biogas conversion efficiency and stability of mesophilic codigestion with waste activated sludge and food waste - Bao-Shan Xing; Yi Zhang; Rui-Qi Zhang; Jing Ma; Xiang-Lin Chang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Chemical Engineering Journal, 2023)

β-Cyclodextrin network crosslinked by novel phosphonium-based tetrakiscarboxylic acid derived from PH3 tail gas: Synthesis and application for rapid removal of organic dyes from wastewater - Yu-Lin Hong; Jian Sun; Xiu-Qin Fang; Qing-Wen Liu; Chang Wang; Cheng-Mei Liu (Carbohydrate Polymers, 2023)

GPU parallelization of particulate matter concentration modeling in indoor environment with cellular automata framework - Hsiang-Lin Yu; Tsang-Jung Chang (Building and Environment, 2023)

Perceptions of Taiwanese owners and behaviour veterinarians on behavioural problems in dogs and preferred training approaches - Hao-Yu Shih; Yu-Min Chang; Kris Descovich; Wen-You Liang; Chung-Hsi Chou; Yi-Chun Lin (Applied Animal Behaviour Science, 2023)

Harnessing split fluorescent proteins in modular protein logic for advanced whole-cell detection - Ping-Heng Lin; Ssu-Tzu Tsai; Yu-Chia Chang; Yi-Ju Chou; Yi-Chun Yeh (Analytica Chimica Acta, 2023)

The association of bisphenol A and paraben exposure with sensorineural hearing loss in children - Chia-Huang Chang; Chun-Ting Lu; Tai-Ling Chen; Wen-Tzu Huang; Pao-Chuan Torng; Chen-Wei Chang; Yu-Chun Chen; Yu-Lin Yu; Yung-Ning Chuang (Environmental Science and Pollution Research, 2023)

A novel framework for spatiotemporal groundwater pumping process estimation based on data-driven approaches - Hwa-Lung Yu; Hua-Ting Tseng; Ying-Fan Lin; Chun-Hung Chen; Ying-Chang Kuo; Yun-Ta Cheng (Journal of Hydrology, 2023)

The AMPK-dependent inhibition of autophagy plays a crucial role in protecting photoreceptor from photooxidative injury - Yu-Lin Li; Tian-Zi Zhang; Li-Kun Han; Chang He; Yi-Ran Pan; Bin Fan; Guang-Yu Li (Journal of Photochemistry and Photobiology B: Biology, 2023)

Dietary administration of a postbiotic, heat-killed Pediococcus pentosaceus PP4012 enhances growth performance, immune response and modulates intestinal microbiota of white shrimp, Penaeus vannamei - Rolissa Ballantyne; Jai-Wei Lee; Sz-Tsan Wang; Jin-Seng Lin; Deng-Yu Tseng; Yi-Chu Liao; Hsiao-Tung Chang; Ting-Yu Lee; Chun-Hung Liu (Fish & Shellfish Immunology, 2023)

Maternal exposure to fine particulate matter and congenital heart defects during preconception and pregnancy period: A cohort-based case-control study in the Taiwan maternal and child health database - Ya-Chu Chang; Yu-Ting Lin; Chau-Ren Jung; Ke-Wei Chen; Bing-Fang Hwang (Environmental Research, 2023)

Association between Glyphosate Exposure and Erythrograms in a Representative Sample of US Adults: NHANES 2013–2014 - Ming-Hao Chang; Pei-Lun Chu; ChiKang Wang; Chien-Yu Lin (Environmental Science and Pollution Research, 2023)

Culturing reef-building corals on a laboratory dish: a simple experimental platform for stony corals - Shinya Shikina; Tzu-Chieh Lin; Yu-Ling Chu; Yin-Chu Cheng; Yu-En Chang; Naohisa Wada; Sen-Lin Tang; Yoshiyuki Iizuka; Yi-Ling Chiu (Frontiers in Marine Science, 2023)
Development and maintenance of coral reef ecosystems rely on daily micro-biological activities of healthy corals. Although a comprehensive understanding of coral biological properties, as well as factors negatively affecting coral growth, are essential to conserve existing corals, the current lack of a tractable culture and experimental platform has delayed acquisition of such knowledge. Here we show a highly versatile culture system, “coral-on-a-laboratory dish” (CLD), allowing long-term culturing of various corals in plastic/glass Petri dishes with maintenance of their biological properties. Under optimized conditions, coral microcolonies (~5 mm x 5 mm fragments) of Pocillopora damicornis were cultured for several months in dishes with high survivorship and characteristic growth. These microcolonies maintained their biological properties, such as reproduction, skeleton formation, coral-algal symbiosis, ingestion, and digestion. Thus far, CLD has been used to maintain at least 4 other coral species from 4 other families, including the Acroporidae, the Pocilloporidae, the Poritidae, and the Merulinidae for more than 2 months with 100% survivorship. CLD is applicable to a variety of biophysiological studies, including coral-algal symbiosis and impact assessment of marine pollutants, e.g., a sunscreen substance, oxybenzone, and an organic biocide, Irgarol 1051, at cellular-level resolution. The CLD platform, which allows easy and inexpensive coral maintenance in a laboratory incubator, represents a technological breakthrough that will greatly advance coral studies.

New ent -kaurene and germacrene derivatives from Mesona procumbens Hemseley and their biological activity - Jerome G. Ganzon; Chia-Ching Liaw; Yu-Chi Lin; Zhi-Hu Lin; Chang-Hung Wang; Che-Yi Chen; Kuo-Hsiang Chuang; Yao-Haur Kuo (Natural Product Research, 2023)

Long-term in-situ starvation and reactivation of co-digestion with food waste and corn straw in a continuous AnDMBR: Performance, sludge characteristics, and microorganism community - Bao-Shan Xing; Xiang-Lin Chang; Sifan Cao; Dong Wu; Yi Zhang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Science of The Total Environment, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Ganglioside-focused Glycan Array Reveals Abnormal Anti-GD1b Auto-antibody in Plasma of Preclinical Huntington’s Disease - Tien-Wei Lin; Jung-Kai Chang; Yih-Ru Wu; Tsung-Hsien Sun; Yang-Yu Cheng; Chien-Tai Ren; Mei-Hung Pan; Jin-Lin Wu; Kuo-Hsuan Chang; Hwai-I Yang; Chiung-Mei Chen; Chung-Yi Wu; et al. (Molecular Neurobiology, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

Numerical study on unsteady propeller exciting characteristics considering shafting whirling vibration effect - Chang-Lin Meng; Zhi-Jun Shuai; Tao Yu; Ke-Xin Ren; Jie Jian; Xi Wang; Dong-Hua Wang; Wan-You Li; Chen-Xing Jiang (Ocean Engineering, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

Improving Aquaculture Water Quality Using Dual-Input Fuzzy Logic Control for Ammonia Nitrogen Management - Hung-Chih Li; Ker-Wei Yu; Chang-Hua Lien; Chitsan Lin; Cheng-Ruei Yu; Sundarapandian Vaidyanathan (Journal of Marine Science and Engineering, 2023)
In this paper, a closed-loop control system using dual-input fuzzy logic theory is proposed to improve the water quality of aquaculture. The new closed-loop control system is implemented on a Raspberry-Pi-embedded platform using Python programming. The proposed closed-loop control system integrates an RS485 function, a database transfer module, a simulating variable group function, and a trigger function import to achieve savings in human resources, power, and water consumption. The proposed closed-loop control system is equipped with an ammonia nitrogen sensor and solenoid valves for the water exchange. The experimental results demonstrate that the intelligent controller can rapidly eliminate ammonia nitrogen within the range of 2.0 ppm and maintain robust control in response to changes in ammonia nitrogen excretion from a school of fish. The experimental results provide insights into the relationship between tank capacity, water exchange solenoid valves, and ammonia nitrogen degradation time, which can be used to optimize aquaculture density and improve industrialization. The experimental results demonstrate that the savings for power and water can be achieved above 95%.

Characteristics of changes in volatile organic compounds and microbial communities during the storage of pickles - Xi-han Sun; Xin Qi; Yu-di Han; Zhi-jun Guo; Cheng-bi Cui; Chang-qing Lin (Food Chemistry, 2023)

Mechanisms of acidic electrolyzed water killing bacteria - Fan Wang; Yan-Ning Lin; Yu Xu; Yong-Bing Ba; Zhao-Huan Zhang; Li Zhao; Wing Lam; Fu-Lan Guan; Yong Zhao; Chang-Hua Xu (Food Control, 2023)

Bona fide upcycling strategy of anhydride cured epoxy and reutilization of decomposed dual monomers into multipurpose applications - Lin Shao; Yu-Chung Chang; Baoming Zhao; Xinyan Yan; Brian J. Bliss; Ming-en Fei; Chenhao Yu; Jinwen Zhang (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

July 2020 heavy rainfall in Japan: effect of real-time river discharge on ocean circulation based on a coupled river-ocean model - Yu-Lin K. Chang; Sergey M. Varlamov; Xinyu Guo; Toru Miyama; Yasumasa Miyazawa (Ocean Dynamics, 2023)
In July 2020, a stationary atmospheric front over Japan caused persistent, nearly continuous rain for most of the month that resulted in new historical highest rainfall records in several areas and caused serious river floods, landslides, and debris-flow events. An existing hindcast and forecast ocean circulation model that includes climatological discharge information of major rivers failed to represent the extreme river discharge under heavy rainfall. New experiments were conducted using real-time river discharge information based on Today's Earth CaMa-Flood simulation that includes 368 rivers in Japan. The inclusion of real-time river discharge improved the salinity bias in the near-surface waters. The differences were significant compared to the observations in the heavy rain region (i.e., Ariake Bay and Tosa Bay), and insignificant at offshore stations. The ensemble experiments of real-time river discharge cases suggested the difference between the climatological and the real-time river discharge experiments was not random, but was robust. The freshening water changed the shelf circulation, and its far-reaching effect appeared hundreds of kilometers away from the shore. Passive particle tracking was conducted for examining the cross-shelf exchange. More particles released from Bungo Channel went offshore in near-surface water when the real-time river discharge was used compared to using the climatology discharge. Particles released in Tosa Bay, Seto Inland Sea, and Kii Channel showed the opposite tendency. The real-time river discharge not only changed the modeled coastal salinity distribution, but also the coastal and offshore currents. The role of the real-time river discharge on modeling normal flow periods or drought events, and its influence on a longer time scale model simulation remain to be explored.

Analysis of natural disasters and energy efficiency in China - Zhong Fang; Yung-ho Chiu; Tai-Yu Lin; Tzu-Han Chang; Yi-Nuo Lin (Environment, Development and Sustainability, 2023)

Effects of biodegradation, biotoxicity and microbial community on biostimulation of sulfolane - Shao-Heng Chang; Chi-Wen Lin; Yu-Shen Cheng; Shu-Hui Liu (Chemosphere, 2023)

Evaluating the waste and CO2 reduction potential of packaging by reuse model in supermarkets in Taiwan - Hsin-Tien Lin; Cian-Wei Chiang; Jhao-Ning Cai; Hsin-Yu Chang; Yu-Nien Ku; Falk Schneider (Waste Management, 2023)

Release, denitrification performance, and generated waste utilization of alkali-modified lignocellulosic materials as denitrification carbon sources - Zhiyuan Lin; Yu Ling; Guokai Yan; Haiyan Wang; Zhuanjun Zhao; Yang Chang; Weiyang Dong; Huan Wang; Zhaosheng Chu; Shuqi Guan; Yanjie Zhang; Fan Guo (Journal of Water Process Engineering, 2023)

The ability of pre-magnetized zero-valent iron for peroxymonosulfate activation to remove ofloxacin - Yang Wu; Jing-ying Zhu; Jia-wen Bai; Li-feng Lin; Chang-ping Yu (Chemical Engineering Journal, 2023)

PanGu Drug Model: learn a molecule like a human - Xinyuan Lin; Chi Xu; Zhaoping Xiong; Xinfeng Zhang; Ningxi Ni; Bolin Ni; Jianlong Chang; Ruiqing Pan; Zidong Wang; Fan Yu; Qi Tian; Hualiang Jiang; et al. (Science China Life Sciences, 2023)

α7 nicotinic acetylcholine receptor agonist improved brain injury and impaired glucose metabolism in a rat model of ischemic stroke - Ya-Yu Wang; Shih-Yi Lin; Cheng-Yi Chang; Chih-Cheng Wu; Wen-Ying Chen; Wei-Chi Huang; Su-Lan Liao; Wen-Yi Wang; Chun-Jung Chen (Metabolic Brain Disease, 2023)

Removal and concurrent reduction of Cr(VI) by thermoacidophilic Cyanidiales: a novel extreme biomaterial enlightened for acidic and neutral conditions - Yen-Lin Cho; Yu-Min Tzou; Chun-Chieh Wang; Yao-Chang Lee; Liang-Ching Hsu; Shao-Lun Liu; Afifah Assakinah; Yu-Hsien Chen; Nhu Anh Thi Than; Yu-Ting Liu; Jörg Rinklebe (Journal of Hazardous Materials, 2023)

Preparation of alumina/silica/exfoliated graphite nanoplatelets composite aerogels and its application as supporting material for erythritol based form-stable phase change materials - Yu-Hao Ning; Ye Tan; Chuan-Huang Lin; Qi Li; Lin-Ping Yu; Zhong Cao; Li-Xian Sun; Chuan-Chang Li; Ju-Lan Zeng (Chemical Engineering Journal, 2023)

Ambient relative humidity-dependent obstructive sleep apnea severity in cold season: A case-control study - Kuan-Jen Bai; Wen-Te Liu; Yuan-Chien Lin; Yansu He; Yueh-Lun Lee; Dean Wu; Ta-Yuan Chang; Li-Te Chang; Chun-Yeh Lai; Cheng-Yu Tsai; Kian Fan Chung; Kin-Fai Ho; et al. (Science of The Total Environment, 2023)

Greenhouse gas emission indicators, energy consumption efficiency, and optimal carbon emission allowance allocation of the EU countries in 2030 - Tai-Yu Lin; Yung-Ho Chiu; Yi-Nuo Lin; Tzu-Han Chang; Pei-Yu Lin (Gas Science and Engineering, 2023)

Associations between maternal phthalate exposure and neonatal neurobehaviors: The Taiwan maternal and infant cohort study (TMICS) - Hsing-Kang Chen; Shu-Li Wang; Yu-Hsun Chang; Chien-Wen Sun; Ming-Tsang Wu; Mei-Lien Chen; Yu-Jie Lin; Chia-Jung Hsieh (Environmental Pollution, 2023)

Possible influence of typhoons, volcanic ash, and ocean productivity on early larval survival and Japanese eel annual cohort recruitment - Yu-Lin K. Chang; Michael J. Miller (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Hydrodynamics and mass transfer performance of gas–liquid microflow in viscous liquids - Lin Sheng; Yu Chang; Jian Deng; Guangsheng Luo (Chemical Engineering Journal, 2023)

Antiherbivore effect of Cuscuta campestris against Spodoptera frugiperda - Chang-Lin Sung; Fang-Yu Hu; Yi Li; Shin-Fu Tsai; Wen-Po Chuang (Arthropod-Plant Interactions, 2023)

The construction of high efficient visible-light-driven 3D porous g-C3N4/Fe3O4 photocatalyst: A new photo-induced bacterial inactivation material enhanced by cascade photo-Fenton reaction - Ze-Yu Liu; Wen-Qian Huang; Chuan-Qing Huang; Zhao-Zhen Liu; Xiao-Yue Tang; Wei-Chang Chen; Zheng-Zheng Tang; Yu-Xing Huang; Shuo-Chun Zheng; Lin Lin; Changzhu Li; Yong Ye (Chemosphere, 2023)

Identification of high-concern organic pollutants in tap waters from the Yangtze River in China based on combined screening strategies - Liben Chou; Chengzhuo Zhou; Wenrui Luo; Jing Guo; Yanhong Shen; Die Lin; Chang Wang; Hongxia Yu; Xiaowei Zhang; Si Wei; Wei Shi (Science of The Total Environment, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Microbiome reengineering by four environmental factors for the rapid biodegradation of trichloroethylene - Yu-Hsuan Cheng; Shu-Chi Chang; Yan-Lin Lai; Chung-Chi Hu (Journal of Environmental Management, 2023)

Using cluster algorithms with a machine learning technique and PMF models to quantify local-specific origins of PM2.5 and associated metals in Taiwan - Chin-Yu Hsu; Jhy-Charm Soo; Sheng-Lun Lin; Chih-Da Wu; Kai Hsien Chi; Wen-Chang Hsu; Chun-Chieh Tseng; Yu-Cheng Chen (Environmental Pollution, 2023)

Realizing the bifunctional electrocatalysis via local charge rearrangement of α-CrOOH-modulated Co@CoMoOx for overall water splitting - Suh-Ciuan Lim; Chao-Lung Chiang; Chun-Kuo Peng; Wen-Bin Wu; Yu-Chang Lin; Yu-Ru Lin; Chi-Liang Chen; Yan-Gu Lin (Chemical Engineering Journal, 2023)

Lightweight Flexible Polyimide-Derived Laser-Induced Graphenes for High-Performance Thermal Management Applications - Yu-Sheng Hsiao; Cai-Wan Chang-Jian; Tzu-Yen Huang; Ying-Lin Chen; Chung-Wei Huang; Jen-Hsien Huang; Nian-Jheng Wu; Shih-Chieh Hsu; Chih-Ping Chen (Chemical Engineering Journal, 2023)

Functionalized graphene oxide/sodium alginate beads with ion responsiveness for uranium trapping - Yu Nan; Jianli Wang; Xue Chang; Kejin Shao; Yuchen Lin; Lijuan Qian; Zhan Li; Peizhuo Hu (Carbohydrate Polymers, 2023)

CFD simulations of effects of recirculation mode and fresh air mode on vehicle cabin indoor air quality - Tong-Bou Chang; Yu-Sheng Lin; Yi-Tian Hsu (Atmospheric Environment, 2023)

Gas-phase and PM2.5-bound phthalates in nail salons: characteristics, exposure via inhalation, and influencing factors - Chia-Ling Chang; Hui-Tzu Chen; Chung-Yu Chen; En-Yu Chen; Kuan-Ting Lin; Chien-Cheng Jung (Environmental Science and Pollution Research, 2023)

Defect inspection of indoor components in buildings using deep learning object detection and augmented reality - Shun-Hsiang Hsu; Ho-Tin Hung; Yu-Qi Lin; Chia-Ming Chang (Earthquake Engineering and Engineering Vibration, 2023)

Associations between residential proximity to agricultural land use as pesticides exposure and birth outcomes - Kuna-Chun Chen; Shuo-Fang Lee; Shyang-Woei Lin; Jia-Shan Xie; Yu‐Hsun Chang; Lih-Ming Yiin; Chia-Jung Hsieh (Environmental Science and Pollution Research, 2022)

Mesenchymal Stem Cell Secreted-Extracellular Vesicles are Involved in Chondrocyte Production and Reduce Adipogenesis during Stem Cell Differentiation - Yu-Chen Tsai; Tai-Shan Cheng; Hsiu-Jung Liao; Ming-Hsi Chuang; Hui-Ting Chen; Chun-Hung Chen; Kai-Ling Zhang; Chih-Hung Chang; Po-Cheng Lin; Chi-Ying F. Huang (Tissue Engineering and Regenerative Medicine, 2022)
Background: Extracellular vesicles (EVs) are derived from internal cellular compartments, and have potential as a diagnostic and therapeutic tool in degenerative disease associated with aging. Mesenchymal stem cells (MSCs) have become a promising tool for functional EVs production. This study investigated the efficacy of EVs and its effect on differentiation capacity. Methods: The characteristics of MSCs were evaluated by flow cytometry and stem cell differentiation analysis, and a production mode of functional EVs was scaled from MSCs. The concentration and size of EVs were quantitated by Nanoparticle Tracking Analysis (NTA). Western blot analysis was used to assess the protein expression of exosome-specific markers. The effects of MSC-derived EVs were assessed by chondrogenic and adipogenic differentiation analyses and histological observation. Results: The range of the particle size of adipose-derived stem cells (ADSCs)- and Wharton’s jelly -MSCs-derived EVs were from 130 to 150 nm as measured by NTA, which showed positive expression of exosomal markers. The chondrogenic induction ability was weakened in the absence of EVs in vitro . Interestingly, after EV administration, type II collagen, a major component in the cartilage extracellular matrix, was upregulated compared to the EV-free condition. Moreover, EVs decreased the lipid accumulation rate during adipogenic induction. Conclusion: The results indicated that the production model could facilitate production of effective EVs and further demonstrated the role of MSC-derived EVs in cell differentiation. MSC-derived EVs could be successfully used in cell-free therapy to guide chondrogenic differentiation of ADSC for future clinical applications in cartilage regeneration.

AIoT-Based Ergometer for Physical Training in Frail Elderly with Cognitive Decline: A Pilot Randomized Control Trial - Chih-Chun Lin; Li-Chieh Kuo; Yu-Sheng Lin; Chia-Ming Chang; Fang Wen Hu; Yi-Jing Chen; Chun-Tse Lin; Fong-Chin Su (Journal of Medical and Biological Engineering, 2022)
Purpose Reduced physical activity is reported in the elderly, especially in institutional residents. Institutionalized older adults exhibit a high prevalence of frailty. In this work, we developed an artificial intelligence of things (AIoT)-based feedback assistive strengthening ergometer (AIFASE), for the physical strengthening of the elderly with intelligent assistance. Methods We conducted a 12-week intervention in a long-term care facility. In total, 16 participants (84.38 ± 6.0 years; 4 males and 12 females) were recruited with 1:1 randomization of exercise to control groups. The muscle strength of the lower extremities, timed up and go test (TUG), and Short-form Physical Performance Battery (SPPB) of the participants were measured. The AIFASE system allows the clinical staff to record the personal physical performance of the elderly and generates personalized exercise prescriptions accordingly. AIFASE also displays the current usage status of all ergometers and the users’ physiological conditions. The algorithms were developed to generate warning alerts when the training workload was too large by personal physiological detection. AIFASE automatically customized the exercise prescription according to the user’s exercise performance. Results After a 12-week AIFASE intervention, the intervention group exhibited significant improvements in the strength of the hip flexor, Semi-Tandem Stand, and Tandem Stand. Conclusion In this study, we developed an AIoT ergometer that delivered customized physical training prescriptions to improve the physical performance of long-term care facility residents. We believe that the application of AIFASE will help improve the quality of institutional care.

Potential risk from and prevention of phytoplankton outbreaks in blocking the cooling water system in a nuclear power plant on the Southeast China coast - Yu Wang; Xiaoyin Chen; Yingyue Lin; Shuyi Zhang; Lin Chang; Xiaoming Tang; Peng Xiang; Heshan Lin (Frontiers in Marine Science, 2022)
The invasion or aggregation of marine biota in coastal waters has become a common problem, threatening the safety of cooling water systems in the context of environmental and climate changes. However, studies on issues of coastal nuclear power plants from the view of marine ecology have mostly focused on the thermal effluent, entrainment effect on organisms, residual chlorine, radioactivity, etc. There is a lack of information on the safety of cooling water systems in nuclear power plants blocked by marine biota. Based on field and historical datasets, this study screened phytoplankton species that may potentially block the cooling water system of the Fuqing nuclear power plant on the Southeast China coast, identified the phytoplankton risk and a risk calendar, and established a catalog of risk phytoplankton species for the cooling water system. The screening criteria were simultaneously required as follows: (1) particle size of cells or group >2000 μm; (2) phytoplankton bloom or aggregation events occurred in surrounding areas; (3) and species abundance maintained at >0.5×10 5 cells/L in the surrounding area. Nine high-risk species were screened out that can easily form colonies, clusters, and groups, including Thalassiosira diporocyclus , Thalassiosira subtilis , Noctiluca scintillans , Phaeocystis globosa , Pseudo-nitzschia pungens , Pseudo-nitzschia delicatissima , Skeletonema costatum , Skeletonema dohrnii , Paralia sulcata . Due to small cells or the formation of short chains, some dominant phytoplankton species, even those with advantages in abundance and occurrence, had difficulty threatening the reliability of cooling water systems in nuclear power plants. The outbreak of different phytoplankton species varied daily, and the risk of blockage was highest from April to July. The biological characteristics, ecological mechanisms underlying outbreaks of high-risk phytoplankton species are reviewed and discussed, suggesting a high degree of temporal and spatial variability of blockage risk. Finally, main prevention and control measures used against high-risk phytoplankton species are provided to imply new ideas and methods for nuclear power plants. These strategies have very important practical and scientific significance.

Protective effect of ginsenoside Rd on military aviation noise-induced cochlear hair cell damage in guinea pigs - Xue-min Chen; Yu-hui Liu; Shuai-fei Ji; Xin-miao Xue; Lin-lin Wang; Min Zhang; Yao-ming Chang; Xiao-cheng Wang (Environmental Science and Pollution Research, 2022)

A study of peatland-derived dissolved organic matter from headstream to sea using multiple analytical tools - François L. L. Muller; Kuei-Chen Chang; Yu-Chieh Wang; Chon-Lin Lee (Environmental Science and Pollution Research, 2022)

7,8-Dihydroxyflavone attenuates the virulence of Staphylococcus aureus by inhibiting alpha-hemolysin - Nan Bian; Xiangqian Chen; Xinran Ren; Zishu Yu; Mengli Jin; Xiaoyu Chen; Chang Liu; Yanhe Luan; Lin Wei; Ying Chen; Wu Song; Yicheng Zhao; et al. (World Journal of Microbiology and Biotechnology, 2022)

A 10-miRNA risk score-based prediction model for pathological complete response to neoadjuvant chemotherapy in hormone receptor-positive breast cancer - Chang Gong; Ziliang Cheng; Yaping Yang; Jun Shen; Yingying Zhu; Li Ling; Wanyi Lin; Zhigang Yu; Zhihua Li; Weige Tan; Chushan Zheng; Wenbo Zheng; et al. (Science China Life Sciences, 2022)

Multi-stage melt impregnation and magma–seawater interaction in a slow-spreading oceanic lithosphere: constraints from cumulates in the Lagkorco ophiolite (central Tibet) - Wei-Qi Zhang; Chuan-Zhou Liu; Tong Liu; Chang Zhang; Zhen-Yu Zhang; Xiao-Ni Li; Zhen Zhang; Yin-Zheng Lin (Contributions to Mineralogy and Petrology, 2022)

Numerical analysis of pile—slope stability and the soil arching around two adjacent piles - Chien-Yuan Chen; Chun-Kai Chang; Yu-Shan Lin (Journal of Mountain Science, 2022)

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

Evaluation of the Potential of the Hard Clam (Meretrix meretrix) Shell Which Can Be Used as the Bioindicator for Heavy Metal Accumulation - Yen-Ting Lin; Fang-Chi Chang; Ming-Tsung Chung; Ze-Kai Li; Chang-Chuan Chan; Ying-Sheng Huang; Kuo-Fang Huang; Yu-San Han (Fishes, 2022)
Clams, Meretrix meretrix, were one of the favorite aquatic products in Taiwan and the world. It was reported that the water pollutants such as heavy metals and chemicals might accumulate in the clam body and shell through filter-feeding behavior. Thus, the bivalves could be used as bioindicators in the aquatic environment. The present study analyzed 20 trace elements, Mg, Sr, Li, Cd, Ba, Mn, Al, U, Ti, Pb, Nd, B, S, Zn, Fe, P, Na, K, Cu, and Ni, in the shells of the clams collected from the wild coastal area and cultured ponds to evaluate which elements have the potential to be biomarkers. The concentrations of 20 elements were detected by Solution-Based Inductively Coupled Plasma Mass Spectrometry (SB-ICPMS). Among them, Cd, Al, U, Ti, Nd, S, and K were below the detection limit. The remaining elements were analyzed for accumulation. The levels of Zn, Fe, and Ni possess high variation in an identical environment; so, a PCA was conducted without these three elements to reduce noise. The PCA result proved that the clam could absorb specific trace elements from the habitat. After a period of time, the contents of the absorption in the shells of the clams living in an identical environment became more similar. The analyzed element, Pb, was not found with a special difference in this study. The levels of Na, Sr, Mg, B, Mn, P, Ba, Li, and Cu reflected different sampling sites, which suggested that these elements in the species M. meretrix had the potential to be used as biomarkers for assessing heavy metal accumulation in the environment.

The influence of climate change on the allocation efficiency of new and tradition energy - Kuei-Ying Huang; Yung-ho Chiu; Tzu-Han Chang; Tai-Yu Lin (Environmental Science and Pollution Research, 2022)

Hippocampal Iron Accumulation Impairs Synapses and Memory via Suppressing Furin Expression and Downregulating BDNF Maturation - Yating Zhang; Xue Bai; Yi Zhang; Shanshan Yao; Yiduo Cui; Lin-Hao You; Peng Yu; Yan-Zhong Chang; Guofen Gao (Molecular Neurobiology, 2022)

Biomechanical Analysis of Mandibular Implant-Assisted Removable Partial Denture with Distal Extension - Yung-Chung Chen; Chi-Lun Lin; Chen-Han Yu; Hung-Chih Chang; Yang-Ming Lin; Jia-Wei Lin (Journal of Medical and Biological Engineering, 2022)

Plant secondary metabolite and temperature determine the prevalence of Arsenophonus endosymbionts in aphid populations - Chun‐Yan Chang; Xiao‐Wan Sun; Pan‐Pan Tian; Ning‐Hui Miao; Yu‐Lin Zhang; Xiang‐Dong Liu (Environmental Microbiology, 2022)
Summary Transmission rate and role in hosts contribute to the prevalence of an endosymbiont. However, factors affecting transmission and role of facultative endosymbionts are still not well understood. Here, we illustrated that host plants and environmental temperatures affected the transmission, relative abundance and role of Arsenophonus in the cotton aphid Aphis gossypii . The transmission rate of this endosymbiont from mother aphids to offspring was relatively lower. High temperatures impeded the transmission, and infection rates declined as aphids were exposed to 30°C. Contents of amino acids and secondary metabolites were remarkably different among host plants. Aphids feeding on zucchini leaves containing a higher titre of amino acids and lower secondary metabolites harboured a relatively lower abundance of Arsenophonus . Concentrations of an amino acid and a plant secondary metabolite, cucurbitacin B, in aphid diet were not associated with Arsenophonus abundance. However, gossypol, another plant secondary metabolite, was strongly related with the abundance. Arsenophonus imparted a fitness benefit to aphids, and the benefit was dependent on host plants and gossypol concentration. In sum, plant secondary metabolite and environmental temperature affect transmission, relative abundance and role of Arsenophonus , which determine the endosymbiont prevalence in aphid populations.

Vertical patterns of chlorophyll a in the euphotic layer are related to mesoscale eddies in the South China Sea - Mei-Lin Wu; You-Shao Wang; Yu-Tu Wang; Fu-Lin Sun; Xiaomei Li; Fang-Fang Gu; Jing-Chang Xiang (Frontiers in Marine Science, 2022)
Phytoplankton closely connects with the hydrodynamics and biogeochemical environment of the ocean. While research focusing on both the physiochemical factors and hydrodynamics regulating phytoplankton has already been conducted, the coupling mechanism between mesoscale eddies and the vertical distribution of phyto plankton in the South China Sea (SCS) is still not well understood. Here, phytoplankton was studied under one weak-cold and two warm eddies along the 18°N transect in the SCS. The results show that the vertical distribution of chlorophyll (chl- a ) presented a similar pattern at all four sampling stations. The mixed layer is less than 50 m. It is the same as the meridional salinity gradients that may be distinguished above a depth of 60 m. The subsurface chlorophyll maximum at the edge of a warm (WI) and cold eddy (CI) at E413 and E411 was shallower than that at the edge of a warm eddy (WII) at E407 and E409, indicating that temperature and salinity may be the important driving factors. On the whole, mesoscale eddies had a significant influence on the vertical pattern of chl- a in the SCS during the study period.

Development of wheat-Dasypyrum villosum T6V#4S·6AL translocation lines with enhanced inheritance for powdery mildew resistance - Xiaolan Ma; Yanan Chang; Jingnan Chen; Mei Yu; Baicui Wang; Xingguo Ye; Zhishan Lin (Theoretical and Applied Genetics, 2022)

Correction to: Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Fine particulate matter measured by satellites predicts the risk of age-related macular degeneration in a longitudinal cohort study - Chung-Ling Liang; Chi-Min Wang; Chau-Ren Jung; Ya-Chu Chang; Chun-Ju Lin; Yu-Ting Lin; Bing-Fang Hwang (Environmental Science and Pollution Research, 2022)

Dapagliflozin protects against doxorubicin-induced cardiotoxicity by restoring STAT3 - Wei-Ting Chang; Jhih-Yuan Shih; Yu-Wen Lin; Zhih-Cherng Chen; Wei-Chih Kan; Tsung-Hsien Lin; Chon-Seng Hong (Archives of Toxicology, 2022)

Streptococcus vulneris sp. nov., isolated from wound of patient with diabetic foot ulcer (DFU) - Jen-hao Chung; Li-Ting Wang; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Jui-hsiang Li (Archives of Microbiology, 2022)

Estrogenic and anti-neutrophilic inflammatory phenanthrenes from Juncus effusus L. - Hao-Chun Hu; Yi-Hong Tsai; Yu-Che Chuang; Kuei-Hung Lai; Yu-Ming Hsu; Tsong-Long Hwang; Chih-Chan Lin; Ferenc Fülöp; Yang-Chang Wu; Szu-Yin Yu; Yu-Ting Kuo; Fang-Rong Chang (Natural Product Research, 2022)

Lactobacillus plantarum PS128 Promotes Intestinal Motility, Mucin Production, and Serotonin Signaling in Mice - Chih-Ming Chen; Chien-Chen Wu; Chin-Lin Huang; Min-Yu Chang; Shih-Hsuan Cheng; Ching-Ting Lin; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2022)
Lactobacillus plantarum PS128 has been reported as a psychobiotic to improve mental health through the gut–brain axis in experimental animal models. To explore its mechanism of action in the gut, this study aimed to analyze the effects of L. plantarum PS128 ingestion on naïve and loperamide (Lop)-induced constipation mice. We found that, in the two mouse models, the weight, number, and water content of feces in the L. plantarum PS128 group were higher than those in the vehicle control group. Histological observation revealed that L. plantarum PS128 increased the level of colonic mucins including the major mucin MUC2. In addition, the charcoal meal test showed that L. plantarum PS128 significantly increased the small intestine transit in naïve mice, but not in the Lop-treated mice. Since intestinal serotonin has been found to modulate motility, we further analyzed the expression of genes related to serotonin signal transduction in the small intestine of naïve mice. The results showed that L. plantarum PS128 significantly altered the expression levels of Tph1 , Chga , Slc6a4 , and Htr4 , but did not affect the expression levels of Tph2 , Htr3a , and Maoa . Furthermore, immunohistochemistry revealed that L. plantarum PS128 significantly increased the number of serotonin-containing intestinal cells in mice. Taken together, our results suggest that L. plantarum PS128 could promote intestinal motility, mucin production, and serotonin signal transduction, leading to a laxative effect in mice.

Shear Instability and Turbulent Mixing in the Stratified Shear Flow Behind a Topographic Ridge at High Reynolds Number - Jia-Lin Chen; Xiao Yu; Ming-Huei Chang; Sen Jan; Yiing Jang Yang; Ren-Chieh Lien (Frontiers in Marine Science, 2022)
Observations on the lee of a topographic ridge show that the turbulence kinetic energy (TKE) dissipation rate due to shear instabilities is three orders of magnitude higher than the typical value in the open ocean. Laboratory-scale studies at low Reynolds number suggest that high turbulent dissipation occurs primarily within the core region of shear instabilities. However, field-scale studies indicate that high turbulence is mainly populated along the braids of shear instabilities. In this study, a high-resolution, resolving the Ozmidov-scale, non-hydrostatic model with Large Eddy Simulation (LES) turbulent closure is applied to investigate dominant mechanisms that control the spatial and temporal scales of shear instabilities and resulting mixing in stratified shear flow at high Reynolds number. The simulated density variance dissipation rate is elevated in the cusp-like bands of shear instabilities with a specific period, consistent with the acoustic backscatter taken by shipboard echo sounder. The vertical length scale of each cusp-like band is nearly half of the vertical length scale of the internal lee wave. However, it is consistent with instabilities originating from a shear layer based on linear stability theory. The model results indicate that the length scale and/or the period of shear instabilities are the key parameters to the mixing enhancement that increases with lateral Froude number Fr L , i.e. stronger shear and/or steeper ridge.

Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Hypothermal Effects on Energy Supply for Ionocytes in Gills of Freshwater- and Seawater-Acclimated Milkfish, Chanos chanos - Chia-Hao Chang; Chia-Jui Liu; Wei-Jie Lu; Li-Yang Wu; Kuang-Jie Lai; Yu-Ting Lin; Tsung-Han Lee (Frontiers in Marine Science, 2022)
The milkfish, Chanos chanos , is an important aquaculture species that can be cultured in freshwater (FW) and seawater (SW) ponds because of its high euryhalinity. In winter, cold snap leading to high mortality of this tropical species is a critical issue for the aquaculture industry in Taiwan. Under hypothermal stress, however, changes in energy supply for osmoregulation of this euryhaline species is intriguing. In this study, we used an antibody against glycogen phosphorylase (GP) to identify glycogen-rich (GR) cells distributed adjacent to the mitochondria-rich (MR) ionocytes in milkfish gills. Glucose transporter 1 (GLUT1), which plays a major role in energy supply, was also identified and localized in GR cells. Moreover, the expression of indicators of aerobic metabolism and energy production, citrate synthase (CS) and cytochrome c oxidase (COX), were analyzed in gills of FW- and SW-acclimated milkfish to reveal different strategies of energy utilization under hypothermal stress. When exposed to a low-temperature environment, SW individuals used branchial glycogen and lactate to match the energy demands of aerobic metabolism in ionocytes, and elevated aerobic capacity to support and maintain normal functions in gills. However, branchial glycogen mainly localized in the GR cells of FW milkfish was not utilized under hypothermal stress. Meanwhile, a similar level of branchial COX activity and COXIV protein abundance at low temperatures between FW and SW milkfish indicated similar energy requirements in gills. This suggested that another source, but not branchial glycogen, maintained the energy demand in FW milkfish. The present study illustrated differential energy supply strategies in gills between SW- and FW-acclimated milkfish for osmoregulation under low temperatures.

Selenium Alleviates Inflammation in Staphylococcus aureus-Induced Mastitis via MerTK-Dependent Activation of the PI3K/Akt/mTOR Pathway in Mice - Si-jie Chen; Chen-yuan Zhang; Di Yu; Chang-jie Lin; Hao-jun Xu; Chang-min Hu (Biological Trace Element Research, 2022)

The significance of riparian communities in the energy flow of subtropical stream ecosystems - Yi-Chang Liao; An-Cheng Lin; Han-Ni Tsai; Yu-Ting Yen; Chyng-Shyan Tzeng; Man-Miao Yang; Hsing-Juh Lin (Aquatic Sciences, 2022)

Association of DNA methylation and transcriptome reveals epigenetic etiology of heart failure - Zhongxiao Lin; Jishuo Chang; Xinzhi Li; Jianglin Wang; Xiaodan Wu; Xiaoyan Liu; YiZhun Zhu; Xi-Yong Yu (Functional & Integrative Genomics, 2022)

Measuring Heterogeneity in 18F-Fluorodeoxyglucose Positron Emission Tomography Images for Classifying Metastatic and Benign Bone Lesions in Patients with Cervical Cancer - Feng-Yuan Liu; Gigin Lin; Jing-Ren Tseng; Angel Chao; Huei-Jean Huang; Hung-Hsueh Chou; Yu-Chen Chang; Tzu-Chen Yen; Chyong-Huey Lai (Journal of Medical and Biological Engineering, 2021)
Purpose Heterogeneity assessment can be applied for medical imaging analysis. Here, we evaluated first-order and texture analysis (TA) metrics in 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET) imaging for classification of metastatic and benign bone lesions in patients with cervical cancer. Methods The data of 18 F-FDG PET studies performed on a specific PET/CT system from 2016 to 2018 in patients with cervical cancer were retrieved. The data of bone lesions extracted from studies over 2016–2017 and 2018 were used as training and validation datasets, respectively. Metastatic bone lesions were identified in each dataset, with an equal number of benign bone lesions selected. Cuboid volume of interest (VOI) consisting of 3 × 3 × 5 reconstructed voxels was applied for first-order metrics, and cubic VOI consisting of smaller voxels with trilinear interpolation of standardized uptake value (SUV) was adopted for TA metrics. First-order metrics included the maximum SUV (SUVmax) of lesions and the mean voxel SUV and its standard deviation (SUVsd), skewness, and kurtosis in VOI. In total, 4464 TA metrics based on 62 texture features were evaluated. Logistic regression was used for classification with area under the receiver operating characteristic curve (AUC) as the performance measure. Results From the training and validation datasets, 98 and 42 metastatic bone lesions were identified, respectively. SUVsd demonstrated higher performance than did SUVmax in both the training (AUC .798 vs .732, P = .001) and validation (AUC .786 vs .684, P < .001) datasets. Top-performing TA metrics demonstrated significantly higher performance in the training dataset, but not in the validation dataset. Conclusion A simple first-order measure of heterogeneity, SUVsd, was found to be superior to SUVmax for the classification of metastatic and benign bone lesions. Multiple hypothesis testing can result in false-positive findings in TA with multiple features and parameters; careful validation is required.

Timing and magnitude of climatic extremes differentially elevate mortality but enhance recovery in a fish population - Ming‐Chih Chiu; Shih‐Hsun Chang; Yu‐Ting Yen; Lin‐Yan Liao; Hsing‐Juh Lin (Global Change Biology, 2021)
The countervailing effects of disturbances (e.g., high mortality and enhanced recovery) on population dynamics can occur through demographic processes under rapidly increasing climatic extremes. Across an extreme‐event gradient, we mechanistically demonstrated how dramatic changes in streamflow have affected the population persistence of endangered salmon in monsoonal Taiwan over a three‐decade period. Our modeling indicated that the dynamics of the age‐structured population were attributed to demographic processes, in which extensive mortality was characterized as a function of climatic extremes and vulnerability in the young stage of fish. In the stochastic simulations, we found that the extensive mortality and high proportion of large fish resulted from extreme flooding, which caused high values of postimpact population recovery. Our empirical evidence suggests that the magnitudes and timing of disturbance can explain the population persistence when facing climatic extremes and thereby challenges the understanding of the mechanistic drivers of these countervailing phenomena under changing environmental conditions.

Streptococcus vaginalis sp. nov., a novel bacterial species isolated from vaginal swabs of a pregnant woman with diabetes - An-Shine Chao; Chiao-Yun Lin; Angel Chao; Yun-Shien Lee; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Yi-Sheng Chen (Archives of Microbiology, 2021)

Wave-ice dynamical interaction: a numerical model and its application - Yang Zhang; Changsheng Chen; Guoping Gao; Jianhua Qi; Huichan Lin; Wei Yu; Liang Chang (Acta Oceanologica Sinica, 2021)

Image Segmentation in 3D Brachytherapy Using Convolutional LSTM - Jui-Hung Chang; Kai-Hsiang Lin; Ti-Hao Wang; Yu-Kai Zhou; Pau-Choo Chung (Journal of Medical and Biological Engineering, 2021)

Bioaccumulation and translocation of trace elements in soil-irrigation water-wheat in arid agricultural areas of Xin Jiang, China - Muyesaier Tudi; Huada Daniel Ruan; Yunjiang Yu; Li Wang; Binggan Wei; Shuangmei Tong; Chang Kong; Lin-sheng Yang (Ecotoxicology, 2021)

The relationship between anthocyanin accumulation and photoprotection in young leaves of two dominant tree species in subtropical forests in different seasons - Zheng-Chao Yu; Wei Lin; Xiao-Ting Zheng; Wah Soon Chow; Yan-Na Luo; Min-Ling Cai; Chang-Lian Peng (Photosynthesis Research, 2021)

The major photoprotective role of anthocyanins in leaves of Arabidopsis thaliana under long-term high light treatment: antioxidant or light attenuator? - Xiao-Ting Zheng; Zheng-Chao Yu; Jun-Wei Tang; Min-Ling Cai; Yi-Lin Chen; Cheng-Wei Yang; Wah Soon Chow; Chang-Lian Peng (Photosynthesis Research, 2021)

Photosynthetic compensation of non-leaf organ stems of the invasive species Sphagneticola trilobata (L.) Pruski at low temperature - Min-ling Cai; Wen-qiao Ding; Jun-jie Zhai; Xiao-ting Zheng; Zheng-chao Yu; Qi-lei Zhang; Xiao-hua Lin; Wah Soon Chow; Chang-lian Peng (Photosynthesis Research, 2021)

Gas-phase isopropanol degradation by nonthermal plasma combined with Mn-Cu/-Al2O3 - Ken-Lin Chang; Yu-Chieh Lin; Ming-Ze Qiu; Chun-Wei Tu; Chih-Ping Chang; Jhong-Lin Wu; Yung-Chang Lin; Chien-Kuei Chang (Environmental Science and Pollution Research, 2021)

Geographic and subsequent biotic isolations led to a diversity anomaly of section Heterotropa (genus Asarum : Aristolochiaceae) in insular versus continental regions of the Sino‐Japanese Floristic Region - Daiki Takahashi; Shota Sakaguchi; Yu Feng; Yuji Isagi; Ying‐Xiong Qiu; Pan Li; Rui‐Sen Lu; Chang‐Tse Lu; Shih‐Wen Chung; Yang‐Shan Lin; Yun‐Chao Chen; Atsushi J. Nagano; et al. (Journal of Biogeography, 2021)
Aim The Sino‐Japanese Floristic Region has extremely high species diversity with respect to temperate plants; however, the reasons for this diversity are poorly understood because most studies have only considered geographic isolation caused by climatic oscillations. In some plant groups, high floral trait diversity and uneven species diversity between insular systems and the continental area suggest other factors may have important roles too. The primary purpose of this study is to reveal how abiotic and biotic factors have shaped the species diversity anomaly of Heterotropa between the insular systems and the continental area. Location The Sino‐Japanese Floristic Region. Taxon Section Heterotropa (genus Asarum ; Aristolochiaceae). Methods Using ddRAD‐seq and chloroplast genome data, we built a time‐calibrated phylogenetic tree including 79 species. We estimated the patterns of floral traits (flowering time and floral size) evolution using macroevolutionary modelling, and tested the correlation of speciation rate with the trait evolution rates. Finally, we estimated the isolation factors of all taxa pairs and sister‐taxa pairs based on distribution range and floral traits. Results Phylogenetic analysis indicated that Heterotropa was diverged into two clades (continental clade and insular clade) in the Miocene, and the major subclades corresponded to geographic entities. Most rate shifts accelerating floral trait's evolution occurred during the Pleistocene period. Evolution rate of floral traits showed positive correlation with the speciation rate. Large proportion of taxa in the insular clade are distributed allopatrically. Several sister pairs showed floral trait divergence with geographic overlap. Main Conclusions The diversification of Heterotropa appears to have been triggered by geographic and climatic events, and subsequent repeated floral trait evolution with and without geographic isolation. Furthermore, the high species diversity in the insular systems would have been formed by the repeated range fragmentations and contractions. Our study demonstrates the importance of multidimensional studies to understand the diversification process of temperate plants in the Sino‐Japanese Floristic Region.

A dye combination for the staining of pollen coat and pollen wall - Xin-Lei Jia; Jing-Shi Xue; Fang Zhang; Chi Yao; Shi-Yi Shen; Chang-Xu Sui; Yu-Jia Peng; Qin-Lin Xu; Yi-Feng Feng; Wen-Jing Hu; Ping Xu; Zhong-Nan Yang (Plant Reproduction, 2021)

Influence of different fluidization and gasification parameters on syngas composition and heavy metal retention in a two-stage fluidized bed gasification process - Jia-Hong Kuo; Chiou-Liang Lin; Chang-Yu Ho; Jia-Chi Hung (Environmental Science and Pollution Research, 2021)

Effects of plant growth regulators and polyamines on bract longevity in Bougainvillea buttiana - Kuan-Hung Lin; Jui-Mei Li; Chun-Wei Wu; Yu-Sen Chang (Horticulture, Environment, and Biotechnology, 2021)

New secondary metabolite with cytotoxicity from spawning soft coral Asterospicularia laurae in Taiwan - Jui-Hsin Su; Chih-I Liu; Mei-Chin Lu; Chi-I Chang; Min-Ying Hsieh; Yu-Chi Lin; Chang-Feng Dai; Ya-Han Zhang; Zheng-Yu Lin; Yun-Sheng Lin (Natural Product Research, 2021)

Shallow gas hydrates off southwest Taiwan and their mechanisms - Yin-Sheng Huang; Shu-Kun Hsu; Chih-Chieh Su; Andrew Tien-Shun Lin; Pai-Sen Yu; Nathalie Babonneau; Gueorgui Ratzov; Serge Lallemand; Pi-Chuen Huang; Shiao-Shan Lin; Jing-Yi Lin; Kuo-Yen Wei; et al. (Marine Geophysical Research, 2021)
We have collected two shallow gas hydrate samples at two sites having different geological settings off southwest Taiwan during the cruise MD214 in 2018. The first core site, MD18-3542, is on the South Yuan-An East Ridge at ~ 1200 m water deep, where a structural unconformity covered by fine-silt sediments appears at ~ 5.5 m below the seafloor. The second core site, MD18-3543, is close to the Good-Weather Ridge at ~ 1100 m water deep, where a gas-related pockmark structure and authigenic carbonates are present at shallow strata with fine-silt sediments near the seafloor. Sediment properties of core MD18-3542 are distinctively different above and below the layer corresponding to the unconformity. Both cores show obvious gaps or voids in the lower core halves. The core features could be linked to the dissociated methane upward migrating from deep strata. Core site settings with upwelling methane would favor the formation of shallow gas hydrates. At site MD18-3542, the shallow hydrate could be formed due to high concentration methane kept beneath the unconformity covered by fine-silt sediments. At site MD18-3543, the shallow hydrate could be formed due to an extremely high flux of upwelling methane trapped either beneath the authigenic carbonates or fine-silt sediments.

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

Projections from Infralimbic Cortex to Paraventricular Thalamus Mediate Fear Extinction Retrieval - Yan Tao; Cheng-Yun Cai; Jia-Yun Xian; Xiao-Lin Kou; Yu-Hui Lin; Cheng Qin; Hai-Yin Wu; Lei Chang; Chun-Xia Luo; Dong-Ya Zhu (Neuroscience Bulletin, 2021)

Dapagliflozin suppresses ER stress and protects doxorubicin-induced cardiotoxicity in breast cancer patients - Wei-Ting Chang; Yu-Wen Lin; Chung-Han Ho; Zhih-Cherng Chen; Ping-Yen Liu; Jhih-Yuan Shih (Archives of Toxicology, 2021)

Concurrent increases in post-pacing action potential duration and contractility predict occurrence of ventricular arrhythmia - Chih-Min Liu; Feng-Zhi Lin; Yao-Chang Chen; Yung-Kuo Lin; Yen-Yu Lu; Cheng-I Wu; Satoshi Higa; Shih-Ann Chen; Yi-Jen Chen (Pflügers Archiv - European Journal of Physiology, 2020)

Unraveling neuroHIV in the Presence of Substance Use Disorders - Yu Lin; Johnny J. He; Roger Sorensen; Linda Chang (Journal of Neuroimmune Pharmacology, 2020)

Improving Image Correlation and Differentiation of 3D Endoluminal Lesions in the Air Spaces Using a Novel Target Gray Level Mapping Technique: A Preliminary Study of Its Application to Computed Tomographic Colonography and Comparison with Traditional Surface Rendering Method - Lih-Shyang Chen; Ta-Wen Hsu; Shao-Jer Chen; Shu-Han Chang; Chih-Wen Lin; Yu-Ruei Chen; Chin-Chiang Hsieh; Shu-Chen Han; Ku-Yaw Chang; Chun-Ju Hou (Journal of Medical and Biological Engineering, 2020)

Correction to: 4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay‑Huyen Chen; Ping‑Chen Shih; Han‑Yu Lin; Po‑Kai Wang; Po‑Ting Pan; Ching‑Wei Chuang; Ming‑Chang Kao (Inflammopharmacology, 2020)

Boys with autism spectrum disorder have distinct cortical folding patterns underpinning impaired self-regulation: a surface-based morphometry study - Hsing-Chang Ni; Hsiang-Yuan Lin; Yu-Chieh Chen; Wen-Yih Isaac Tseng; Susan Shur-Fen Gau (Brain Imaging and Behavior, 2020)

Overexpression of a multifunctional β-glucosidase gene from thermophilic archaeon Sulfolobus solfataricus in transgenic tobacco could facilitate glucose release and its use as a reporter - Chih-Hao Huang; Tzu-Ling Huang; Yu-Chang Liu; Ting-Chieh Chen; Shih-Ming Lin; Shyh-Yu Shaw; Ching-Chun Chang (Transgenic Research, 2020)

Optimizing the MIC breakpoints of amoxicillin and tetracycline for antibiotic selection in the rescue therapy of H. pylori with bismuth quadruple regimen - Ming-Tsung Hsieh; Wei-Lun Chang; Chung-Tai Wu; Hsiao-Bai Yang; Hsin-Yu Kuo; Meng-Ying Lin; Hsiu-Chi Cheng; Yu-Chin Tsai; Bor-Shyang Sheu (European Journal of Clinical Pharmacology, 2020)

Erratum to: An Examination of the Predictability of Tropical Cyclone Genesis in High-Resolution Coupled Models with Dynamically Downscaled Coupled Data Assimilation Initialization - Mingkui Li; Shaoqing Zhang; Lixin Wu; Xiaopei Lin; Ping Chang; Gohkan Danabasoglu; Zhiqiang Wei; Xiaolin Yu; Huiqin Hu; Xiaohui Ma; Weiwei Ma; Haoran Zhao; et al. (Advances in Atmospheric Sciences, 2020)

A new macrocyclic diterpenoid from Anisomeles indica - Chen-Liang Chao; Hui-Chi Huang; Hsiou-Yu Ding; Jenn-Haung Lai; Hang-Ching Lin; Wen-Liang Chang (Natural Product Research, 2020)

Infusion of Human Mesenchymal Stem Cells Improves Regenerative Niche in Thioacetamide-Injured Mouse Liver - Ying-Hsien Kao; Yu-Chun Lin; Po-Huang Lee; Chia-Wei Lin; Po-Han Chen; Tzong-Shyuan Tai; Yo-Chen Chang; Ming-Huei Chou; Chih-Yang Chang; Cheuk-Kwan Sun (Tissue Engineering and Regenerative Medicine, 2020)

Matriptase and prostasin proteolytic activities are differentially regulated in normal and wounded skin - Shun-Cheng Chang; Chien-Ping Chiang; Chih-Hsin Lai; Po-Wen A. Du; Yu-Sin Hung; Yu-Hsuan Chen; Hui-Yu Yang; Hao-Yu Fang; Shiao-Pieng Lee; Hung-Jen Tang; Jehng-Kang Wang; Michael D. Johnson; et al. (Human Cell, 2020)

Complete Genome of Vibrio neocaledonicus CGJ02-2, An active Compounds Producing Bacterium Isolated from South China Sea - Lin Tan; Isabel Gómez-Betancur; Suxia Guo; Yu Ge; Jianping Zhao; Chang Chen; Nan Wang (Current Microbiology, 2020)

Roles of MicroRNA-122 in Cardiovascular Fibrosis and Related Diseases - Ying Liu; Jia-Wei Song; Jian-Yu Lin; Ran Miao; Jiu-Chang Zhong (Cardiovascular Toxicology, 2020)

On the mechanism of soft clay being improved entirely in the ECT treatment - Chang-Yu Ou; Chien-Yu Lin; Shao-Chi Chien (Bulletin of Engineering Geology and the Environment, 2020)

An Examination of the Predictability of Tropical Cyclone Genesis in High-Resolution Coupled Models with Dynamically Downscaled Coupled Data Assimilation Initialization - Mingkui Li; Shaoqing Zhang; Lixin Wu; Xiaopei Lin; Ping Chang; Gohkan Danabasoglu; Zhiqiang Wei; Xiaolin Yu; Huiqin Hu; Xiaohui Ma; Weiwei Ma; Haoran Zhao; et al. (Advances in Atmospheric Sciences, 2020)

Four new species of Phylloporia (Hymenochaetales, Basidiomycota) from southeastern Taiwan - Sheng-Hua Wu; Chiung-Chih Chang; Chia-Ling Wei; Yu-Ting Lin; Siou-Zhen Chen (Mycological Progress, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

Hispidulin Inhibits Neuroinflammation in Lipopolysaccharide-Activated BV2 Microglia and Attenuates the Activation of Akt, NF-κB, and STAT3 Pathway - Chung-I Yu; Cheng-I Cheng; Ya-Fei Kang; Po-Chih Chang; In-Pin Lin; Yu-His Kuo; An-Jie Jhou; Mei-Ying Lin; Chung-Yi Chen; Chien-Hsing Lee (Neurotoxicity Research, 2020)

The interaction between dietary marine components and intestinal flora - Lin Li; Chang-Hu Xue; Tian-Tian Zhang; Yu-Ming Wang (Marine Life Science & Technology, 2020)

Prior Antiplatelet Therapy, Excluding Phosphodiesterase Inhibitor Is Associated with Poor Outcome in Patients with Spontaneous Intracerebral Haemorrhage - Zhuo-Hao Liu; Chi-Hung Liu; Po-Hsun Tu; Ping K. Yip; Ching-Chang Chen; Yu-Chi Wang; Nan-Yu Chen; Yu-Sheng Lin (Translational Stroke Research, 2020)

Novel dammarane-type saponins from Gynostemma pentaphyllum and their neuroprotective effect - Shao-Fang Xing; Man Lin; Yu-Rong Wang; Tuo Chang; Wei-Ye Cui; Xiang-Lan Piao (Natural Product Research, 2020)

An alternative splicing variant of mineralocorticoid receptor discovered in preeclampsia tissues and its effect on endothelial dysfunction - Mengxi Guo; Chengliang Zhou; Gufeng Xu; Lin Tang; Yechun Ruan; Ying Yu; Xianhua Lin; Dandan Wu; Hao Chen; Priscilla Yu; Luyang Jin; Yinyu Wang; et al. (Science China Life Sciences, 2020)

Therapeutic Efficacy of Subcutaneous and Intraperitoneal Injections of a Single Dose of Human Umbilical Mesenchymal Stem Cells in Acute and Chronic Colitis in a Mouse Model - Yu-Lung Chang; Huei-Yu Lo; Shun-Ping Cheng; Kuo-Ting Chang; Xiu-Fang Lin; Sheng-Ping Lee; Jason Ma; Ming-Ling Kuo; Ming-Fa Hsieh; Chin-Kan Chan (Journal of Medical and Biological Engineering, 2020)

Chronic ketamine abuse is associated with orexin-A reduction and ACTH elevation - Ming-Chyi Huang; Chun-Hsin Chen; Lian-Yu Chen; Hu-Ming Chang; Chih-Ken Chen; Shih-Ku Lin; Ke Xu (Psychopharmacology, 2020)

Gallic Acid Attenuated LPS-Induced Neuroinflammation: Protein Aggregation and Necroptosis - Yu-Ling Liu; Chia-Chi Hsu; Hui-Ju Huang; Chih-Jung Chang; Shu-Hui Sun; Anya Maan-Yuh Lin (Molecular Neurobiology, 2020)

Correction to: Soluble Epoxide Hydrolase Inhibition Attenuates Excitotoxicity Involving 14,15-Epoxyeicosatrienoic Acid–Mediated Astrocytic Survival and Plasticity to Preserve Glutamate Homeostasis - Yi-Min Kuo; Pei-Chien Hsu; Chia-Chi Hung; Ya-Yu Hu; Yu-Jie Huang; Yu-Ling Gan; Chun-Hua Lin; Feng-Shiun Shie; Wen-Kuei Chang; Lung-Sen Kao; Mei-Yung Tsou; Yi-Hsuan Lee (Molecular Neurobiology, 2019)

Soluble Epoxide Hydrolase Inhibition Attenuates Excitotoxicity Involving 14,15-Epoxyeicosatrienoic Acid–Mediated Astrocytic Survival and Plasticity to Preserve Glutamate Homeostasis - Yi-Min Kuo; Pei-Chien Hsu; Chia-Chi Hung; Ya-Yu Hu; Yu-Jie Huang; Yu-Ling Gan; Chun-Hua Lin; Feng-Shiun Shie; Wen-Kuei Chang; Lung-Sen Kao; Mei-Yung Tsou; Yi-Hsuan Lee (Molecular Neurobiology, 2019)

Mutational signatures and mutagenic impacts associated with betel quid chewing in oral squamous cell carcinoma - Shih-Chi Su; Lun-Ching Chang; Chiao-Wen Lin; Mu-Kuan Chen; Chun-Ping Yu; Wen-Hung Chung; Shun-Fa Yang (Human Genetics, 2019)

Forecasts of MJO Events during DYNAMO with a Coupled Atmosphere-Ocean Model: Sensitivity to Cumulus Parameterization Scheme - Mei-Yu Chang; Tim Li; Pay-Liam Lin; Ting-Huai Chang (Journal of Meteorological Research, 2019)

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

Indication of dynamic neurovascular coupling from inconsistency between EEG and fMRI indices across sleep–wake states - Changwei W. Wu; Pei-Jung Tsai; Sharon Chia-Ju Chen; Chia-Wei Li; Ai-Ling Hsu; Hong-Yi Wu; Yu-Ting Ko; Pai-Chuan Hung; Chun-Yen Chang; Ching-Po Lin; Timothy J. Lane; Chia-Yuen Chen (Sleep and Biological Rhythms, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Development of Multi-axis Motor Control Systems for Lower Limb Robotic Exoskeleton - Cheng-Tang Pan; Chun-Chieh Chang; Pei-Yuan Sun; Cheng-Lung Lee; Tzu-Chieh Lin; Chung-Kun Yen; Yu-Sheng Yang (Journal of Medical and Biological Engineering, 2019)

Isolation of a New PAK1 Gene from Sea Cucumber (Apostichopus japonicus) and Its Expression Analysis and Function Characterization - Liyuan Ren; Kaiquan Li; Yaoyao Zhan; Yi Wang; Yao Yu; Yang Chen; Kai Lin; Jian Song; Yaqing Chang (Journal of Ocean University of China, 2019)

Real-Time Water-Level Forecasting Using Dilated Causal Convolutional Neural Networks - Jhih-Huang Wang; Gwo-Fong Lin; Ming-Jui Chang; I-Hang Huang; Yu-Ren Chen (Water Resources Management, 2019)

4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay-Huyen Chen; Ping-Chen Shih; Han-Yu Lin; Po-Kai Wang; Po-Ting Pan; Ching-Wei Chuang; Ming-Chang Kao (Inflammopharmacology, 2019)

Permanent displacement models of earthquake-induced landslides considering near-fault pulse-like ground motions - Ying-bin Zhang; Chen-lin Xiang; Yan-long Chen; Qian-gong Cheng; Li Xiao; Peng-cheng Yu; Zhi-wang Chang (Journal of Mountain Science, 2019)

The roles of morphological traits, resource variation and resource partitioning associated with the dietary niche expansion in the fish‐eating bat Myotis pilosus - Yang Chang; Shengjing Song; Aoqiang Li; Yu Zhang; Zhongle Li; Yanhong Xiao; Tinglei Jiang; Jiang Feng; Aiqing Lin (Molecular Ecology, 2019)
Niche expansion and shifts are involved in the response and adaptation to environmental changes. However, it is unclear how niche breadth evolves and changes toward higher‐quality resources. Myotis pilosus is both an insectivore and a piscivore. We examined the dietary composition and seasonality in M . pilosus and the closely related Myotis fimbriatus using next‐generation DNA sequencing. We tested whether resource variation or resource partitioning help explain the dietary expansion from insects to fish in M . pilosus . While diet composition and diversity varied significantly between summer and autumn, the proportion of fish‐eating individuals did not significantly change between seasons in M . pilosus . Dietary overlap between M . pilosus and M . fimbriatus during the same seasons was much higher than within individual species across seasons. We recorded a larger body size, hind foot length, and body mass in M . pilosus than in M . fimbriatus and other insectivorous trawling bats from China. Similar morphological differences were found between worldwide fishing bats and nonfishing trawling bats. Our results suggest that variation in insect availability or interspecific competition may not play important roles in the dietary expansion from insects to fish in M . pilosus . Myotis pilosus has morphological advantages that may help it use fish as a diet component. The morphological advantage promoting dietary niche evolution toward higher quality resources may be more important than variation in the original resource and the effects of interspecific competition.

Dynamic changes in lakes in the Hoh Xil region before and after the 2011 outburst of Zonag Lake - Wen-hui Liu; Chang-wei Xie; Lin Zhao; Tong-hua Wu; Wu Wang; Yu-xin Zhang; Gui-qian Yang; Xiao-fan Zhu; Guang-yang Yue (Journal of Mountain Science, 2019)

Magnesium sulfate inhibits binding of lipopolysaccharide to THP-1 cells by reducing expression of cluster of differentiation 14 - Ya-Ying Chang; Tzu-Yu Lin; Ming-Chang Kao; Tsung-Ying Chen; Ching-Feng Cheng; Chih-Shung Wong; Chun-Jen Huang (Inflammopharmacology, 2019)

Correction to: Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2019)

Analysis of Electroencephalography Event-Related Desynchronisation and Synchronisation Induced by Lower-Limb Stepping Motor Imagery - Yi-Hung Liu; Li-Fong Lin; Chun-Wei Chou; Yun Chang; Yu-Tsung Hsiao; Wei-Chun Hsu (Journal of Medical and Biological Engineering, 2019)

Inhibition of macrophage inflammatory protein-1β improves endothelial progenitor cell function and ischemia-induced angiogenesis in diabetes - Ting-Ting Chang; Liang-Yu Lin; Jaw-Wen Chen (Angiogenesis, 2019)

The analgesic effect and possible mechanisms by which koumine alters type II collagen-induced arthritis in rats - Gui-Lin Jin; Jian Yang; Wan-Qing Chen; Jie Wang; Hong-Qiang Qiu; Ying Xu; Chang-Xi Yu (Journal of Natural Medicines, 2019)

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease - Chia-Chia Lee; Ching-Pang Chang; Chun-Jung Lin; Hsing-Lin Lai; Yu-Han Kao; Sin-Jhong Cheng; Hui-Mei Chen; Yu-Ping Liao; Emilie Faivre; Luc Buée; David Blum; Jim-Min Fang; et al. (Molecular Neurobiology, 2018)

Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2018)

Tissue Section Image-Based Liver Scar Detection - Yung-Kuan Chan; Ming-Jen Chang; Yi-Wen Hung; Ching-Lin Wang; Chun-Fu Hong; Kwong-Chung Tung; Shyr Shen Yu (Journal of Medical and Biological Engineering, 2018)

Exercise Rehabilitation Attenuates Cognitive Deficits in Rats with Traumatic Brain Injury by Stimulating the Cerebral HSP20/BDNF/TrkB Signalling Axis - Willy Chou; Yu-Fan Liu; Cheng-Hsien Lin; Mao-Tsun Lin; Chi-Chun Chen; Wen-Pin Liu; Ching-Ping Chang; Chung-Ching Chio (Molecular Neurobiology, 2018)

Detection, sequence analysis, and antibody prevalence of porcine deltacoronavirus in Taiwan - Tien-Huan Hsu; Hao-Ping Liu; Chieh-Yu Chin; Chinling Wang; Wan-Zhen Zhu; Bing-Lin Wu; Yu-Chung Chang (Archives of Virology, 2018)

Regulatory Effects of Neuroinflammatory Responses Through Brain-Derived Neurotrophic Factor Signaling in Microglial Cells - Sheng-Wei Lai; Jia-Hong Chen; Hsiao-Yun Lin; Yu-Shu Liu; Cheng-Fang Tsai; Pei-Chun Chang; Dah-Yuu Lu; Chingju Lin (Molecular Neurobiology, 2018)

Clinical and microbiological characteristics of peritoneal dialysis-related peritonitis caused by Escherichia coli in southern Taiwan - Wei-Hung Lin; Chin-Chung Tseng; An-Bang Wu; Yu-Tzu Chang; Te-Hui Kuo; Jo-Yen Chao; Ming-Cheng Wang; Jiunn-Jong Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Yak and Tibetan sheep trampling inhibit reproductive and photosynthetic traits of Medicago ruthenica var. inschanica - Hong Xiao; Zhen Peng; Chang Lin Xu; De Gang Zhang; Jin Long Chai; Tao Tao Pan; Xiao Jun Yu (Environmental Monitoring and Assessment, 2018)

The complete mitogenome of the winged argonaut Argonauta hians and its phylogenetic relationships in Octopoda - Yu-Wen Chiu; Chih-Wei Chang; Hung-Du Lin; Kang-Ning Shen (Conservation Genetics Resources, 2018)

Studies on the Development of Small Abalone ( Haliotis diversicolor supertexta ) Essence and its Antioxidative Properties - Yu-Wei Chang; Chun-Che Lin; Wen-Chieh Sung (Journal of Aquatic Food Product Technology, 2018)

A new antiviral pregnane from a gorgonian-derived Cladosporium sp. fungus - Mei-Lin Yu; Fei-Fei Guan; Fei Cao; Yan-Lai Jia; Chang-Yun Wang (Natural Product Research, 2018)

Impact of mixed anthropogenic and natural emissions on air quality and eco-environment—the major water-soluble components in aerosols from northwest to offshore isle - Yilun Jiang; Guoshun Zhuang; Qiongzhen Wang; Kan Huang; Congrui Deng; Guangyuan Yu; Chang Xu; Qingyan Fu; Yanfen Lin; Joshua S. Fu; Mei Li; Zhen Zhou (Air Quality, Atmosphere & Health, 2018)

A Quninolylthiazole Derivatives as an ICT-Based Fluorescent Probe of Hg(II) and its Application in Ratiometric Imaging in Live HeLa Cells - Jian-Ying Bai; Yu-Zhong Xie; Chang-Jiang Wang; Shu-Qing Fang; Lin-Nan Cao; Ling-Li Wang; Jing-Yi Jin (Journal of Fluorescence, 2018)

Converting natural evergreen broadleaf forests to intensively managed moso bamboo plantations affects the pool size and stability of soil organic carbon and enzyme activities - Ziwen Lin; Yongfu Li; Caixian Tang; Yu Luo; Weijun Fu; Xiaoqing Cai; Yongchun Li; Tian Yue; Peikun Jiang; Shuaidong Hu; Scott X. Chang (Biology and Fertility of Soils, 2018)

Treatment outcome of non-carbapenemase-producing carbapenem-resistant Klebsiella pneumoniae infections: a multicenter study in Taiwan - Chin-Fang Su; Chien Chuang; Yi-Tsung Lin; Yu-Jiun Chan; Jung-Chung Lin; Po-Liang Lu; Ching-Tai Huang; Jann-Tay Wang; Yin-Ching Chuang; L. Kristopher Siu; Chang-Phone Fung (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Dose Verification for Tumor Motion with Different Treatment Planning Systems: A Dynamic Thorax Phantom Study - Shih-Neng Yang; Chun-Wei Lin; Mu-Bai Chang; Geoffrey G. Zhang; Kuei-Ting Chou; Yu-Rou Chiou; Shung-Shung Sun; Louis Lui; Tsung-Jung Ho; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

Prevalence, mechanisms and genetic relatedness of the human pathogenic fungus Aspergillus fumigatus exhibiting resistance to medical azoles in the environment of Taiwan - Hsuan‐Chen Wang; Jui‐Chang Huang; Yong‐Hong Lin; Yu‐Hsin Chen; Ming‐I Hsieh; Pui‐Ching Choi; Hsiu‐Jung Lo; Wei‐Lun Liu; Ching‐Shan Hsu; Hsin‐I Shih; Chi‐Jung Wu; Yee‐Chun Chen (Environmental Microbiology, 2018)
Summary Emerging azole resistance in Aspergillus fumigatus poses a serious threat to human health. This nationwide surveillance study investigated the prevalence and molecular characteristics of azole‐resistant A. fumigatus environmental isolates in Taiwan, an island country with increasing use of azole fungicides. Of the 2760 air and soil samples screened from 2014 to 2016, 451 A. fumigatus isolates were recovered from 266 samples and 34 isolates from 29 samples displayed resistance to medical azoles (itraconazole, voriconazole or posaconazole). The resistance prevalence was 10.9% and 7.5% in A. fumigatus ‐positive samples and isolates respectively. Most (29, 85.3%) azole‐resistant isolates harboured TR 34 /L98H mutations, which were widely distributed, clustered genetically with clinical isolates, and had growth rates that were similar to those of the wild‐type isolates. Microsatellite genotyping revealed both the global spread of the TR 34 /L98H isolates and the occurrence of TR 34 /L98H/S297T/F495I isolates belonging to local microsatellite genotypes. AfuMDR3 and atrF , two efflux transporter genes, were constitutively upregulated in two individual resistant isolates without cyp51A mutations, highlighting their potential roles in azole resistance. These results emphasize the need for periodic environmental surveillance at the molecular level in regions in which azole fungicides are applied, and agricultural fungicide management strategies that generate less selective pressure should be investigated.

Mapping and comparative proteomic analysis of the starch biosynthetic pathway in rice by 2D PAGE/MS - Tao-Shan Chang; Chih-Wei Liu; Yu-Ling Lin; Chao-Yi Li; Arthur Z. Wang; Min-Wei Chien; Chang-Sheng Wang; Chien-Chen Lai (Plant Molecular Biology, 2017)

Comparative and population genomic landscape of Phellinus noxius : A hypervariable fungus causing root rot in trees - Chia‐Lin Chung; Tracy J. Lee; Mitsuteru Akiba; Hsin‐Han Lee; Tzu‐Hao Kuo; Dang Liu; Huei‐Mien Ke; Toshiro Yokoi; Marylette B. Roa; Mei‐Yeh J. Lu; Ya‐Yun Chang; Pao‐Jen Ann; et al. (Molecular Ecology, 2017)
The order Hymenochaetales of white rot fungi contain some of the most aggressive wood decayers causing tree deaths around the world. Despite their ecological importance and the impact of diseases they cause, little is known about the evolution and transmission patterns of these pathogens. Here, we sequenced and undertook comparative genomic analyses of Hymenochaetales genomes using brown root rot fungus Phellinus noxius , wood‐decomposing fungus Phellinus lamaensis, laminated root rot fungus Phellinus sulphurascens and trunk pathogen Porodaedalea pini . Many gene families of lignin‐degrading enzymes were identified from these fungi, reflecting their ability as white rot fungi. Comparing against distant fungi highlighted the expansion of 1,3‐beta‐glucan synthases in P. noxius , which may account for its fast‐growing attribute. We identified 13 linkage groups conserved within Agaricomycetes, suggesting the evolution of stable karyotypes. We determined that P. noxius has a bipolar heterothallic mating system, with unusual highly expanded ~60 kb A locus as a result of accumulating gene transposition. We investigated the population genomics of 60 P. noxius isolates across multiple islands of the Asia Pacific region. Whole‐genome sequencing showed this multinucleate species contains abundant poly‐allelic single nucleotide polymorphisms with atypical allele frequencies. Different patterns of intra‐isolate polymorphism reflect mono‐/heterokaryotic states which are both prevalent in nature. We have shown two genetically separated lineages with one spanning across many islands despite the geographical barriers. Both populations possess extraordinary genetic diversity and show contrasting evolutionary scenarios. These results provide a framework to further investigate the genetic basis underlying the fitness and virulence of white rot fungi.

Two reported cytotypes of the emergent orchid model species Erycina pusilla are two different species - Hsuan-Yu Yeh; Choun-Sea Lin; Hans de Jong; Song-Bin Chang (Euphytica, 2017)
Each species is characterized by a specific set of chromosomes, which is described as the chromosome portrait or karyotype. In general, such a karyotype is the same for all individuals in the population. An exception to that rule has recently been found in the orchid Erycina pusilla , which has been reported to have two cytotypes with chromosome numbers of 2n = 10 and 2n = 12. Here, we examined the karyotypes of the two cytotypes and found differences in arm ratios and heterochromatin patterns as well as in the presence of satellite chromosomes and in the number and location of rDNA and telomeric repeat sites. These differences are extensive and would have required multiple chromosome rearrangements to generate the differences between the two karyotypes. We also found that F1 hybrids between the parents with the two different chromosome numbers resulted in sterile offspring, in accordance with our previous findings. The combination of hybrid sterility and extensively rearranged chromosomes supports the hypothesis that these two reported cytotypes are, in fact, two different species.

Groundwater origins and recharge in a well field near Chien-Shih, Shinchu, Taiwan - Pei-Ying Lin; Louis Loung-Yie Tsai; Chung-Ho Wang; Kuei-Wen Chang; Yu-Yen Sheng; I-Tzu Chu; Wang-Ru Lee (Sustainable Water Resources Management, 2017)

IL-28 and IL-29 as protective markers in subject with dengue fever - Chih-Hsing Hung; Chung-Hao Huang; Lin Wang; Chun-Chi Huang; Meng-Chieh Wu; Yi-Ying Chin; Chun-Yu Lin; Ko Chang; Deng-Chyang Wu; Yen-Hsu Chen (Medical Microbiology and Immunology, 2017)

HCV core inhibits hepatocellular carcinoma cell replicative senescence through downregulating microRNA-138 expression - Tzu-Yue Shiu; Yu-Lueng Shih; An-Chieh Feng; Hsuan-Hwai Lin; Shih-Ming Huang; Tien-Yu Huang; Chung-Bao Hsieh; Wei-Kuo Chang; Tsai-Yuan Hsieh (Journal of Molecular Medicine, 2017)

p-Hydroxyacetophenone suppresses nuclear factor-κB-related inflammation in nociceptive and inflammatory animal models - Chang Ching-Wen; Chen Yun-Chieh; Lin Yu-Chin; Peng Wen-Huang (Journal of Natural Medicines, 2017)

Static Magnetic Field Increases Survival Rate of Thawed RBCs Frozen in DMSO-Free Solution - Yi-June Lo; Yu-Hwa Pan; Chun-Yen Lin; Wei-Jen Chang; Haw-Ming Huang (Journal of Medical and Biological Engineering, 2017)

Therapeutic potential of pro-angiogenic BPC157 is associated with VEGFR2 activation and up-regulation - Ming-Jer Hsieh; Hsien-Ta Liu; Chao-Nin Wang; Hsiu-Yun Huang; Yuling Lin; Yu-Shien Ko; Jong-Shyan Wang; Vincent Hung-Shu Chang; Jong-Hwei S. Pang (Journal of Molecular Medicine, 2017)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

Microseismic Precursory Characteristics of Rock Burst Hazard in Mining Areas Near a Large Residual Coal Pillar: A Case Study from Xuzhuang Coal Mine, Xuzhou, China - An-ye Cao; Lin-ming Dou; Chang-bin Wang; Xiao-xiao Yao; Jing-yuan Dong; Yu Gu (Rock Mechanics and Rock Engineering, 2016)

A WD40 protein, AtGHS40, negatively modulates abscisic acid degrading and signaling genes during seedling growth under high glucose conditions - Yu-Chun Hsiao; Yi-Feng Hsu; Yun-Chu Chen; Yi-Lin Chang; Co-Shine Wang (Journal of Plant Research, 2016)

Goatpoxvirus ATPase activity is increased by dsDNA and decreased by zinc ion - Ming-Liang Lee; Wei-Li Hsu; Chi-Young Wang; Hui-Yu Chen; Fong-Yuan Lin; Ming-Huang Chang; Hong-You Chang; Min-Liang Wong; Kun-Wei Chan (Virus Genes, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Two AMT2-Type Ammonium Transporters from Pyrus betulaefolia Demonstrate Distinct Expression Characteristics - Hui Li; Yu Cong; You-hong Chang; Jing Lin (Plant Molecular Biology Reporter, 2016)

Leifiporia rhizomorpha gen. et sp. nov. and L. eucalypti comb. nov. in Polyporaceae (Basidiomycota) - Chang-Lin Zhao; Fang Wu; Yu-Cheng Dai (Mycological Progress, 2016)

Curcumin downregulates p38 MAPK-dependent X-ray repair cross-complement group 1 (XRCC1) expression to enhance cisplatin-induced cytotoxicity in human lung cancer cells - Chun-Liang Tung; Yi-Jun Jian; Jyh-Cheng Chen; Tai-Jing Wang; Wen-Ching Chen; Hao-Yu Zheng; Po-Yuan Chang; Kai-Sheng Liao; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Resistance to viral yellow leaf curl in tomato through RNAi targeting two Begomovirus species strains - Huei-mei Chen; Chen-yu Lin; Wen-shi Tsai; Lawrence Kenyon; Ming-tsair Chan; Jo-yi Yen; Shao-yu Chang; Robert de la Peña; Roland Schafleitner (Journal of Plant Biochemistry and Biotechnology, 2016)

Development of Home-Based Frailty Detection Device Using Wireless Sensor Networks - Chung-Chih Lin; Chun-Chang Chen; Pay-Shin Lin; Ren-Guey Lee; Jing-Siang Huang; Tsai-Hsuan Tsai; Yu-Chuan Chang (Journal of Medical and Biological Engineering, 2016)

Transcriptional and posttranscriptional regulation of CXCL8/IL-8 gene expression induced by connective tissue growth factor - Chien-Huang Lin; Yuan-Hung Wang; Yu-Wen Chen; Yu-Liang Lin; Bing-Chang Chen; Mei-Chieh Chen (Immunologic Research, 2016)

Naringenin Suppresses Neuroinflammatory Responses Through Inducing Suppressor of Cytokine Signaling 3 Expression - Ling-Hsuan Wu; Chingju Lin; Hsiao-Yun Lin; Yu-Shu Liu; Caren Yu-Ju Wu; Cheng-Fang Tsai; Pei-Chun Chang; Wei-Lan Yeh; Dah-Yuu Lu (Molecular Neurobiology, 2016)

Quantitative measurement of Parkinsonian gait from walking in monocular image sequences using a centroid tracking algorithm - Sheng-Huang Lin; Shih-Wei Chen; Yu-Chun Lo; Hsin-Yi Lai; Chich-Haung Yang; Shin-Yuan Chen; Yuan-Jen Chang; Chin-Hsing Chen; Wen-Tzeng Huang; Fu-Shan Jaw; You-Yin Chen; Siny Tsang; et al. (Medical & Biological Engineering & Computing, 2016)

Canonical and non-canonical Wnt signaling control the regeneration of amputated rodent vibrissae follicles - Yan-Ping Yuan; Keng Huang; Yan-Min Xu; Xian-Cai Chen; Hai-Hong Li; Bo-Zhi Cai; Yang Liu; Huan Zhang; Yu Li; Chang-Min Lin (Journal of Molecular Histology, 2016)

Clinical Pedicle Screw Insertion Trials and System Improvement of C-arm Image Navigation System - Chih-Ju Chang; Ching-Hsiao Yu; Geng-Li Lin; Alex Tse; Hong-Yu Chu; Ching-Shiow Tseng (Journal of Medical and Biological Engineering, 2016)

Isolation, complete genome sequencing, and phylogenetic analysis of the first Chuzan virus in China - Fang Wang; Jun Lin; Jitao Chang; Yingying Cao; Shaomin Qin; Jianmin Wu; Li Yu (Virus Genes, 2016)

Groundwater Molybdenum from Emerging Industries in Taiwan - Kuo-Sheng Tsai; Yu-Min Chang; Jimmy C. M. Kao; Kae-Long Lin (Bulletin of Environmental Contamination and Toxicology, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

Roles of microRNA-1 in hypoxia-induced apoptotic insults to neuronal cells - Chia-Yu Chang; Tai-Ngar Lui; Jia-Wei Lin; Yi-Ling Lin; Chung-Hsi Hsing; Jhi-Joung Wang; Ruei-Ming Chen (Archives of Toxicology, 2016)

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

Erratum to: The collective nuclear migration of p53 and phosphorylated S473 of Akt during ellipticine-mediated apoptosis in human lung epithelial cancer cells - Jing-Ping Wang; Ya-Chu Yu; Shih-Ping Chen; Huan-Chang Liang; Chia-Wei Lin; Kang Fang (Molecular and Cellular Biochemistry, 2015)

Cytogenetic and cytometric analyses in artificial intercytotypic hybrids of the emergent orchid model species Erycina pusilla - Hsuan-Yu Yeh; Choun-Sea Lin; Song-Bin Chang (Euphytica, 2015)
Erycina pusilla is considered a potential model organism for orchids, because of several advantageous features, such as short juvenile period, low chromosome number and all year round blooming. Two different chromosome numbers (2n = 10 and 2n = 12) are reported for E. pusilla , which suggests two cytotypes. To reveal the genome homology between these two cytotypes, we generated hybrids from the intercytotypic reciprocal crosses (2n = 10 × 2n = 12 and 2n = 12 × 2n = 10), and applied 4′,6-diamidino-2-phenylindole staining, genomic in situ hybridization and flow cytometry for genomic and cytogenetic analysis. The parental genomes showed high similarity both in genomic composition and content. The hybrids displayed a chromosome number of 2n = 11 in mitotic cells. Moreover, five bivalents and one univalent were observed at meiotic metaphase I stage. We observed meiotic synaptic behavior and found homeologous pairing with unpaired loops between parental chromosome pairing segments. These results demonstrated that chromosome rearrangement events have occurred between parental cytotypes during evolution. This study also illustrated the genome homology and homeologous pairing at pachytene phase, indicating that the chromosome number variation of two cytotypes mainly resulted from chromosome rearrangements, not changes in genomic constitution.

A space-time typhoon trajectories analysis in the vicinity of Taiwan - Yuan-Chien Lin; Tsang-Jung Chang; Mong-Ming Lu; Hwa-Lung Yu (Stochastic Environmental Research and Risk Assessment, 2015)

Intra-Colonial Functional Differentiation-Related Modulation of the Cellular Membrane in a Pocilloporid Coral Seriatopora caliendrum - Chuan-Ho Tang; Ping-Chang Ku; Ching-Yu Lin; Te-Hao Chen; Kuo-Hsin Lee; Shu-Hui Lee; Wei-Hsien Wang (Marine Biotechnology, 2015)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

The collective nuclear migration of p53 and phosphorylated S473 of Akt during ellipticine-mediated apoptosis in human lung epithelial cancer cells - Jing-Ping Wang; Ya-Chu Yu; Shih-Ping Chen; Huan-Chang Liang; Chia-Wei Lin; Kang Fang (Molecular and Cellular Biochemistry, 2015)

Metabolites of Scutellariae Radix Inhibit Injury of Endothelial Cells in Hypoxia Device - Chia-Lun Chao; Shiuan-Pey Lin; Yu-Chi Hou; Pei-Dawn Lee Chao; Nen-Chung Chang; Yu-Ching Huang; Feng-Ming Ho (Journal of Medical and Biological Engineering, 2015)

Response of shoot growth, photosynthetic capacity, flowering, and fruiting of potted ‘Nagami’ kumquat to different regulated deficit irrigation - Yung-Chiung Chang; Yu-Sen Chang; Lian-Hsiung Lin (Horticulture, Environment, and Biotechnology, 2015)

Effects of Polypropylene Carbonate/Poly(d,l-lactic) Acid/Tricalcium Phosphate Elastic Composites on Improving Osteoblast Maturation - Hsu-Wei Fang; Wei-Yu Kao; Pei-I Lin; Guang-Wei Chang; Ya-Jung Hung; Ruei-Ming Chen (Annals of Biomedical Engineering, 2015)

The differential roles of Slit2-exon 15 splicing variants in angiogenesis and HUVEC permeability - Yun-Chiu Yang; Pei-Ni Chen; Siou-Yu Wang; Chen-Yi Liao; Yu-Ying Lin; Shih-Rhong Sun; Chun-Ling Chiu; Yih-Shou Hsieh; Jia-Ching Shieh; Jinghua Tsai Chang (Angiogenesis, 2015)

Photodegradation of Alachlor Using BiVO4 Photocatalyst Under Visible Light Irradiation - Yi-Kuo Chang; Yu-Shen Wu; Chung-Shin Lu; Pei-Feng Lin; Tsung-Yen Wu (Water, Air, & Soil Pollution, 2015)

Genetic relationships and ecological divergence in Salix species and populations in Taiwan - Chun-Lin Huang; Chung-Te Chang; Bing-Hong Huang; Jeng-Der Chung; Jui-Hung Chen; Yu-Chung Chiang; Shih-Ying Hwang (Tree Genetics & Genomes, 2015)

Interaction of DRD2TaqI, COMT, and ALDH2 genes associated with bipolar II disorder comorbid with anxiety disorders in Han Chinese in Taiwan - Ming-Chuan Hu; Sheng-Yu Lee; Tzu-Yun Wang; Yun-Hsuan Chang; Shiou-Lan Chen; Shih-Heng Chen; Chun-Hsien Chu; Chen-Lin Wang; I Hui Lee; Po See Chen; Yen Kuang Yang; Ru-Band Lu (Metabolic Brain Disease, 2015)

Expression of Wnt/β-catenin signaling, stem-cell markers and proliferating cell markers in rat whisker hair follicles - Chang-min Lin; Yan-ping Yuan; Xian-cai Chen; Hai-hong Li; Bo-zhi Cai; Yang Liu; Huan Zhang; Yu Li; Keng Huang (Journal of Molecular Histology, 2015)

Surface Properties and In Vitro Bioactivity of Fluorapatite/TiO2 Coatings Deposited on Ti Substrates by Nd:YAG Laser Cladding - Chi-Sheng Chien; Yu-Sheng Ko; Tsung-Yuan Kuo; Tze-Yuan Liao; Huan-Chang Lin; Tzer-Min Lee; Ting-Fu Hong (Journal of Medical and Biological Engineering, 2015)

Phylogenetic and recombination analysis of rice black-streaked dwarf virus segment 9 in China - Yu Zhou; Jian-Feng Weng; Yan-Ping Chen; Chang-Lin Liu; Xiao-Hua Han; Zhuan-Fang Hao; Ming-Shun Li; Hong-Jun Yong; De-Gui Zhang; Shi-Huang Zhang; Xin-Hai Li (Archives of Virology, 2015)

Temperature‐sensitive fitness cost of insecticide resistance in C hinese populations of the diamondback moth P lutella xylostella - Lin Jie Zhang; Yu Pu Jing; Xiao Hui Li; Chang Wei Li; Denis Bourguet; Gang Wu (Molecular Ecology, 2015)
Alleles conferring a higher adaptive value in one environment may have a detrimental impact on fitness in another environment. Alleles conferring resistance to pesticides and drugs provide textbook examples of this trade‐off as, in addition to conferring resistance to these molecules, they frequently decrease fitness in pesticide/drug‐free environments. We show here that resistance to chlorpyrifos, an organophosphate ( OP ), in Chinese populations of the diamondback moth, Plutella xylostella , is conferred by two mutations of ace1 – the gene encoding the acetylcholinesterase enzyme targeted by OP s – affecting the amino acid sequence of the corresponding protein. These mutations were always linked, consistent with the segregation of a single resistance allele, ace1R , carrying both mutations, in the populations studied. We monitored the frequency of ace1R (by genotyping more than 20 000 adults) and the level of resistance (through bioassays on more than 50 000 individuals) over several generations. We found that the ace1R resistance allele was costly in the absence of insecticide and that this cost was likely recessive. This fitness costs involved a decrease in fecundity: females from resistant strains laid 20% fewer eggs, on average, than females from susceptible strains. Finally, we found that the fitness costs associated with the ace1R allele were greater at high temperatures. At least two life history traits were involved: longevity and fecundity. The relative longevity of resistant individuals was affected only at high temperatures and the relative fecundity of resistant females – which was already affected at temperatures optimal for development – decreased further at high temperatures. The implications of these findings for resistance management are discussed.

Methodology of disaster risk assessment for debris flows in a river basin - Ing-Jia Chiou; Ching-Ho Chen; Wei-Lin Liu; Shiao-Mei Huang; Yu-Min Chang (Stochastic Environmental Research and Risk Assessment, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Molecular cloning and identification of an ammonium transporter gene from pear - Hui Li; Yu Cong; Jing Lin; You Hong Chang (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

The versatile roles of CARDs in regulating apoptosis, inflammation, and NF-κB signaling - Wen-Pin Kao; Chao-Yu Yang; Tsung-Wei Su; Yin-Ting Wang; Yu-Chih Lo; Su-Chang Lin (Apoptosis, 2015)

Tandem DEDs and CARDs suggest novel mechanisms of signaling complex assembly - Yu-Chih Lo; Su-Chang Lin; Chao-Yu Yang; Jung-Yu Tung (Apoptosis, 2015)

Rhodococcus soli sp. nov., an actinobacterium isolated from soil using a resuscitative technique - Shan-Hui Li; Xiao-Yun Yu; Dong-Jin Park; Wael N. Hozzein; Chang-Jin Kim; Wen-Sheng Shu; Mohammed A. M. Wadaan; Lin-Xian Ding; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Allyl isothiocyanate (AITC) inhibits pregnane X receptor (PXR) and constitutive androstane receptor (CAR) activation and protects against acetaminophen- and amiodarone-induced cytotoxicity - Yun-Ping Lim; Ching-Hao Cheng; Wei-Cheng Chen; Shih-Yu Chang; Dong-Zong Hung; Jih-Jung Chen; Lei Wan; Wei-Chih Ma; Yu-Hsien Lin; Cing-Yu Chen; Tsuyoshi Yokoi; Miki Nakajima; et al. (Archives of Toxicology, 2015)

Genetic diversity and identification of race 3 of Fusarium oxysporum f. sp. lactucae in Taiwan - Ying-Hong Lin; Po-Jung Lai; Tao-Ho Chang; Yu-Ling Wan; Jenn-Wen Huang; Jin-Hsing Huang; Pi-Fang Linda Chang (European Journal of Plant Pathology, 2014)

Establishment of a structural equation model for ground-level ozone: a case study at an urban roadside site - Kun-Ming Lin; Tai-Yi Yu; Len-Fu Chang (Environmental Monitoring and Assessment, 2014)

Expression screening and annotation of Sepiella maindroni ink sac cDNA library - WEI-WEI SONG; CHANG-KAO MU; SHAO CHU; YU-YU ZHANG; PING-PING ZHAN; CHUN-LIN WANG (Journal of Genetics, 2014)

Characterization of ammonia gas release from concrete added with ammoniated fly ash - Lin Shou; Joshua Hayes; Weizhi Cheng; Chang-Yu Wu; Timothy Townsend; Tim Vinson; John Schert (Air Quality, Atmosphere & Health, 2014)

The effects of Typhoon Morakot on concentration of airborne particulates derived from unvegetated riverbanks - Kun-Ming Lin; Wang-Kun Chen; Tai-Yi Yu; Len-Fu Chang (Natural Hazards, 2014)

Identifying candidate genes for discrimination of ulcerative colitis and Crohn’s disease - Lian-Jie Lin; Ying Zhang; Yan Lin; Yu Jin; Chang-Qing Zheng (Molecular Biology Reports, 2014)

Spatial distribution of soil erosion and suspended sediment transport rate for Chou-Shui river basin - Chin-Ping Lin; Ching-Nuo Chen; Yu-Min Wang; Chih-Heng Tsai; Chang-Tai Tsai (Journal of Earth System Science, 2014)

Two Frequent Mutations Associated with the Classic Form of Propionic Acidemia in Taiwan - Yen-Hui Chiu; Yu-Ning Liu; Wei-Ling Liao; Ying-Chen Chang; Shuan-Pei Lin; Chia-Chi Hsu; Pao-Chin Chiu; Dau-Ming Niu; Chung-Hsing Wang; Yu-Yuan Ke; Yin-Hsiu Chien; Kwang-Jen Hsiao; et al. (Biochemical Genetics, 2014)

The capability of estuarine sediments to remove nitrogen: implications for drinking water resource in Yangtze Estuary - Lin Liu; Dongqi Wang; Huanguang Deng; Yangjie Li; Siqi Chang; Zhanlei Wu; Lin Yu; Yujie Hu; Zhongjie Yu; Zhenlou Chen (Environmental Science and Pollution Research, 2014)

Flammeopellis bambusicola gen. et. sp. nov. (Polyporales, Basidiomycota) evidenced by morphological characters and phylogenetic analysis - Chang-Lin Zhao; Xin-Sheng He; Kun-Yuan Wanghe; Bao-Kai Cui; Yu-Cheng Dai (Mycological Progress, 2014)

Concentrations of particulates in ambient air, gaseous elementary mercury (GEM), and particulate-bound mercury (Hg(p)) at a traffic sampling site: a study of dry deposition in daytime and nighttime - Guor-Cheng Fang; Yen-Heng Lin; Chia-Ying Chang; Yu-Cheng Zheng (Environmental Geochemistry and Health, 2014)

Investigation of key microRNAs associated with hepatocellular carcinoma using small RNA-seq data - Lian-Jie Lin; Yan Lin; Yu Jin; Chang-Qing Zheng (Molecular Biology Reports, 2014)

Investigating the interactive mechanisms between surface water and groundwater over the Jhuoshuei river basin in central Taiwan - Fi-John Chang; Cheng-Hsien Lin; Kuang-Chih Chang; Yu-Hsuan Kao; Li-Chiu Chang (Paddy and Water Environment, 2014)

Yeast Oropharyngeal Colonization in Human Immunodeficiency Virus-Infected Patients in Central Taiwan - Mao-Wang Ho; Yun-Liang Yang; Chih-Chao Lin; Chih-Yu Chi; Hui-Ting Chen; Po-Chang Lin; Li-Yun Hsieh; Chia-Hui Chou; Wen-Li Chu; Chiou-Pyng Wu; Tsai-Ling Lauderdale; Hsiu-Jung Lo (Mycopathologia, 2014)

Abundance and distribution of meiofauna in the Chukchi Sea - Rongcheng Lin; Dingyong Huang; Yuqing Guo; Yu Chang; Yinkun Cao; Jianjia Wang (Acta Oceanologica Sinica, 2014)

Genetic variations in TP53 binding sites are predictors of clinical outcomes in prostate cancer patients - Victor C. Lin; Chao-Yuan Huang; Yung-Chin Lee; Chia-Cheng Yu; Ta-Yuan Chang; Te-Ling Lu; Shu-Pin Huang; Bo-Ying Bao (Archives of Toxicology, 2014)

Genetic variation at 8q24, family history of cancer, and upper gastrointestinal cancers in a Chinese population - Heather P. Tarleton; Shen-Chih Chang; Sungshim Lani Park; Lin Cai; Baoguo Ding; Na He; Shehnaz K. Hussain; Qingwu Jiang; Li-Na Mu; Jianyu Rao; Hua Wang; Nai-Chieh Y. You; et al. (Familial Cancer, 2014)

Analysis of STCC eddies using the Okubo–Weiss parameter on model and satellite data - Yu-Lin Chang; Lie-Yauw Oey (Ocean Dynamics, 2014)

Gemifloxacin inhibits migration and invasion and induces mesenchymal–epithelial transition in human breast adenocarcinoma cells - Tun-Chieh Chen; Ya-Ling Hsu; Yu-Chieh Tsai; Yu-Wei Chang; Po-Lin Kuo; Yen-Hsu Chen (Journal of Molecular Medicine, 2014)

Telbivudine and adefovir combination therapy for patients with chronic lamivudine-resistant hepatitis B virus infections - Ming-Tsung Lin; Yeh-Pin Chou; Tsung-Hui Hu; Hsien-Chung Yu; Yu-Chun Hsu; Ming-Chao Tsai; Po-Lin Tseng; Kuo-Chin Chang; Yi-Hao Yen; King-Wah Chiu (Archives of Virology, 2014)

The role of MrbHLH1 and MrMYB1 in regulating anthocyanin biosynthetic genes in tobacco and Chinese bayberry (Myrica rubra) during anthocyanin biosynthesis - Xiao-Fen Liu; Xue-Ren Yin; Andrew C. Allan; Kui Lin-Wang; Yan-Na Shi; Yu-Ji Huang; Ian B. Ferguson; Chang-Jie Xu; Kun-Song Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

A pthA homolog from a variant of Xanthomonas axonopodis pv. citri enhances virulence without inducing canker symptom - Hsin-Cheng Lin; Yu-An Chang; Hsiang Chang (European Journal of Plant Pathology, 2013)

Aerosol characteristics of different types of episode - Chung-Yih Kuo; Yan-Ruei Lin; Shih-Yu Chang; Chuan-Yao Lin; Chun-Hung Chou (Environmental Monitoring and Assessment, 2013)

Ecological Risks Assessment and Pollution Source Identification of Trace Elements in Contaminated Sediments from the Pearl River Delta, China - Feng Li; Xiang-yun Zeng; Chang-hua Wu; Zhi-peng Duan; Yan-mao Wen; Guo-ru Huang; Xiao-lin Long; Min-Jian Li; Man-Jie Li; Jiang-Yu Xu (Biological Trace Element Research, 2013)

The effect of data quality on model performance with application to daily evaporation estimation - Ming-Chang Wu; Gwo-Fong Lin; Hsuan-Yu Lin (Stochastic Environmental Research and Risk Assessment, 2013)

Responses to booster hepatitis B vaccination are significantly correlated with genotypes of human leukocyte antigen (HLA)-DPB1 in neonatally vaccinated adolescents - Tzu-Wei Wu; Chen-Chung Chu; Tzu-Ying Ho; Huei-Wen Chang Liao; Sheng-Kai Lin; Marie Lin; Hans Hsienhong Lin; Li-Yu Wang (Human Genetics, 2013)

Immunologic Mechanism of Patchouli Alcohol Anti-H1N1 Influenza Virus May Through Regulation of the RLH Signal Pathway In Vitro - Xian-Lin Wu; Da-Hong Ju; Jia Chen; Bin Yu; Kang-Li Liu; Jin-Xiong He; Cong-Qi Dai; Sha Wu; Zhou Chang; You-Ping Wang; Xiao-Yin Chen (Current Microbiology, 2013)

The first complete genomic characterization of an Amur virus isolate from China - Yu Zhang; Bo-Hua Liu; Fang Lin; Yong-Guo Zhang; Bing-Yin Si; Xiao-Ping Kang; Yi Hu; Jing Li; Xiao-Yan Wu; Yu-Chang Li; Qing-Yu Zhu; Yin-Hui Yang (Archives of Virology, 2013)

Visualization of rodent brain tumor angiogenesis and effects of antiangiogenic treatment using 3D ΔR2-μMRA - Chien-Yuan Lin; Tiing Yee Siow; Ming-Huang Lin; Yi-Hua Hsu; Yu-Yin Tung; Taichang Jang; Lawrence Recht; Chen Chang (Angiogenesis, 2013)

Activating transcription factor 4 is involved in endoplasmic reticulum stress-mediated apoptosis contributing to vascular calcification - Xiao-Hui Duan; Jin-Rui Chang; Jing Zhang; Bao-Hong Zhang; Yu-Lin Li; Xu Teng; Yi Zhu; Jie Du; Chao-Shu Tang; Yong-Fen Qi (Apoptosis, 2013)

Identification and Characterization of an Extracellular Alkaline Phosphatase in the Marine Diatom Phaeodactylum tricornutum - Hung-Yun Lin; Chi-Yu Shih; Hung-Chun Liu; Jeng Chang; Ying-Lan Chen; Yet-Ran Chen; Han-Tso Lin; Yu-Yung Chang; Chun-Hua Hsu; Han-Jia Lin (Marine Biotechnology, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Particle swarm optimization algorithm for analyzing SNP–SNP interaction of renin-angiotensin system genes against hypertension - Shyh-Jong Wu; Li-Yeh Chuang; Yu-Da Lin; Wen-Hsien Ho; Fu-Tien Chiang; Cheng-Hong Yang; Hsueh-Wei Chang (Molecular Biology Reports, 2013)

Application of a web-based remote agro-ecological monitoring system for observing spatial distribution and dynamics of Bactrocera dorsalis in fruit orchards - Joe-Air Jiang; Tzu-Shiang Lin; En-Cheng Yang; Chwan-Lu Tseng; Chia-Pang Chen; Chung-Wei Yen; Xiang-Yao Zheng; Chun-Yi Liu; Ren-Hau Liu; Yu-Fan Chen; Wan-Yi Chang; Cheng-Long Chuang (Precision Agriculture, 2013)

Acid loading stimulates rat glomerular mesangial cells proliferation through Na+–H+ exchanger isoform 1 (NHE1)-dependent pathway - Kun Li; Wei Su; Man Li; Chang-jie Chen; Yong-yu Li; Lin-yun Lai; Ming-min Zhang; Shao-jun Liu; Jakub Fichna; Ai Peng; Chuan-ming Hao; Yong Gu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

A novel antitubulin agent, DPQZ, induces cell apoptosis in human oral cancer cells through Ras/Raf inhibition and MAP kinases activation - Mann-Jen Hour; Kun-Tsung Lee; Yang-Chang Wu; Chi-Yu Wu; Bang-Jau You; Tai-Lin Chen; Hong-Zin Lee (Archives of Toxicology, 2013)

Computer Aided Alignment and Quantitative 4D Structural Plasticity Analysis of Neurons - Ping-Chang Lee; Hai-yan He; Chih-Yang Lin; Yu-Tai Ching; Hollis T. Cline (Neuroinformatics, 2013)

Composition and Distribution of Elements and Ultrastructural Topography of a Human Cardiac Calculus - Ching-Li Cheng; Hsiao-Huang Chang; Pei-Jung Huang; Yu-Ting Chu; Shan-Yang Lin (Biological Trace Element Research, 2013)

A study of the frequency of methylation of gene promoter regions in colorectal cancer in the Taiwanese population - CHANG-CHIEH WU; JEN-CHUN KUAN; CHIH-HSIUNG HSU; TZU-AN CHEN; CHIEN-AN SUN; TSAN YANG; SHINN-LONG LIN; YU-CHING CHOU (Journal of Genetics, 2013)

Recent advances in the study of testicular nuclear receptor 4 - Xian-fan Ding; Shi-cheng Yu; Bi-de Chen; Shin-jen Lin; Chawnshang Chang; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2013)

Moscatilin inhibits migration and metastasis of human breast cancer MDA-MB-231 cells through inhibition of Akt and Twist signaling pathway - Hui-Chen Pai; Li-Hsun Chang; Chieh-Yu Peng; Ya-Ling Chang; Chien-Chih Chen; Chien-Chang Shen; Che-Ming Teng; Shiow-Lin Pan (Journal of Molecular Medicine, 2013)

The active alkaloids of Gelsemium elegans Benth. are potent anxiolytics - Ming Liu; Hui-Hui Huang; Jian Yang; Yan-Ping Su; Hong-Wei Lin; Li-Qing Lin; Wei-Jian Liao; Chang-Xi Yu (Psychopharmacology, 2013)

Glycogen synthase kinase-3β inactivation is an intracellular marker and regulator for endotoxemic neutrophilia - Tsan-Tzu Yang; Chia-Ling Chen; Wei-Chieh Lin; Yee-Shin Lin; Po-Chun Tseng; Chia-Yuan Hsieh; Yu-Hong Chen; Wei-Ching Huang; Cheng-Chieh Tsai; Chi-Yun Wang; Chi-Chang Shieh; Chiou-Feng Lin (Journal of Molecular Medicine, 2013)

A molecular diagnosis method using real-time PCR for quantification and detection of Fusarium oxysporum f. sp. cubense race 4 - Ying-Hong Lin; Ching-Chung Su; Chih-Ping Chao; Chi-Yu Chen; Chung-Jan Chang; Jenn-Wen Huang; Pi-Fang Linda Chang (European Journal of Plant Pathology, 2013)

Characterization and Expression of a Phytochelatin Synthase Gene in Birch-leaf Pear (Pyrus betulaefolia Bunge) - You Hong Chang; Hui Li; Yu Cong; Jing Lin; Bao Long Sheng (Plant Molecular Biology Reporter, 2012)

A Mucormycosis Case in a Cirrhotic Patient Successfully Treated with Posaconazole and Review of Published Literature - Shang-Yi Lin; Po-Liang Lu; Kun-Bow Tsai; Chun-Yu Lin; Wei-Ru Lin; Tun-Chieh Chen; Ya-Ting Chang; Chung-Hao Huang; Chi-Yu Chen; Chung-Chih Lai; Yen-Hsu Chen (Mycopathologia, 2012)

Heat acclimation decreased oxidative DNA damage resulting from exposure to high heat in an occupational setting - Yung-Kai Huang; Che-Wei Lin; Chen-Chen Chang; Pai-Fen Chen; Chien-Jen Wang; Yu-Mei Hsueh; Hung-Che Chiang (European Journal of Applied Physiology, 2012)

Recombined sequences between the non-coding control regions of JC and BK viruses found in the urine of a renal transplantation patient - Yu-Ching Liaw; Cheng-Hsu Chen; Kuo-Hsiung Shu; Chiung-Yao Fang; Wei-Chih Ou; Pei-Lain Chen; Cheng-Huang Shen; Mien-Chun Lin; Deching Chang; Meilin Wang (Virus Genes, 2012)

Strengthening of paleo‐typhoon and autumn rainfall in Taiwan corresponding to the Southern Oscillation at late Holocene - Huei‐Fen Chen; Shie‐Ying Wen; Shen‐Rong Song; Tien‐Nan Yang; Teh‐Quei Lee; Sue‐Fen Lin; Shih‐Chieh Hsu; Kuo‐Yen Wei; Ping‐Yu Chang; Pai‐Sen Yu (Journal of Quaternary Science, 2012)
The purpose of this study is to improve prehistoric knowledge of paleo‐typhoon and winter monsoon activity in the western North Pacific after 8 cal. ka BP. We examine two sediment cores derived from lakes located to the south and north of the Ilan Plain in northeastern Taiwan. Seasonal and typhoon rainfall data over the past several decades are collected for this study region. We also use mineral indicators, K/Rb ratios and grain size to estimate sediment sources, intensity of chemical weathering and rainfall intensity. The results show that the chemical weathering index (K/Rb ratio) of Meihua Lake indicates the continuing effects of autumn rainfall, while coarse grain sizes of Dahu Lake sediments suggest increased intensity in typhoon rainfall. Grain size results reveal that increasing El Niño–Southern Oscillation intensity in the tropical Pacific has intensified the activity of super typhoons in the western North Pacific. Finally, we find that frequent activity of super paleo‐typhoons occurred in Taiwan during the La Niña‐like state, and the strengthening winter monsoon activity and higher sea surface temperature enhanced plentiful autumn rainfall in El Niño‐like state. After comparing our results with the paleo‐typhoon data in Japan and south China, we suggest that the tracks of super typhoon are mainly affected by variations in the warm pool and subtropical Northwestern Pacific High in the western Pacific. Copyright © 2012 John Wiley & Sons, Ltd.

Albumin prevents reactive oxygen species-induced mitochondrial damage, autophagy, and apoptosis during serum starvation - Shu-Yu Liu; Chia-Ling Chen; Tsan-Tzu Yang; Wei-Ching Huang; Chia-Yuan Hsieh; Wan-Jou Shen; Tsung-Ting Tsai; Chi-Chang Shieh; Chiou-Feng Lin (Apoptosis, 2012)

The dissection and SSR mapping of a high-temperature adult-plant stripe rust resistance gene in American spring wheat cultivar Alturas - Lei Zhao; Jing Feng; Chun-Yu Zhang; Xiao-Dan Xu; Xian-Ming Chen; Quan Sun; Qing Miao; Shi-Chang Xu; Feng Lin (European Journal of Plant Pathology, 2012)

Cool seasons are related to poor prognosis in patients with infective endocarditis - Su-Jung Chen; Tze-Fan Chao; Yenn-Jiang Lin; Li-Wei Lo; Yu-Feng Hu; Ta-Chuan Tuan; Tsui-Lieh Hsu; Wen-Chung Yu; Hsin-Bang Leu; Shih-Lin Chang; Shih-Ann Chen (International Journal of Biometeorology, 2012)

Peroxisome Proliferator-Activated Receptor Gamma (PPAR-γ) and Neurodegenerative Disorders - Yu-Chang Chen; Jui-Sheng Wu; Hsin-Da Tsai; Chien-Yu Huang; Jin-Jer Chen; Grace Y. Sun; Teng-Nan Lin (Molecular Neurobiology, 2012)

Celecoxib inhibits growth of human autosomal dominant polycystic kidney cyst-lining epithelial cells through the VEGF/Raf/MAPK/ERK signaling pathway - Tao Xu; Nian-Song Wang; Li-Li Fu; Chao-Yang Ye; Sheng-Qiang Yu; Chang-Lin Mei (Molecular Biology Reports, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Oxidative stress in greater duckweed (Spirodela polyrhiza) caused by long-term NaCl exposure - In-Hwa Chang; Kai-Teng Cheng; Po-Chuan Huang; Yen-Yu Lin; Lee-Ju Cheng; Tai-Sheng Cheng (Acta Physiologiae Plantarum, 2012)

Growth and union acclimation process of sweet pepper grafted by a tubing-grafting robotic system - Yung-Chiung Chang; Suming Chen; Yi-Chich Chiu; Lian-Hsiung Lin; Yu-Sen Chang (Horticulture, Environment, and Biotechnology, 2012)

Microbial methane cycling in a terrestrial mud volcano in eastern Taiwan - Yung‐Hsin Chang; Ting‐Wen Cheng; Wen‐Jing Lai; Wen‐Yu Tsai; Chih‐Hsien Sun; Li‐Hung Lin; Pei‐Ling Wang (Environmental Microbiology, 2012)
Summary Microbial communities responsible for methane cycling in mud volcanoes onshore are poorly characterized. This study analysed bubbling fluids and cored sediments retrieved from a mud volcano in eastern Taiwan. The pore water profiles revealed that methane concentrations generally increased with depth and changed dramatically at different depth intervals at different sites. The methane concentrations were inversely correlated with Fe 2+ /Mn 2+ concentrations and δ 13 C values of methane, marking iron/manganese‐methane transition zones in the sediment cores. Archaeal communities were dominated by ANME‐2a members and methylotrophic methanogens, whereas bacterial communities consisted primarily of Proteobacteria, Firmicutes and Bacteroidetes . The 16S rRNA gene copy numbers of ANME‐2a and Desulfuromonas / Pelobacter populations varied by two to three orders of magnitude along the profile and exhibited a pattern comparable with those of Fe 2+ and δ 13 C values of methane. These lines of evidence suggest a coupling between anaerobic methanotrophy and metal reduction in the metal‐methane transition zones under sulfate‐deficient conditions, a metabolic scheme contrasting with that observed in marine cold seeps. Anaerobic methanotrophs proliferate by removing methane produced from in situ methanogenesis and originating from the deep source. Methane finally emitted into the atmosphere is quantitatively and isotopically altered by various microbial processes compartmentalized at different depth intervals.

Three-dimensional interpretation of sparse survey line MT data: Synthetic examples - Chang-Hong Lin; Han-Dong Tan; Qing Shu; Tuo Tong; Yu-Mei Zhang (Applied Geophysics, 2012)

HepG2 cells infected with Klebsiella pneumoniae show DNA laddering at apoptotic and necrotic stages - Pei-Yin Yang; Wen-Xin Chen; Fong-Yin Chang; Hui-Wen Chen; Chun-Hung Lin; Yu-Chun Hsu; June Hsieh Wu (Apoptosis, 2012)

Individual Management of Recurrent Intracranial Aneurysms: The Wuxi Experience - Lin Yu-chang; Santosh Kesari; Leng Bing; Ding Ya-suo; Pang Ming-zhi (Cell Biochemistry and Biophysics, 2011)

Phenotypic and molecular characterization of rhizobacterium Burkholderia sp. strain R456 antagonistic to Rhizoctonia solani, sheath blight of rice - Bin Li; Bao-Ping Liu; Rong-Rong Yu; Miao-Miao Lou; Yan-Li Wang; Guan-Lin Xie; Hong-Ye Li; Guo-Chang Sun (World Journal of Microbiology and Biotechnology, 2011)

Nitric oxide activates superoxide dismutase and ascorbate peroxidase to repress the cell death induced by wounding - Chih-Ching Lin; Pei-Ju Jih; Hsin-Hung Lin; Jeng-Shane Lin; Ling-Lan Chang; Yu-Hsing Shen; Shih-Tong Jeng (Plant Molecular Biology, 2011)

Biophysical studies of an NAD(P)+-dependent aldehyde dehydrogenase from Bacillus licheniformis - Huei-Fen Lo; Jian-Yu Su; Hsiang-Ling Chen; Jui-Chang Chen; Long-Liu Lin (European Biophysics Journal, 2011)

Frontal circulation induced by up-front and coastal downwelling winds - Yu-Lin Chang; Lie-Yauw Oey (Ocean Dynamics, 2011)

Relationship between temperature change and the requirement for a permanent pacemaker implantation in bradyarrhythmias - I-Fan Liu; Shih-Lin Chang; Li-Wei Lo; Yu-Feng Hu; Ta-Chuan Tuan; Chi-Woon Kong; Tsu-Juey Wu; Chern-En Chiang; Shih-Ann Chen; Yenn-Jiang Lin (International Journal of Biometeorology, 2011)

On the forced tangentially-averaged radial-vertical circulation within vortices. Part II: The transformation of Tropical Storm Haima (2004) - Yu-Kun Qian; Chang-Xia Liang; Qiaoqian Liang; Liangxun Lin; Zhuojian Yuan (Advances in Atmospheric Sciences, 2011)

Electrostatic droplets assisted synthesis of alginate microcapsules - Keng-Shiang Huang; Chih-Hui Yang; Yung-Sheng Lin; Chih-Yu Wang; Kang Lu; Yu-Fan Chang; Yi-Ling Wang (Drug Delivery and Translational Research, 2011)

Idebenone inhibition of glutamate release from rat cerebral cortex nerve endings by suppression of voltage-dependent calcium influx and protein kinase A - Yi Chang; Yu-Wan Lin; Su-Jane Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Estimation of nested spatial patterns and seasonal variation in the longitudinal distribution of Sicyopterus japonicus in the Datuan Stream, Taiwan by using geostatistical methods - Yu-Pin Lin; Cheng-Long Wang; Chi-Ru Chang; Hsiao-Hsuan Yu (Environmental Monitoring and Assessment, 2011)

2010 oil spill: trajectory projections based on ensemble drifter analyses - Yu-Lin Chang; Leo Oey; Fang-Hua Xu; Hung-Fu Lu; Ayumi Fujisaki (Ocean Dynamics, 2011)

A comparative study on arsenic and humic substances in alluvial aquifers of Bengal delta plain (NW Bangladesh), Chianan plain (SW Taiwan) and Lanyang plain (NE Taiwan): implication of arsenic mobilization mechanisms - A. H. M. Selim Reza; Jiin-Shuh Jean; Huai-Jen Yang; Ming-Kuo Lee; Hua-Fen Hsu; Chia-Chuan Liu; Yao-Chang Lee; Jochen Bundschuh; Kao-Hong Lin; Chi-Yu Lee (Environmental Geochemistry and Health, 2011)

National policy of watershed management and flood mitigation after the 921 Chi-Chi earthquake in Taiwan - Yong-Jun Lin; Yuan-Hsiou Chang; Yih-Chi Tan; Hong-Yuan Lee; Yu-Jia Chiu (Natural Hazards, 2011)

Effects of Tai Chi on adiponectin and glucose homeostasis in individuals with cardiovascular risk factors - Rei-Yeuh Chang; Malcolm Koo; Meng-Ying Ho; Zi-Zi Lin; Zer-Ran Yu; Yen-Fen Lin; Be-Jen Wang (European Journal of Applied Physiology, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

Human herpesvirus 8 viral FLICE-inhibitory protein retards cell proliferation via downregulation of Id2 and Id3 expression - Yi-Fen Wang; Lin-Yu Wang; Yi-Ling Li; Huey-Wen Shyu; Yee-Hsuan Chiou; Miao-Chen Chou; Kuan-Hua Lin; Ming-Hong Tai; Chang-Yu Chen (Molecular and Cellular Biochemistry, 2010)

Using a hybrid approach to optimize experimental network design for aquifer parameter identification - Liang-Cheng Chang; Hone-Jay Chu; Yu-Pin Lin; Yu-Wen Chen (Environmental Monitoring and Assessment, 2010)

The changes in different ozone metrics and their implications following precursor reductions over northern Taiwan from 1994 to 2007 - Yu-Kai Lin; Ta-Hsiung Lin; Shuenn-Chin Chang (Environmental Monitoring and Assessment, 2010)

The envelope glycoprotein domain III of dengue virus type 2 induced the expression of anticoagulant molecules in endothelial cells - Lien-Cheng Chen; Trai-Ming Yeh; Yi-Ying Lin; Yi-Fen Wang; Shu-Jem Su; Chang-Yu Chen; Kuan-Hua Lin; Miao-Chen Chou; Huey-Wen Shyu (Molecular and Cellular Biochemistry, 2010)

The functional expression of calcium-sensing receptor in the differentiated THP-1 cells - Yu-hui Xi; Hong-zhu Li; Wei-hua Zhang; Li-na Wang; Li Zhang; Yan Lin; Shu-zhi Bai; Hong-xia Li; Ling-yun Wu; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2010)

Planning for Implementation of Riparian Buffers in the Feitsui Reservoir Watershed - Chia-Ling Chang; Tsung-Hung Hsu; Yunn-Jiin Wang; Jen-Yang Lin; Shaw L. Yu (Water Resources Management, 2010)

Roles of cysteines Cys115 and Cys201 in the assembly and thermostability of grouper betanodavirus particles - Chun-Hsiung Wang; Chi-Hsin Hsu; Yi-Min Wu; Yu-Chun Luo; Mei-Hui Tu; Wei-hau Chang; R. Holland Cheng; Chan-Shing Lin (Virus Genes, 2010)

Genetic analysis of the VP1 region of enterovirus 71 reveals the emergence of genotype A in central China in 2008 - Haiyang Yu; Wei Chen; Hongwei Chang; Renshu Tang; Jun Zhao; Lin Gan; Boyu Liu; Jason Chen; Mingli Wang (Virus Genes, 2010)

E4BP4 is a cardiac survival factor and essential for embryonic heart development - Yi-Jiun Weng; Dennis Jine-Yuan Hsieh; Wei-Wen Kuo; Tung-Yuan Lai; Hsi-Hsien Hsu; Chang-Hai Tsai; Fuu-Jen Tsai; Ding-Yu Lin; James A. Lin; Chih-Yang Huang; Kwong-Chung Tung (Molecular and Cellular Biochemistry, 2010)

Reuse of return flow from wetland paddy to supplement industrial water needs - Yu‐Chuan Chang; Wei‐Taw Lin; Nien‐Sheng Hsu; Chun‐E. Kan (Irrigation and Drainage, 2010)
In this paper a water reuse system in wetland paddy was simulated to supply water for industry. A two‐tank model was employed to represent the return flow of the wetland paddy. Historical data were used for parameter estimation and model verification. The simulation results show that the return flow from wetland paddy has potential benefit for water reuse. Under a series of water management strategies, about 87% of the total volume of return flow can supplement industrial water needs which decreases local water needs by about 22.4%. The strategies include increasing the volume of return flow through deepwater management practices, stabilizing the reuse of return flow in the purification unit through the regulated large‐capacity pond downstream, and harmonizing the supply‐and‐demand gap through a suitable cultivated paddy scale of the crop rotation pattern. Apart from meeting water needs at peak demand periods, the reuse of return flow is a quick‐response water supply solution. Accompanied by the series of water management strategies, water reliability and crop security can be achieved at the same time. Copyright © 2009 John Wiley & Sons, Ltd.

Anti-apoptotic Actions of PPAR-γ Against Ischemic Stroke - Wen-Hsuan Fong; Hsin-Da Tsai; Yu-Chang Chen; Jui-Sheng Wu; Teng-Nan Lin (Molecular Neurobiology, 2010)

Application of System Dynamics on Shallow Multipurpose Artificial Lakes: A Case Study of Detention Pond at Tainan, Taiwan - Hone-Jay Chu; Liang-Cheng Chang; Yu-Pin Lin; Yung-Chieh Wang; Yu-Wen Chen (Environmental Modeling & Assessment, 2010)

Two genetic divergence centers revealed by chloroplastic DNA variation in populations of Cinnamomum kanehirae Hay - Dai-Chang Kuo; Chia-Chia Lin; Kuo-Chieh Ho; Yu-Pin Cheng; Shih-Ying Hwang; Tsan-Piao Lin (Conservation Genetics, 2010)

Probing the catalytically essential residues of a recombinant dipeptidyl carboxypeptidase from Escherichia coli - Huei-Fen Lo; Hsiang-Ling Chen; Shao-Yu Yen; Ping-Lin Ong; Wen-Shiue Chang; Chen-Tien Chang (Biologia, 2010)

Construction of a Genetic Linkage Map and Mapping of a Female-Specific DNA Marker in Half-Smooth Tongue Sole (Cynoglossus semilaevis) - Xiaolin Liao; Hong-Yu Ma; Gen-Bo Xu; Chang-Wei Shao; Yong-Sheng Tian; Xiang-Shan Ji; Jing-Feng Yang; Song-Lin Chen (Marine Biotechnology, 2009)

Erratum to: Role of the Conserved Thr399 and Thr417 Residues of Bacillus licheniformis γ-Glutamyltranspeptidase as Evaluated by Mutational Analysis - Rui-Cin Lyu; Hui-Yu Hu; Lih-Ying Kuo; Huei-Fen Lo; Ping-Lin Ong; Hui-Ping Chang; Long-Liu Lin (Current Microbiology, 2009)

Role of the Conserved Thr399 and Thr417 Residues of Bacillus licheniformis γ-Glutamyltranspeptidase as Evaluated by Mutational Analysis - Rui-Cin Lyu; Hui-Yu Hu; Lih-Ying Kuo; Huei-Fen Lo; Ping-Lin Ong; Hui-Ping Chang; Long-Liu Lin (Current Microbiology, 2009)

Isolation and characterization of 12 microsatellite loci from cutlassfish (Trichiurus haumela) - Jin-Zhen Bi; Chang-Wei Shao; Gui-Dong Miao; Hong-Yu Ma; Song-Lin Chen (Conservation Genetics, 2009)

Deletion analysis of the C-terminal region of a molecular chaperone DnaK from Bacillus licheniformis - Wan-Chi Liang; Min-Guan Lin; Meng-Chun Chi; Hui-Yu Hu; Huei-Fen Lo; Hui-Ping Chang; Long-Liu Lin (Archives of Microbiology, 2009)

A vitronectin M381T polymorphism increases risk of hemangioblastoma in patients with VHL gene defect - Jing-Shan Huang; Chih-Ming Lin; Yu-Che Cheng; Kun-Long Hung; Chih-Cheng Chien; Shao-Kuan Chen; Chih-Ju Chang; Chan-Wei Chen; Chi-Jung Huang (Journal of Molecular Medicine, 2009)

Development of polymorphic microsatellite markers from barfin flounder (Verasper moseri) and their cross-species amplification - Gui-Dong Miao; Chang-Wei Shao; Xiao-Lin Liao; Hong-Yu Ma; Yong-Sheng Tian; Song-Lin Chen (Conservation Genetics, 2009)

The effect of capillarisin on glycochenodeoxycholic acid-induced apoptosis and heme oxygenase-1 in rat primary hepatocytes - Tzung-Yan Lee; Fang-Yu Chen; Hen-Hong Chang; Han-Chieh Lin (Molecular and Cellular Biochemistry, 2009)

Recombinant ORF66 and ORFK12 antigens for the detection of human herpesvirus 8 antibodies in HIV-positive and -negative patients - Tsuey-Ching Yang; Chun-Pin Chang; Yu-Ching Lan; Chao-Li Liu; Mu-Chin Shih; Fang-Yang Wu; Cheng-Wen Lin (Biotechnology Letters, 2009)

Mechanical interactions of cuspal-coverage designs and cement thickness in a cusp-replacing ceramic premolar restoration: a finite element study - Yen-Hsiang Chang; Wen-Hsueng Lin; Wen-Chieh Kuo; Chia-Yu Chang; Chun-Li Lin (Medical & Biological Engineering & Computing, 2009)

The dipeptidyl carboxypeptidase of Escherichia coli novablue: overproduction and molecular characterization of the recombinant enzyme - Hsiang-Ling Chen; Chen-Tien Chang; Long-Liu Lin; Tein-Yu Li; Huei-Fen Lo (World Journal of Microbiology and Biotechnology, 2009)

Digenic inheritance of non-syndromic deafness caused by mutations at the gap junction proteins Cx26 and Cx31 - Xue-Zhong Liu; Yongyi Yuan; Denise Yan; Emilie Hong Ding; Xiao Mei Ouyang; Yu Fei; Wenxue Tang; Huijun Yuan; Qing Chang; Li Lin Du; Xin Zhang; Guojian Wang; et al. (Human Genetics, 2009)

Human mesenchymal stem cells-like cells as cellular vehicles for delivery of immunotoxin in vitro - Chang-chen Hu; Yi-quan Ke; Xin-lin Sun; Xiao-dan Jiang; Ru-xiang Xu; Jun Lv; Yu-sheng Wang; Ying-qian Cai; Ling-sha Qin; Yu-xi Zou (Biotechnology Letters, 2009)

Development of a Methodology for Strategic Environmental Assessment: Application to the Assessment of Golf Course Installation Policy in Taiwan - Ching-Ho Chen; Ray-Shyan Wu; Wei-Lin Liu; Wen-Ray Su; Yu-Min Chang (Environmental Management, 2009)

Effect of calmidazolium on [Ca2+]i and viability in human hepatoma cells - Wei-Chuan Liao; Chorng-Chih Huang; He-Hsiung Cheng; Jue-Long Wang; Ko-Long Lin; Jin-Shiung Cheng; Kuo-Liang Chai; Pei-Te Hsu; Jeng-Yu Tsai; Yi-Chien Fang; Yih-Chau Lu; Hong-Tai Chang; et al. (Archives of Toxicology, 2009)

Baicalein attenuates intimal hyperplasia after rat carotid balloon injury through arresting cell-cycle progression and inhibiting ERK, Akt, and NF-κB activity in vascular smooth-muscle cells - Chieh-Yu Peng; Shiow-Lin Pan; Ying-Wen Huang; Jih-Hwa Guh; Ya-Ling Chang; Che-Ming Teng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Genetic structure and diversity of cultivated soybean (Glycine max (L.) Merr.) landraces in China - Yinghui Li; Rongxia Guan; Zhangxiong Liu; Yansong Ma; Lixia Wang; Linhai Li; Fanyun Lin; Weijiang Luan; Pengyin Chen; Zhe Yan; Yuan Guan; Li Zhu; et al. (Theoretical and Applied Genetics, 2008)

Time to rehospitalization in patients with bipolar I disorder on lithium or valproate with adjunctive antipsychotics - Ching-Hua Lin; Ching-Wen Huang; Cheng-Chung Chen; Yu-Fen Hsu; Wen-Ho Chang; Hsien-Yuan Lane (Psychopharmacology, 2008)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Direct displacement-based design for seismic retrofit of existing buildings using nonlinear viscous dampers - Yu-Yuan Lin; Kuo-Chun Chang; Chang-Yu Chen (Bulletin of Earthquake Engineering, 2008)

Gene expression variation increase in trisomy 21 tissues - Ching Yu Chou; Li Yu Liu; Chien Yu Chen; Cheng Hsien Tsai; Hsiao Lin Hwa; Li Yun Chang; Yi Shing Lin; Fon Jou Hsieh (Mammalian Genome, 2008)

Anoxia survival in common carp and crucian carp is related to high zinc concentration in tissues - Sen Shyong JENG; Tzu Yung LIN; Ming Shyong WANG; Yu Yin CHANG; Chao Yi CHEN; Chih Chieh CHANG (Fisheries Science, 2008)

Attenuation by methyl mercury and mercuric sulfide of pentobarbital induced hypnotic tolerance in mice through inhibition of ATPase activities and nitric oxide production in cerebral cortex - Jiunn-Jye Chuu; Zih-Ning Huang; Hsun-Hsin Yu; Liang-Hao Chang; Shoei-Yn Lin-Shiau (Archives of Toxicology, 2008)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

The contents and forms of solid-phase species of radioactive strontium and cesium in Taiwan soils - S. W. Chang Chien; M. C. Wang; C. L. Chiu; Yu-Ming Lin; Shu-Ying Lai (Environmental Monitoring and Assessment, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Protoplast Fusion between Geotrichum candidium and Phanerochaete chrysosporium to Produce Fusants for Corn Stover Fermentation - Yong Zhang; Shu-Mei Lin; Yu-Jing Zhu; Chang-Jiang Liu; Yan Dong; Fang-Fang Li; Gao-Feng Wu; Hai-Yan Wang; Jing-Hai Zhang (Biotechnology Letters, 2006)

Assessing Impacts of Typhoons and the Chi-Chi Earthquake on Chenyulan Watershed Landscape Pattern in Central Taiwan Using Landscape Metrics - Yu-pin Lin; Tsun-kuo Chang; Chen-fa Wu; Te-chih Chiang; Shin-hwei Lin (Environmental Management, 2006)

Functional polymorphisms of FGA, encoding α fibrinogen, are associated with susceptibility to venous thromboembolism in a Taiwanese population - Yu-Lin Ko; Lung-An Hsu; Tsu-Shiu Hsu; Chia-Ti Tsai; Ming-Sheng Teng; Semon Wu; Chi-Jen Chang; Ying-Shiung Lee (Human Genetics, 2006)

Molecular analysis of increased iron status in moderately exercised rats - Yu Qian Liu; Xiang Lin Duan; Yan Zhong Chang; Hai Tao Wang; Zhong Ming Qian (Molecular and Cellular Biochemistry, 2006)

A Natural Compound (Ginsenoside Re) Isolated from Panax ginseng as a Novel Angiogenic Agent for Tissue Regeneration - Ya-Chun Huang; Chiung-Tong Chen; Sung-Ching Chen; Po-Hong Lai; Huang-Chien Liang; Yen Chang; Lin-Chien Yu; Hsing-Wen Sung (Pharmaceutical Research, 2005)

Antitermitic and Antifungal Activities of Essential Oil of Calocedrus formosana Leaf and Its Composition - Sen-Sung Cheng; Chi-Lin Wu; Hui-Ting Chang; Yu-Ting Kao; Shang-Tzen Chang (Journal of Chemical Ecology, 2004)

Intracellular expression of Vitreoscilla hemoglobin in Aspergillus terreus to alleviate the effect of a short break in aeration during culture - Yu-Hui Lin; Ywan-Feng Li; Min-Chang Huang; Ying-Chieh Tsai (Biotechnology Letters, 2004)

Study on construction of cDNA libraries from rat normal liver and regeneration liver with smart technique - Lin Jun-Tang; Wang Cong-Rui; Jogenananda Pramanik; Zhang Hui-Yong; Feng Hui-Gen; Yang Bao-Sheng; L. I. Yu-Chang; Xu Cun-Shuan (Indian Journal of Clinical Biochemistry, 2004)

Identification of essential histidine residues in a recombinant ?-amylase of thermophilic and alkaliphilic Bacillus sp. strain TS-23 - Chen-Tien Chang; Huei-Fen Lo; Meng-Chun Chi; Chia-Yu Yao; Wen-Hwei Hsu; Long-Liu Lin (Extremophiles, 2003)

Polychlorinated Biphenyls in Taiwanese Primipara Human Milk and Associated Factors - H.-R. Chao; S.-L. Wang; L.-Y. Lin; H.-Y. Yu; Y.-K. Lu; W.-L. Chou; Y.-L. Guo; L. W. Chang (Bulletin of Environmental Contamination and Toxicology, 2003)

Risk of hepatocellular carcinoma and habits of alcohol drinking, betel quid chewing and cigarette smoking: a cohort of 2416 HBsAg-seropositive and 9421 HBsAg-seronegative male residents in Taiwan - Li-Yu Wang; San-Lin You; Sheng-Nan Lu; Hsi-Chang Ho; Mei-Hui Wu; Chien-An Sun; Hwai-I Yang; Chien-Jen Chen (Cancer Causes & Control, 2003)

Replacement of Methionine 208 in a Truncated Bacillus sp. TS-23 α-Amylase with Oxidation-Resistant Leucine Enhances Its Resistance to Hydrogen Peroxide - Long-Liu Lin; Huei-Fen Lo; Wen-Ying Chiang; Hui-Yu Hu; Wen-Hwei Hsu; Chen-Tien Chang (Current Microbiology, 2003)

Nickel-induced oxidative stress and effect of antioxidants in human lymphocytes - Chang-Yu Chen; Yi-Fen Wang; Yu-Hwan Lin; Shu-Fang Yen (Archives of Toxicology, 2003)

Lipid peroxidation and cell death mechanisms in pulmonary epithelial cells induced by peroxynitrite and nitric oxide - Yuan-Soon Ho; Hung-Bin Liou; Jen-Kun Lin; Jiiang-Huei Jeng; Min-Hsiung Pan; Yu-Ping Lin; How-Ran Guo; Sheng-Yow Ho; Ching-Chang Lee; Ying-Jan Wang (Archives of Toxicology, 2002)

Identifications, Classification, and Evolution of the Vertebrate α-Amino-3-Hydroxy-5-Methyl-4-Isoxazole Propionic Acid (AMPA) Receptor Subunit Genes - Yu-Chia Chen; Shieh-Shiuh Kung; Bo-Yuan Chen; Chi-Chang Hung; Chun-Chen Chen; Tzi-Yuan Wang; Yi-Mi Wu; Wei-Hsiang Lin; Chyng-Shyan Tzeng; Wei-Yuan Chow (Journal of Molecular Evolution, 2001)

Decolorization kinetics of a recombinant Escherichia coli strain harboring azo-dye-decolorizing determinants from Rhodococcus sp. - Jo-Shu Chang; Chia-Yu Lin (Biotechnology Letters, 2001)

Chemical characters and antioxidative properties of sulfated polysaccharides from Laminaria japonica - Chang-Hu Xue; Yu Fang; Hong Lin; Lei Chen; Zhao-Jie Li; Deng Deng; Chong-Xiao Lu (Journal of Applied Phycology, 2001)

A Defective RNA Associated with Bamboo Mosaic Virus and the Possible Common Mechanisms for RNA Recombination in Potexviruses - Ting-Yu Yeh; Biing-Yuan Lin; Ya-Chun Chang; Yau-Heiu Hsu; Na-Sheng Lin (Virus Genes, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Effects of vitamin A pretreatment on nickel-induced lipid peroxidation and concentration of essential metals in liver, kidney and lung of mice - Chang-Yu Chen; Yeou-Lih Huang; Te-Hsien Lin (Archives of Toxicology, 1998)

lipid peroxidation in liver of mice administrated with nickel chloride - Chang-Yu Chen; Yeou-Lih Huang; Te-Hsien Lin (Biological Trace Element Research, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)